3D high-speed multifocal multiphoton microscopy in muscle and wavelet analysis of fast elementary calcium release events - Von Wegner, Frederic; Both, Martin; Fink, Rainer; Friedrich, Oliver (2006 3rd IEEE International Symposium on Biomedical Imaging: From Nano to Macro, 2006)
Recent approaches to record and analyze skeletal muscle elementary calcium release events (ECRE) in three dimensions (XYT) were restricted to short time series and small areas of interest. Here, we present a combined method for XYT analysis of ECRE using high-speed multifocal multiphoton calcium imaging and a wavelet based automated denoising and detection algorithm. Images were analyzed with the 'à trous' implementation of the wavelet transform. 'Hardthreshold' wavelet denoising resulted in markedly improved signal-to-noise ratios compared to low-pass filtering. Automated detection of ECRE was performed across wavelet scales and single events were tracked within an image sequence using 3D segmentation. With this combined approach, the morphological dynamics of fast ECRE in mammalian skeletal muscle fibres could be faithfully monitored with high spatial and temporal resolution. Our method may provide an improved tool for the facilitated detection of ECRE in muscle in three dimensions even under conditions of undisturbed calcium homeostasis. © 2006 IEEE.

3D printed gelatin/decellularized bone composite scaffolds for bone tissue engineering: Fabrication, characterization and cytocompatibility study - Kara, Aylin; Distler, Thomas; Polley, Christian; Schneidereit, Dominik; Seitz, Hermann; Friedrich, Oliver; Tihminlioglu, Funda; Boccaccini, Aldo R. (Materials Today Bio, 2022)
Three-dimensional (3D) printing technology enables the design of personalized scaffolds with tunable pore size and composition. Combining decellularization and 3D printing techniques provides the opportunity to fabricate scaffolds with high potential to mimic native tissue. The aim of this study is to produce novel decellularized bone extracellular matrix (dbECM)-reinforced composite-scaffold that can be used as a biomaterial for bone tissue engineering. Decellularized bone particles (dbPTs, 100 mu m diameter) were obtained from rabbit femur and used as a reinforcement agent by mixing with gelatin (GEL) in different concentrations. 3D scaffolds were fabricated by using an extrusion-based bioprinter and crosslinking with microbial transglutaminase (mTG) enzyme, followed by freeze-drying to obtain porous structures. Fabricated 3D scaffolds were characterized morphologically, mechanically, and chemically. Furthermore, MC3T3-E1 mouse pre-osteoblast cells were seeded on the dbPTs reinforced GEL scaffolds (GEL/dbPTs) and cultured for 21 days to assess cytocompatibility and cell attachment. We demonstrate the 3D-printability of dbPTs-reinforced GEL hydrogels and the achievement of homogenous distribution of the dbPTs in the whole scaffold structure, as well as bioactivity and cytocompatibility of GEL/dbPTs scaffolds. It was shown that Young's modulus and degradation rate of scaffolds were enhanced with increasing dbPTs content. Multiphoton microscopy imaging displayed the interaction of cells with dbPTs, indicating attachment and proliferation of cells around the particles as well as into the GEL-particle hydrogels. Our results demonstrate that GEL/dbPTs hydrogel formulations have potential for bone tissue engineering.
CRIS-Team WoS Importer:2022-07-15

3D printed lab-on-a-chip platform for chemical stimulation and parallel analysis of ion channel function - Aschenbrenner, Daniel; Friedrich, Oliver; Gilbert, Daniel (Micromachines, 2019)
Functional imaging has been a widely established method for the assessment of ion channel function in vitro. Conventional infrastructure used for in vitro functional analysis of ion channels is typically proprietary, non-customizable, expensive, and requires a high level of skill to use and maintain. 3D desktop printing, which is employed in the rapid prototyping field, allows for quick engineering of alternatives to conventional imaging infrastructure that are customizable, low cost, and user friendly. Here, we describe an ultra-low-cost microfluidic lab-on-a-chip (LOC) device manufactured using acrylonitrile butadiene styrene (ABS) for in vitro functional imaging of ion channels that can quickly and easily be reconstructed using three-dimensional (3D) desktop printing. The device is light weight (< 5 g), small (20 mm × 49 mm), and extremely low cost (< EUR 1). We simulate fluidics within the printed channels and assess the suitability of the engineered chamber to generate homogeneous mixtures during solution exchange. We demonstrate the usability of the 3D printed microfluidic device in a case study using Fluo-4-loaded human embryonal kidney-derived (HEK293) cells, recombinantly expressing the capsaicin receptor, transient receptor potential vanilloid receptor type 1 (TRPV1), as a model system. In the case study, we confirm its applicability to solution exchange for chemical stimulation and parallel functional time-lapse fluorescence microscopy-based calcium imaging. We assess the suitability of ABS for culturing HEK293 cells inside the microfluidic LOC, based on qualitative analysis of microscopic transmission light images of ABS-exposed HEK293 cells and confirm the previously reported biocompatibility of ABS. To highlight the versatility of the 3D printed microfluidic device, we provide an example for multiplication of the shown concept within a 3D printed multichannel microfluidic LOC to be used, for example, in a higher throughput format for parallelized functional analysis of ion channels. While this work focusses on Ca2+ imaging with TRPV1 channels, the device may also be useful for application with other ion channel types and in vitro models.
CRIS-Team Scopus Importer:2019-08-30
Keywords: 3D printing; ABS; Ca; Capsaicin; Fluo-4 AM; HEK293 cells; Microfluidic; TRPV1; Zigzag channel

3D printed oxidized alginate-gelatin bioink provides guidance for C2C12 muscle precursor cell orientation and differentiation via shear stress during bioprinting - Distler, Thomas; Solisito, Aditya; Schneidereit, Dominik; Friedrich, Oliver; Detsch, Rainer; Boccaccini, Aldo R. (Biofabrication, 2020)
Biofabrication can be a tool to three-dimensionally (3D) print muscle cells embedded inside hydrogel biomaterials, ultimately aiming to mimic the complexity of the native muscle tissue and to createin-vitromuscle analogues for advanced repair therapies and drug testing. However, to 3D print muscle analogues of high cell alignment and synchronous contraction, the effect of biofabrication process parameters on myoblast growth has to be understood. A suitable biomaterial matrix is required to provide 3D printability as well as matrix degradation to create space for cell proliferation, matrix remodelling capacity, and cell differentiation. We demonstrate that by the proper selection of nozzle size and extrusion pressure, the shear stress during extrusion-bioprinting of mouse myoblast cells (C2C12) can achieve cell orientation when using oxidized alginate-gelatin (ADA-GEL) hydrogel bionk. The cells grow in the direction of printing, migrate to the hydrogel surface over time, and differentiate into ordered myotube segments in areas of high cell density. Together, our results show that ADA-GEL hydrogel can be a simple and cost-efficient biodegradable bioink that allows the successful 3D bioprinting and cultivation of C2C12 cellsin-vitroto study muscle engineering.
Keywords: myoblasts; muscle tissue engineering; 3D printing; oxidized alginate; gelatin; hydrogel

3D-Printed Reusable Cell Culture Chamber with Integrated Electrodes for Electrical Stimulation and Parallel Microscopic Evaluation - Schneidereit, Dominik; Tschernich, Jessica; Friedrich, Oliver; Scharin-Mehlmann, Marina; Gilbert, Daniel (3D Printing and Additive Manufacturing, 2018)
Electrical stimulation of mammalian cells in vitro, including stem or neuronal cells and myocytes, has been a widely established method for assessing physiological or pathophysiological mechanisms in a variety of fields of research. Conventional infrastructure used in in vitro electrical stimulation experiments is typically proprietary, noncustomizable, costly, and requires a high level of skill to use and maintain. The emergence of rapid prototyping technology makes it possible to quickly engineer alternatives to conventional stimulation infrastructure that are open source, customizable, low cost, and user friendly. In this study, we describe the rapid prototype of a three- dimensional (3D)-printed reusable growth chamber with integrated electrodes for electrical stimulation and parallel microscopic evaluation of cultured cells that can easily be reconstructed within a few hours using 3D desktop printing and off-the-shelf components. The chamber is light weight (similar to 8 g), small ( 76 x 26 x 6 mm), and extremely low cost (< EUR 1). We demonstrate the applicability of the printed device for maintenance of in vitro cultures as well as for electrical and chemical stimulation using the conditionally immortal dorsal root ganglia cell line MED17.11 as a model system. The applicability for microscopic evaluation was demonstrated by time-resolved high-content imaging of the intracellular calcium concentration as a measure of stimulation-induced membrane depolarization. We provide a comprehensive parts list, 3D design files, a wiring diagram, and software code for rebuilding the cost-effective infrastructure for electrical and/or chemical stimulation and parallel high-content microscopy of cells in vitro. While this work focuses on electrical stimulation of mammalian cells, the presented technology could also be adapted for use with other biological specimens and provides a general example of rapidly prototyped low-cost biotechnology for application in life sciences and education.
Keywords: 3D desktop printing; conductive filament; PLA; electrical stimulation; Fluo-4 AM; MED17.11 dorsal root ganglia cell line; Arduino; LabVIEW

3D printing of piezoelectric and bioactive barium titanate-bioactive glass scaffolds for bone tissue engineering - Polley, Christian; Distler, Thomas; Scheufler, Caroline; Detsch, Rainer; Lund, Henrik; Springer, Armin; Schneidereit, Dominik; Friedrich, Oliver; Boccaccini, Aldo R.; Seitz, Hermann (Materials Today Bio, 2023)
Bone healing is a complex process orchestrated by various factors, such as mechanical, chemical and electrical cues. Creating synthetic biomaterials that combine several of these factors leading to tailored and controlled tissue regeneration, is the goal of scientists worldwide. Among those factors is piezoelectricity which creates a physiological electrical microenvironment that plays an important role in stimulating bone cells and fostering bone regeneration. However, only a limited number of studies have addressed the potential of combining piezoelectric biomaterials with state-of-the-art fabrication methods to fabricate tailored scaffolds for bone tissue engineering. Here, we present an approach that takes advantage of modern additive manufacturing techniques to create macroporous biomaterial scaffolds based on a piezoelectric and bioactive ceramic-crystallised glass composite. Using binder jetting, scaffolds made of barium titanate and 45S5 bioactive glass are fabricated and extensively characterised with respect to their physical and functional properties. The 3D-printed ceramic-crystallised glass composite scaffolds show both suitable mechanical strength and bioactive behaviour, as represented by the accumulation of bone-like calcium phosphate on the surface. Piezoelectric scaffolds that mimic or even surpass bone with piezoelectric constants ranging from 1 to 21 pC/N are achieved, depending on the composition of the composite. Using MC3T3-E1 osteoblast precursor cells, the scaffolds show high cytocompatibility coupled with cell attachment and proliferation, rendering the barium titanate/45S5 ceramic-crystallised glass composites promising candidates for bone tissue engineering.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 3D printing; Barium titanate; Bioactivity; Bone regeneration; Piezoelectricity

4Pi-SHG imaging of mammalian myofibrillar structures - Vogel, Martin; Hahn, Dorothea; Schürmann, Sebastian; Lang, Marion; von Wegner, Frederic; Friedrich, Oliver; Engelhardt, Johann; Hell, Stefan; Fink, Rainer (Multiphoton Microscopy in the Biomedical Sciences VI, 2006)
Intrinsic Second Harmonic Generation (SHG) signals obtained from the motor protein myosin are of particular interest for 3D-imaging of living muscle cells. In addition, the new and powerful tool of 4Pi microscopy allows to markedly enhance the optical resolution of microscopy as well as the sensitivity for small objects because of the high peak intensities due to the interference pattern created in the focus. In the present study, we report, to our knowledge for the first time, measurements of intrinsic SHG signals under 4Pi conditions of type A. These measurements on mammalian myofibrilar structures are combined with very high resolution 4Pi fluorescence data obtained from the same preparations. We have chosen myofibrillar preparations of isolated mammalian muscle fibers as they (i) possess a regular repetitive pattern of actin and myosin filaments within sarcomers 2 to 3 mu;m in length, (ii) consist of single myofibrils of small total diameter of approximately 1 mu;m and (iii) are ideally suited to study the biomedically important process of force generation via calcium regulated motor protein interactions. Myofibrillar preparations were obtained from murine skeletal and heart muscle by using a combined chemical and mechanical fractionation (Both et al. 2004, JBO 9(5):882-892). BODIPY FL phallacidin has been used to fluorescently label the actin filaments. The experiments were carried out with a Leica SP2 multi photon microscope modified for 4Pi measurements using a Ti:Sa laser tuned to 850-900 nm. SHG as well as fluorescence photons were detected confocally by a counting APD detector. The approach taken our study provides new 3D-data for the analysis and simulation of the important process of excitation-contraction coupling under normal physiological as well as under pathophysiological conditions.
Keywords: 4Pi; Mammalian skeletal muscle; Second harmonic generation

Absence of the Z-disc protein α-actinin-3 impairs the mechanical stability of Actn3KO mouse fast-twitch muscle fibres without altering their contractile properties or twitch kinetics - Haug, Michael; Reischl, Barbara; Nübler, Stefanie; Kiriaev, Leonit; Mázala, Davi A.G.; Houweling, Peter J.; North, Kathryn N.; Friedrich, Oliver; Head, Stewart I. (Skeletal Muscle, 2022)
Background: A common polymorphism (R577X) in the ACTN3 gene results in the complete absence of the Z-disc protein α-actinin-3 from fast-twitch muscle fibres in 16% of the world’s population. This single gene polymorphism has been subject to strong positive selection pressure during recent human evolution. Previously, using an Actn3KO mouse model, we have shown in fast-twitch muscles, eccentric contractions at L0 + 20% stretch did not cause eccentric damage. In contrast, L0 + 30% stretch produced a significant 40% deficit in maximum force; here, we use isolated single fast-twitch skeletal muscle fibres from the Actn3KO mouse to investigate the mechanism underlying this. Methods: Single fast-twitch fibres are separated from the intact muscle by a collagenase digest procedure. We use label-free second harmonic generation (SHG) imaging, ultra-fast video microscopy and skinned fibre measurements from our MyoRobot automated biomechatronics system to study the morphology, visco-elasticity, force production and mechanical strength of single fibres from the Actn3KO mouse. Data are presented as means ± SD and tested for significance using ANOVA. Results: We show that the absence of α-actinin-3 does not affect the visco-elastic properties or myofibrillar force production. Eccentric contractions demonstrated that chemically skinned Actn3KO fibres are mechanically weaker being prone to breakage when eccentrically stretched. Furthermore, SHG images reveal disruptions in the myofibrillar alignment of Actn3KO fast-twitch fibres with an increase in Y-shaped myofibrillar branching. Conclusions: The absence of α-actinin-3 from the Z-disc in fast-twitch fibres disrupts the organisation of the myofibrillar proteins, leading to structural weakness. This provides a mechanistic explanation for our earlier findings that in vitro intact Actn3KO fast-twitch muscles are significantly damaged by L0 + 30%, but not L0 + 20%, eccentric contraction strains. Our study also provides a possible mechanistic explanation as to why α-actinin-3-deficient humans have been reported to have a faster decline in muscle function with increasing age, that is, as sarcopenia reduces muscle mass and force output, the eccentric stress on the remaining functional α-actinin-3 deficient fibres will be increased, resulting in fibre breakages.
CRIS-Team Scopus Importer:2022-07-01
Keywords: a-Actinin-3; Biomechatronics; Biosensors; Exercise; Myorobotics; Sarcoplasmic reticulum; Single fibre; Skeletal muscle; Skinned fibre

Access to Artemisinin-Triazole Antimalarials via Organo-Click Reaction: High In Vitro/In Vivo Activity against Multi-Drug-Resistant Malaria Parasites - Herrmann, Lars; Leidenberger, Maria; Quadros, Helenita C.; Grau, Benedikt; Hampel, Frank; Friedrich, Oliver; Moreira, Diogo R.M.; Kappes, Bärbel; Tsogoeva, Svetlana (JACS Au, 2024)
Malaria is one of the most widespread diseases worldwide. Besides a growing number of people potentially threatened by malaria, the consistent emergence of resistance against established antimalarial pharmaceuticals leads to an urge toward new antimalarial drugs. Hybridization of two chemically diverse compounds into a new bioactive product is a successful concept to improve the properties of a hybrid drug relative to the parent compounds and also to overcome multidrug resistance. 1,2,3-Triazoles are a significant pharmacophore system among nitrogen-containing heterocycles with various applications, such as antiviral, antimalarial, antibacterial, and anticancer agents. Several marketed drugs possess these versatile moieties, which are used in a wide range of medical indications. While the synthesis of hybrid compounds containing a 1,2,3-triazole unit was described using Cu- and Ru-catalyzed azide-alkyne cycloaddition, an alternative metal-free pathway has never been reported for the synthesis of antimalarial hybrids. However, a metal-free pathway is a green method that allows toxic and expensive metals to be replaced with an organocatalyst. Herein, we present the synthesis of new artemisinin-triazole antimalarial hybrids via a facile Ramachary-Bressy-Wang organocatalyzed azide-carbonyl [3 + 2] cycloaddition (organo-click) reaction. The prepared new hybrid compounds are highly potent in vitro against chloroquine (CQ)-resistant and multi-drug-resistant Plasmodium falciparum strains (IC50 (Dd2) down to 2.1 nM; IC50 (K1) down to 1.8 nM) compared to CQ (IC50 (Dd2) = 165.3 nM; IC50 (K1) = 302.8 nM). Moreover, the most potent hybrid drug was more efficacious in suppressing parasitemia and extending animal survival in Plasmodium berghei-infected mice (up to 100% animal survival and up to 40 days of survival time) than the reference drug artemisinin, illustrating the potential of the hybridization concept as an alternative and powerful drug-discovery approach.
CRIS-Team Scopus Importer:2024-04-05
Keywords: artemisinin-triazole hybrids; in vitro/in vivo studies; multi-drug-resistant malaria; organo-click reaction

Access to new highly potent antileukemia, antiviral and antimalarial agents via hybridization of natural products (homo)egonol, thymoquinone and artemisinin - Capci Karagöz, Aysun; Reiter, Christoph; Seo, Ean-Jeong; Gruber, Lisa; Hahn, Friedrich; Leidenberger, Maria; Klein, Volker; Hampel, Frank; Friedrich, Oliver; Marschall, Manfred; Kappes, Bärbel; Efferth, Thomas; et al. (Bioorganic & Medicinal Chemistry, 2018)
Hybridization of natural products has high potential to further improve their activities and may produce synergistic effects between linked pharmacophores. Here we report synthesis of nine new hybrids of natural products egonol, homoegonol, thymoquinone and artemisinin and evaluation of their activities against P. falciparum 3D7 parasites, human cytomegalovirus, sensitive and multidrug-resistant human leukemia cells. Most of the new hybrids exceed their parent compounds in antimalarial, antiviral and antileukemia activities and in some cases show higher in vitro efficacy than clinically used reference drugs chloroquine, ganciclovir and doxorubicin. Combined, our findings stress the high potency of these hybrids and encourages further use of the hybridization concept in applied pharmacological research.
EVALuna2:35269

Acidified nitrite contributes to the antitumor effect of cold atmospheric plasma on melanoma cells - Zimmermann, Tom; Gebhardt, Lisa; Kreiß, Lucas; Schneider, Christin; Arndt, Stephanie; Karrer, Sigrid; Friedrich, Oliver; Fischer, Michael Jochen Marco; Boßerhoff, Anja Katrin (International Journal of Molecular Sciences, 2021)
Cold atmospheric plasma (CAP) is partially ionized gas near room temperature with previously reported antitumor effects. Despite extensive research and growing interest in this technol-ogy, active components and molecular mechanisms of CAP are not fully understood to date. We used Raman spectroscopy and colorimetric assays to determine elevated nitrite and nitrate levels after treatment with a MiniFlatPlaster CAP device. Previously, we demonstrated CAP-induced acidification. Cellular effects of nitrite and strong extracellular acidification were assessed using live-cell imaging of intracellular Ca2+ levels, cell viability analysis as well as quantification of p21 and DNA damage. We further characterized these observations by analyzing established molecular effects of CAP treatment. A synergistic effect of nitrite and acidification was found, leading to strong cytotoxicity in melanoma cells. Interestingly, protein nitration and membrane damage were absent after treatment with acidified nitrite, thereby challenging their contribution to CAP-induced cyto-toxicity. Further, phosphorylation of ERK1/2 was increased after treatment with both acidified ni-trite and indirect CAP. This study characterizes the impact of acidified nitrite on melanoma cells and supports the importance of RNS during CAP treatment. Further, it defines and evaluates im-portant molecular mechanisms that are involved in the cancer cell response to CAP.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Acidification; Acidified nitrite; Cold atmospheric plasma; Malignant melanoma; Membrane damage; Nitration; Nitrite

Adding dimension to cellular mechanotransduction: Advances in biomedical engineering of multiaxial cell-stretch systems and their application to cardiovascular biomechanics and mechano-signaling. - Friedrich, Oliver; Schneidereit, Dominik; Nikolaev, Y. A.; Nikolova-Krstevski, V.; Schürmann, Sebastian; Wirth-Hücking, Anette; Merten, Anna-Lena; Fatkin, D.; Martinac, B. (Progress in biophysics and molecular biology, 2017)
Hollow organs (e.g. heart) experience pressure-induced mechanical wall stress sensed by molecular mechano-biosensors, including mechanosensitive ion channels, to translate into intracellular signaling. For direct mechanistic studies, stretch devices to apply defined extensions to cells adhered to elastomeric membranes have stimulated mechanotransduction research. However, most engineered systems only exploit unilateral cellular stretch. In addition, it is often taken for granted that stretch applied by hardware translates 1:1 to the cell membrane. However, the latter crucially depends on the tightness of the cell-substrate junction by focal adhesion complexes and is often not calibrated for. In the heart, (increased) hemodynamic volume/pressure load is associated with (increased) multiaxial wall tension, stretching individual cardiomyocytes in multiple directions. To adequately study cellular models of chronic organ distension on a cellular level, biomedical engineering faces challenges to implement multiaxial cell stretch systems that allow observing cell reactions to stretch during live-cell imaging, and to calibrate for hardware-to-cell membrane stretch translation. Here, we review mechanotransduction, cell stretch technologies from uni-to multiaxial designs in cardio-vascular research, and the importance of the stretch substrate-cell membrane junction. We also present new results using our IsoStretcher to demonstrate mechanosensitivity of Piezo1 in HEK293 cells and stretch-induced Ca(2+) entry in 3D-hydrogel-embedded cardiomyocytes.

A fluorescence-based opto-mechatronic screening module (OMSM) for automated 3D cell culture workflows - Kahl, Melanie; Schneidereit, Dominik; Meinert, Christoph; Bock, Nathalie; Hutmacher, Dietmar W.; Friedrich, Oliver (Biosensors and Bioelectronics: X, 2023)
Cost-effective automated solutions for hydrogel-based 3D cell culture workflows are required to increase throughput, reproducibility and user-independent results. 3D bioprinters can handle viscous biomaterials, however, throughput is low, they are limited to specific biomaterials, and lack post-processing and analysis methods. Conversely, liquid handling robots have higher throughput but miss viscous materials handling capabilities. Furthermore, commercial systems are not only expensive but mostly not ‘open-source’ and hence are not adaptable to specific experimental requirements. The aim of this study was the implementation of an opto-mechatronic screening module (OMSM) for automated 3D cell culture workflows from production to analysis into a previously developed biomanufacturing workstation. An analysis module with a fluorescence wide-field microscope and a motorised XYZ stage was engineered to transport tissue-culture plates from the storage rack of the workstation to the custom-made microscope and to assess fluorescence-based cell parameters. The microscope has two fluorescence channels and a resolution greater than 228 lp/mm. The XYZ-stage achieved an accuracy of 0.8 μm in X-direction (repeatability 2.4 μm) and 1.4 μm in Z-direction (repeatability <0.1 μm). Viability assays and drug-response studies were conducted on 2D and 3D prostate cancer gelatin-methacryloyl hydrogel models demonstrating its capabilities comparable to a conventional fluorescence microscope. Altogether, the integration of an opto-mechatronic screening module into the biomanufacturing workstation enables automated, reproducible, and user-independent production, imaging and analysis of hydrogel-based 3D cell cultures.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Automation; Fluorescence microscope; High-throughput; Hydrogel-based 3D culture models; Open-source; Opto-mechatronic

Aging-related progressive skeletal muscle weakness in mutant DesR349P muscles: a matter of compromised cytoarchitecture - Diermeier, Stefanie; Buttgereit, Andreas; Clemen, CS; Schröder, Rolf; Friedrich, Oliver (Acta Physiologica, 2016)

A low-cost uniaxial cell stretcher for six parallel wells - Kah, Delf-Thorge Eric; Winterl, Alexander; Přechová, Magdalena; Schöler, Ulrike; Schneider, Werner; Friedrich, Oliver; Gregor, Martin; Fabry, Ben (HardwareX, 2021)
Cells in the lungs, the heart, and numerous other organs, are constantly exposed to dynamic forces and deformations. To mimic these dynamic mechanical loading conditions and to study the resulting cellular responses such as morphological changes or the activation of biochemical signaling pathways, cells are typically seeded on flexible 2D substrates that are uniaxially or biaxially stretched. Here, we present an open-source cell stretcher built from parts of an Anet A8 3D printer. The cell stretcher is controlled by a fully programmable open-source software using GCode and Python. Up to six flexible optically clear substrates can be stretched simultaneously, allowing for comparative multi-batch biological studies including microscopic image analysis. The cell yield from the cell culture area of 4 cm2 per substrate is sufficient for Western-blot protein analysis. As a proof-of-concept, we study the activation of the Yes-associated protein (YAP) mechanotransduction pathway in response to increased cytoskeletal tension induced by uniaxial stretching of epithelial cells. Our data support the previously observed activation of the YAP transcription pathway by stretch-induced increase in cytoskeletal tension and demonstrate the suitability of the cell stretcher to study complex mechano-biological processes.
CRIS-Team Scopus Importer:2021-01-01
Keywords: 3D printer; Cell Mechanics; Cell stretcher; Mechanosensing; Uniaxial stretch; YAP

Altered Ca2+ Kinetics Associated with alpha-Actinin-3 Deficiency May Explain Positive Selection for ACTN3 Null Allele in Human Evolution - Head, Stewart I.; Chan, Stephen; Houweling, Peter J.; Quinlan, Kate G. R.; Murphy, Robyn; Wagner, Sören; Friedrich, Oliver; North, Kathryn N. (PLoS Genetics, 2015)
Over 1.5 billion people lack the skeletal muscle fast-twitch fibre protein alpha-actinin-3 due to homozygosity for a common null polymorphism (R577X) in the ACTN3 gene. alpha-Actinin-3 deficiency is detrimental to sprint performance in elite athletes and beneficial to endurance activities. In the human genome, it is very difficult to find single-gene loss-of-function variants that bear signatures of positive selection, yet intriguingly, the ACTN3 null variant has undergone strong positive selection during recent evolution, appearing to provide a survival advantage where food resources are scarce and climate is cold. We have previously demonstrated that alpha-actinin-3 deficiency in the Actn3 KO mouse results in a shift in fast-twitch fibres towards oxidative metabolism, which would be more "energy efficient" in famine, and beneficial to endurance performance. Prolonged exposure to cold can also induce changes in skeletal muscle similar to those observed with endurance training, and changes in Ca2+ handling by the sarcoplasmic reticulum (SR) are a key factor underlying these adaptations. On this basis, we explored the effects of alpha-actinin-3 deficiency on Ca2+ kinetics in single flexor digitorum brevis muscle fibres from Actn3 KO mice, using the Ca2+-sensitive dye fura-2. Compared to wild-type, fibres of Actn3 KO mice showed: (i) an increased rate of decay of the twitch transient; (ii) a fourfold increase in the rate of SR Ca2+ leak; (iii) a threefold increase in the rate of SR Ca2+ pumping; and (iv) enhanced maintenance of tetanic Ca2+ during fatigue. The SR Ca2+ pump, SERCA1, and the Ca2+-binding proteins, calsequestrin and sarcalumenin, showed markedly increased expression inmuscles of KO mice. Together, these changes in Ca2+ handling in the absence of a-actinin-3 are consistent with cold acclimatisation and thermogenesis, and offer an additional explanation for the positive selection of the ACTN3 577X null allele in populations living in cold environments during recent evolutio

A method for high-content functional imaging of intracellular calcium responses in gelatin-immobilized non-adherent cells - Ritter, Paul; Bye, Lydia J.; Finol-Urdaneta, Rocio K.; Lesko, Christian; Adams, David J.; Friedrich, Oliver; Gilbert, Daniel (Experimental Cell Research, 2020)
Functional imaging of the intracellular calcium concentration [Ca2+]i using fluorescent indicators is a powerful and frequently applied method for assessing various biological questions in vitro, including ion channel function and intracellular signaling in homeostasis and disease. In functional [Ca2+]i imaging experiments, the fluorescence intensity of single cells is typically recorded during application of a chemical stimulus, i.e. by exchange of modified extracellular media, exposure to drugs and/or ligands. The concomitant mechanical perturbation caused by the perfusion of different solution during experimentation severely hinders calcium imaging in non-adherent cells, including peripheral immune cells, as cells in suspension are dislocated by turbulent flow during chemical stimulation. The quantitative analysis, involving time-courses of intracellular fluorescence signal changes, necessitates cells to remain at the same position throughout the experiment. To prevent dislocation of cells during solution exchange, and to enable imaging as well as analysis of Ca2+ responses in immune cells, a gelatin-based method for immobilization of non-adherent cells was developed. Gelatin has been a long-serving material for cell immobilization, e.g. in 3D bio-printing of cells and has thus, also been employed in the context of this study. To demonstrate the applicability of the established method for functional Ca2+ imaging in gelatin-immobilized suspension cells, a proof-of-concept study was conducted using human peripheral blood model cell lines (Jurkat/T-lymphocytes and THP-1/monocytes), Ca2+ indicators (Fluo-4 and Fura-2) and two different fluorescence microscopy rigs. The data presented that the established methodology is applicable for studying Ca2+ signaling by in vitro high-content functional imaging of [Ca2+]i in suspension cells, including but not restricted to human immune cells.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Calcium imaging; Fluo-4; Fura-2; Gelatin; Jurkat cells; THP-1 cells

Amorphous calcium phosphate reinforced alginate-dialdehyde-gelatin (ADA-GEL) bioink for biofabrication of bone tissue scaffolds - Indurkar, Abhishek; Heid, Susanne; Bauer, Julian; Rubenis, Kristaps; Friedrich, Oliver; Locs, Janis; Boccaccini, Aldo R. (Carbohydrate Polymer Technologies and Applications, 2025)
The aim of this work was to develop a nanocomposite bioink closely resembling the nanostructure of bone incorporating amorphous calcium phosphate (ACP) as an inorganic counterpart, specifically, citrate stabilized ACP (ACP_CIT) and non-stabilized ACP (ACP_ACE) in an organic hydrogel matrix consisted of alginate dialdehyde-gelatin (ADA-GEL). The hydrogel's physical properties were evaluated, confirming the reinforcement effect of ACP. The frequency sweep analysis showed that G' and G" of ADA-GEL were 99 ± 9 Pa and 9 ± 1 Pa, respectively. By the addition of ACP_ACE, G' and G" increased. Overall, the viscoelastic and mechanical properties of ADA-GEL hydrogel were enhanced by ACP. ACP_CIT was more effective than ACP_ACE. Further, printing parameters were optimized. The bioink was formulated by embedding MC3T3-E1 cells in ADA-GEL and ACP-reinforced ADA-GEL hydrogels, followed by fabricating scaffolds at optimized printing parameters (pressure: 65 kPa, speed: 5 mm/s). Crosslinking was performed by immersing constructs in CaCl2 and microbial transglutaminase solution. Post-printing analysis was performed using the printability index and average pore area analysis. The lowest structural stability was observed in ADA-GEL constructs. The highest structural stability was noted in ADA-GEL-ACP_CIT constructs. Epifluorescence and two-photon microscopy of Rhodamine/Phalloidin stained constructs confirmed the cytocompatibility of the bioinks.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Alginate dialdehyde-gelatin bioink; Bioprinting; Bone tissue engineering; Citrate stabilized amorphous calcium phosphate; Nanocomposite bioink

Amyloidogenic amyloid-?-peptide variants induce microbial agglutination and exert antimicrobial activity - Spitzer, Philipp; Condic, Mateja; Herrmann, Martin; Oberstein, Timo; Scharin-Mehlmann, Marina; Gilbert, Daniel; Friedrich, Oliver; Groemer, Teja; Kornhuber, Johannes; Lang, Roland; Maler, Juan Manuel (Scientific Reports, 2016)
Amyloid-? (A?) peptides are the main components of the plaques found in the brains of patients with Alzheimer's disease. However, A? peptides are also detectable in secretory compartments and peripheral blood contains a complex mixture of more than 40 different modified and/or N- and C-terminally truncated A? peptides. Recently, anti-infective properties of A? peptides have been reported. Here, we investigated the interaction of A? peptides of different lengths with various bacterial strains and the yeast Candida albicans. The amyloidogenic peptides A?1-42, A?2-42, and A?3p-42 but not the non-amyloidogenic peptides A?1-40 and A?2-40 bound to microbial surfaces. As observed by immunocytochemistry, scanning electron microscopy and Gram staining, treatment of several bacterial strains and Candida albicans with A? peptide variants ending at position 42 (A?x-42) caused the formation of large agglutinates. These aggregates were not detected after incubation with A?x-40. Furthermore, A?x-42 exerted an antimicrobial activity on all tested pathogens, killing up to 80% of microorganisms within 6 h. A?1-40 only had a moderate antimicrobial activity against C. albicans. Agglutination of A?1-42 was accelerated in the presence of microorganisms. These data demonstrate that the amyloidogenic A?x-42 variants have antimicrobial activity and may therefore act as antimicrobial peptides in the immune system.
EVALuna2:7714

An advanced optical clearing protocol allows label-free detection of tissue necrosis via multiphoton microscopy in injured whole muscle - Schneidereit, Dominik; Broellochs, Anita; Ritter, Paul; Kreiß, Lucas; Mokhtari, Zeinab; Beilhack, Andreas; Krönke, Gerhard; Ackermann, Jochen; Faas, Maria; Grüneboom, Anika; Schürmann, Sebastian; Friedrich, Oliver (Theranostics, 2021)
Rationale: Structural remodeling or damage as a result of disease or injury is often not evenly distributed throughout a tissue but strongly depends on localization and extent of damaging stimuli. Skeletal muscle as a mechanically active organ can express signs of local or even systemic myopathic damage, necrosis, or repair. Conventionally, muscle biopsies (patients) or whole muscles (animal models) are mechanically sliced and stained to assess structural alterations histologically. Three-dimensional tissue information can be obtained by applying deep imaging modalities, e.g. multiphoton or light-sheet microscopy. Chemical clearing approaches reduce scattering, e.g. through matching refractive tissue indices, to overcome optical penetration depth limits in thick tissues.
CRIS-Team WoS Importer:2021-01-22

An alginate-cellulose based bioink mimics the viscoelastic features of the melanoma microenvironment and its influence on cell cycle and invasion - Eckert, Carolin; Schmidt, Sonja; Faber, Jessica; Detsch, Rainer; Vielreicher, Martin; Lamberger, Zan; Stahlhut, Philipp; Sandor, Evelin; Karimi, Tannaz; Schmid, Rafael; Arkudas, Andreas; Friedrich, Oliver; et al. (Bioprinting, 2025)
Melanoma, an aggressive tumor from melanocytes, poses challenges despite recent therapeutic advances. Understanding molecular changes in its progression is crucial. Melanoma cells develop in the epidermis, then start spreading into the dermis– the first step of the invasive, progressive process. The dermis is composed of elastic (proteoglycans) and stabilizing (collagens) molecules. To overcome limitations of 2D-cell culture models, we established a 3D-bio-printed dermis model for the analysis of tumor cell features using a blend of alginate and microfibrillar cellulose. Testing different compositions in extrusion-based bioprinting confirmed good printability with high cell viability for AlgCell ink. Mechanical and optical analyses revealed dermis-like viscoelasticity and a pore size allowing nutrition supply and cell movement. We evaluated survival and proliferation of the cells and printed tumor spheroids and determined different migratory behavior comparing alginate to AlgCell. Interestingly, multiphoton microscopy revealed random cellulose fiber distribution around the spheroids after 7 days of cultivation with individual single cells, which had left the tumor spheroid and invaded into the microenvironment. Traditional 2D-models inadequately capture 3D mechanisms like invasion and migration. Our 3D-tumor model mimics the microenvironment, enabling in-depth analyses akin to in vivo conditions. This promises insights into tumor progression and testing of therapeutic interventions.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Bioink; Cell migration; Melanoma; Spheroid printing

A New Printable Alginate/Hyaluronic Acid/Gelatin Hydrogel Suitable for Biofabrication of In Vitro and In Vivo Metastatic Melanoma Models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2022)
Two-dimensional (2D) cancer models have been the standard for drug development over the past few years, but they frequently do not resemble in vivo properties adequately. 3D models are superior in many aspects and are, therefore, more similar to human pathophysiology. Over the past years, the emerging field of biofabrication has made significant advances, resulting in even more sophisticated 3D models. With this study, a hydrogel is created for biofabrication that is suitable for mimicking the tumor microenvironment in vitro and is further tested as a new vascularized melanoma model in vivo. The alginate/hyaluronic acid/gelatin bioink shows good shape-fidelity, high cell survival rates, and enables successful cultivation of melanoma cells and adipose-derived stem cells as well as cell differentiation in vitro. In vivo, in the arteriovenous loop model, it proves to be a unique method to study melanoma progression, tumor vascularization, and ultimately and reliably metastases in an isolated and controlled environment. These results show that this 3D model is very application-oriented for molecular research and therapy development.
CRIS-Team Scopus Importer:2021-10-22
Keywords: bioinks; metastasis; stem cells; tissue engineering; tumors

An open-source technology platform to increase reproducibility and enable high-throughput production of tailorable gelatin methacryloyl (GelMA) - based hydrogels - Eggert, Sebastian; Kahl, Melanie; Bock, Nathalie; Meinert, Christoph; Friedrich, Oliver; Hutmacher, Dietmar W. (Materials and Design, 2021)
Gelatin methacryloyl (GelMA)-based hydrogels have become highly studied as modular tissue culture platforms due to the combination of the bioactivity of gelatin and tailorability of photo-crosslinkable hydrogels. However, current production and characterization workflows still rely on manual, time-consuming, and low-throughput processes, ultimately limiting widespread adaption. To address these challenges, an open-source technology platform is engineered and validated for automated high-throughput production of GelMA-based 3D constructs by integrating automated pipetting capabilities for viscous and non-viscous liquids. Firstly, the platform is applied in combination with inexpensive absorbance measurements to systematically optimize the mixing sequence for GelMA-based precursor solutions. This enables a decrease in the relative standard deviation of the prepared mixtures from 63% to 2.5%, demonstrating a significantly improved reproducibility. Next, the applicability and high-throughput capacity are demonstrated by the reproducible generation of GelMA dilution series with 0.5 and 2% (w/v) concentration steps as well as double network hydrogels consisting of 2% (w/v) alginate and 5% (w/v) GelMA. Finally, a simple and user-friendly methodology is described that integrates Design of Experiments approaches to systematically study the combinatorial effects of material and crosslinking parameters and to establish a parameter library for on-demand production of mechanically defined GelMA-based hydrogels. The platform enables reproducible production and offers an open-source and accessible alternative to high-priced liquid-handling robots and bioprinters.
CRIS-Team Scopus Importer:2021-04-02
Keywords: 3D cell culture; Bioprinting; Gelatin methacryloyl (GelMA); Hydrogels; Open-source; Reproducibility; Tissue engineering

A novel bone substitute with high bioactivity, strength, and porosity for repairing large and load-bearing bone defects - Li, Jiao Jiao; Dunstan, Colin; Entezari, Ali; Li, Qing; Steck, Roland; Saifzadeh, Siafak; Sadeghpour, Ameneh; Field, John R; Akey, Austin; Vielreicher, Martin; Friedrich, Oliver; Esfahani, Seyed-Iman; et al. (Advanced Healthcare Materials, 2019)
Achieving adequate healing in large or load-bearing bone defects is highly challenging even with surgical intervention. The clinical standard of repairing bone defects using autografts or allografts has many drawbacks. A bioactive ceramic scaffold, strontium-hardystonite-gahnite or "Sr-HT-Gahnite" (a multi-component, calcium silicate-based ceramic) is developed, which when 3D-printed combines high strength with outstanding bone regeneration ability. In this study, the performance of purely synthetic, 3D-printed Sr-HT-Gahnite scaffolds is assessed in repairing large and load-bearing bone defects. The scaffolds are implanted into critical-sized segmental defects in sheep tibia for 3 and 12 months, with bone autografts used for comparison. The scaffolds induce substantial bone formation and defect bridging after 12 months, as indicated by X-ray, micro-computed tomography, and histological and biomechanical analyses. Detailed analysis of the bone-scaffold interface using focused ion beam scanning electron microscopy and multiphoton microscopy shows scaffold degradation and maturation of the newly formed bone. In silico modeling of strain energy distribution in the scaffolds reveal the importance of surgical fixation and mechanical loading on long-term bone regeneration. The clinical application of 3D-printed Sr-HT-Gahnite scaffolds as a synthetic bone substitute can potentially improve the repair of challenging bone defects and overcome the limitations of bone graft transplantatio

A novel modular opto-biomechatronics bioreactor for simultaneous isotropic mechanical stretch application and fluorescence microscopy under cell and tissue culture conditions - Merten, Anna-Lena; Schöler, Ulrike; Lesko, Christian; Kreiß, Lucas; Schneidereit, Dominik; Linsenmeier, Fabian; Stolz, Axel; Rappl, Sebastian; Ali, Mohamed; Potié, Tim; Ahmed, Adel; Morales-Dalmau, Jordi; et al. (Biosensors and Bioelectronics: X, 2024)
Mechanical stresses are an environmental challenge virtually all tissues in the body are exposed to and thus, are of fundamental interest to study cell reactions in mechanobiology. Yet, unlike acute short-term mechanical cell stimulations, long-term or cyclic mechano-stimulation as experienced in the body is difficult to reproduce. Bioreactors are designed to control cell culture conditions, but still, there are yet no technical solutions available to merge bioreactor and opto-biomechatronics technologies for cyclic stretch-applications and simultaneous live cell imaging. To close this gap, we have engineered an opto-biomechatronics module, consisting of our in-house developed IsoStretcher technology and customised epifluorescence optics, into an automated bioreactor platform. For this, redesigned polydimethylsiloxane (PDMS) chambers with closed geometry (∽700 μL internal volume) to warrant sterile operation were developed. Those chambers could be flushed with cell solution for cell seeding in a sterile manner. The epifluorescence imaging module was engineered into the reactor underneath the IsoStretcher to allow for continuous image acquisition during long-term stretch cycles (hours to days). The system was validated on human fibroblast BJ foreskin cells, and Cal-520 Ca2＋ fluorescence was stably imaged using our in-built autofocus functionality. Cultures for 24 h within the IsoStretcher-bioreactor preserved a normal cell morphology as compared to external incubator control cultures. Isotropic stretch was reliably transferred to the cell membranes. Our system with in-built bioreactor and opto-biomechatronics functionality provides a holistic technology platform for the growing field of mechanobiology to allow long-term observations of cultured single cells and confluent cell layers that are subjected to cyclic long-term isotropic stretch protocols.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Automation; Bioreactor; Cell stretching device; Mechanosensitive ion channels; Mechanotransduction

A novel quantitative morphometry approach to assess regeneration in dystrophic skeletal muscle. - Buttgereit, Andreas; Weber, Cornelia; Friedrich, Oliver (Neuromuscular Disorders, 2014)
Duchenne muscular dystrophy is an inherited degenerative muscle disease with progressive weakness of skeletal and cardiac muscle. Disturbed calcium homeostasis and signalling pathways result in degeneration/regeneration cycles with fibrotic remodelling of muscle tissue, sustained by chronic inflammation. In addition to altered microarchitecture, regeneration in dystrophic muscle fibres is often only classified by centrally located nuclei but correlation of the regeneration process to nuclear volumes, myosin amounts, architecture and functional quality are missing, in particular in old muscles where the regenerative capacity is exhausted. Such information could yield novel regeneration-to-function biomarkers. Here we used second harmonic generation and multi photon fluorescence microscopy in intact single muscle fibres from wild-type, dystrophic mdx and transgenic mdx mice expressing an Δex 17-48 mini-dystrophin to determine the percentage of centronucleated fibres and nucleus-to-myosin volume ratio as a function of age. Based on this ratio we define a 'biomotoric efficiency' as an optical measure for fibre maturation, which is close to unity in adult wild-type and mini-dystrophin fibres, but smaller in very young and old mdx mice as a result of ongoing cell maturation (young) and regeneration (aged). With these parameters it is possible to provide a quantitative measure about muscle fibre regeneration.
Keywords: Muscular dystrophy; Nucleus; Myosin; Regeneration; Efficiency; Myonuclear domain; Second harmonic generation

Anti-beta 7 integrin treatment impedes the recruitment on non-classical monocytes to the gut and delays macrophage-mediated intestinal wound healing - Sommer, Katrin; Heidbreder, Karin; Kreiß, Lucas; Dedden, Mark; Paap, Eva-Maria; Wiendl, Maximilian; Becker, Emily; Atreya, Raja; Müller, Tanja; Atreya, Imke; Waldner, Maximilian; Schürmann, Sebastian; et al. (Clinical and Translational Medicine, 2023)
BackgroundClosing mucosal defects to reach mucosal healing is an important goal of therapy in inflammatory bowel disease (IBD). Among other cells, monocyte-derived macrophages are centrally involved in such intestinal wound healing. We had previously demonstrated that the anti-alpha 4 beta 7 integrin antibody vedolizumab blocks the recruitment of non-classical monocytes as biased progenitors of wound healing macrophages to the gut and delays wound healing. However, although important for the interpretation of disappointing results in recent phase III trials in IBD, the effects of the anti-beta 7 antibody etrolizumab on wound healing are unclear so far. MethodsWe analyzed the expression of etrolizumab targets on human and mouse monocyte subsets by flow cytometry and assessed their function in adhesion and homing assays. We explored wound-associated monocyte recruitment dynamics with multi-photon microscopy and compared the effects of etrolizumab and vedolizumab surrogate (-s) antibodies on experimental wound healing and wound-associated macrophage abundance. Finally, we investigated wound healing macrophage signatures in the large intestinal transcriptome of patients with Crohn's disease treated with etrolizumab. ResultsHuman and mouse non-classical monocytes expressed more alpha E beta 7 integrin than classical monocytes and were a target of etrolizumab-s, which blocked non-classical monocyte adhesion to MAdCAM-1 and E-Cadherin as well as gut homing in vivo. Intestinal wound healing was delayed on treatment with etrolizumab-s along with a reduction of peri-lesional wound healing macrophages. Wound healing macrophage signatures in the colon of patients with Crohn's disease were substantially down-regulated on treatment with etrolizumab, but not with placebo. ConclusionsCombined blockade of alpha E beta 7 and alpha 4 beta 7 with etrolizumab seems to exceed the effect of anti-alpha 4 beta 7 treatment on intestinal wound healing, which might help to inform further investigations to understand the recent observations in the etrolizumab phase III trial program.
CRIS-Team WoS Importer:2023-05-05

A portable low-cost long-term live-cell imaging platform for biomedical research and education. - Walzik, Maria P.; Vollmar, Verena; Lachnit, Theresa; Dietz, Helmut; Haug, Susanne; Bachmann, Holger; Fath, Moritz; Aschenbrenner, Daniel; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Biosensors and Bioelectronics, 2015)
Time-resolved visualization and analysis of slow dynamic processes in living cells has revolutionized many aspects of in vitro cellular studies. However, existing technology applied to time-resolved live-cell microscopy is often immobile, costly and requires a high level of skill to use and maintain. These factors limit its utility to field research and educational purposes. The recent availability of rapid prototyping technology makes it possible to quickly and easily engineer purpose-built alternatives to conventional research infrastructure which are low-cost and user-friendly. In this paper we describe the prototype of a fully automated low-cost, portable live-cell imaging system for time-resolved label-free visualization of dynamic processes in living cells. The device is light-weight (3.6 kg), small (22 × 22 × 22 cm) and extremely low-cost (<€1250). We demonstrate its potential for biomedical use by long-term imaging of recombinant HEK293 cells at varying culture conditions and validate its ability to generate time-resolved data of high quality allowing for analysis of time-dependent processes in living cells. While this work focuses on long-term imaging of mammalian cells, the presented technology could also be adapted for use with other biological specimen and provides a general example of rapidly prototyped low-cost biosensor technology for application in life sciences and education.
Keywords: Label-free long-term live-cell imaging; Low-cost biosensor technology; Rapid prototyping; 3D-desktop printing; Arduino

A Print-and-Fuse Strategy for Sacrificial Filaments Enables Biomimetically Structured Perfusable Microvascular Networks with Functional Endothelium Inside 3D Hydrogels - Ryma, Matthias; Genc, Hatice; Nadernezhad, Ali; Paulus, Ilona; Schneidereit, Dominik; Friedrich, Oliver; Andelovic, Kristina; Lyer, Stefan; Alexiou, Christoph; Cicha, Iwona; Groll, Juergen (Advanced Materials, 2022)
A facile and flexible approach for the integration of biomimetically branched microvasculature within bulk hydrogels is presented. For this, sacrificial scaffolds of thermoresponsive poly(2-cyclopropyl-2-oxazoline) (PcycloPrOx) are created using melt electrowriting (MEW) in an optimized and predictable way and subsequently placed into a customized bioreactor system, which is then filled with a hydrogel precursor solution. The aqueous environment above the lower critical solution temperature (LCST) of PcycloPrOx at 25 degrees C swells the polymer without dissolving it, resulting in fusion of filaments that are deposited onto each other (print-and-fuse approach). Accordingly, an adequate printing pathway design results in generating physiological-like branchings and channel volumes that approximate Murray's law in the geometrical ratio between parent and daughter vessels. After gel formation, a temperature decrease below the LCST produces interconnected microchannels with distinct inlet and outlet regions. Initial placement of the sacrificial scaffolds in the bioreactors in a pre-defined manner directly yields perfusable structures via leakage-free fluid connections in a reproducible one-step procedure. Using this approach, rapid formation of a tight and biologically functional endothelial layer, as assessed not only through fluorescent dye diffusion, but also by tumor necrosis factor alpha (TNF-alpha) stimulation, is obtained within three days.
CRIS-Team WoS Importer:2022-06-17

A Recombinant Human Pluripotent Stem Cell Line Stably Expressing Halide-Sensitive YFP-I152L for GABAAR and GlyR-Targeted High-Throughput Drug Screening and Toxicity Testing. - Künzel, Katharina; Friedrich, Oliver; Gilbert, Daniel (Frontiers in Molecular Neuroscience, 2016)
GABARs and GlyRs are considered attractive drug targets for therapeutic intervention and are also increasingly recognized in the context of in vitro neurotoxicity (NT) and developmental neurotoxicity (DNT) testing. However, systematic human-specific GABAR and GlyR-targeted drug screening and toxicity testing is hampered due to lack of appropriate in vitro models that express native GABARs and GlyRs. We have established a human pluripotent stem cell line (NT2) stably expressing YFP-I152L, a halide-sensitive variant of yellow fluorescent protein (YFP), allowing for fluorescence-based functional analysis of chloride channels. Upon stimulation with retinoic acid, NT2 cells undergo neuronal differentiation and allow pharmacological and toxicological evaluation of native GABARs and GlyRs at different stages of brain maturation. We applied the cell line in concentration-response experiments with the neurotransmitters GABA and glycine as well as with the drugs strychnine, picrotoxin, fipronil, lindane, bicuculline, and zinc and demonstrate that the established in vitro model is applicable to GABAR and GlyR-targeted pharmacological and toxicological profiling. We quantified the proportion of GABAR and GlyR-sensitive cells, respectively, and identified percentages of approximately 20% each within the overall populations, rendering the cells a suitable model for systematic in vitro GABAR and GlyR-targeted screening in the context of drug development and NT/DNT testin
Keywords: Gamma-aminobutyric acid receptor type-A chloride channel (GABAAR); Glycine receptor chloride channel (GlyR); Human pluripotent embryonal teratocarcinoma stem cells; NT2 cells; NT2-N cells; YFP-I152L

Artemisinin–(Iso)quinoline Hybrids by C−H Activation and Click Chemistry: Combating Multidrug-Resistant Malaria - Çapcı, Aysun; Lorion, Mélanie M.; Wang, Hui; Simon, Nina; Leidenberger, Maria; Borges Silva, Mariana C.; Moreira, Diogo R.M.; Zhu, Yongping; Meng, Yuqing; Chen, Jia Yun; Lee, Yew Mun; Friedrich, Oliver; et al. (Angewandte Chemie International Edition, 2019)
A substantial challenge worldwide is emergent drug resistance in malaria parasites against approved drugs, such as chloroquine (CQ). To address these unsolved CQ resistance issues, only rare examples of artemisinin (ART)-based hybrids have been reported. Moreover, protein targets of such hybrids have not been identified yet, and the reason for the superior efficacy of these hybrids is still not known. Herein, we report the synthesis of novel ART–isoquinoline and ART–quinoline hybrids showing highly improved potencies against CQ-resistant and multidrug-resistant P. falciparum strains (EC50 (Dd2) down to 1.0 nm; EC50 (K1) down to 0.78 nm) compared to CQ (EC50 (Dd2)=165.3 nm; EC50 (K1)=302.8 nm) and strongly suppressing parasitemia in experimental malaria. These new compounds are easily accessible by step-economic C−H activation and copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) click reactions. Through chemical proteomics, putatively hybrid-binding protein targets of the ART-quinolines were successfully identified in addition to known targets of quinoline and artemisinin alone, suggesting that the hybrids act through multiple modes of action to overcome resistance.
CRIS-Team Scopus Importer:2019-08-27
Keywords: antimalarial agents; artemisinin; drug resistance; hybridization; proteomics

Assaying Proliferation Characteristics of Cells Cultured Under Static Versus Periodic Conditions - Gilbert, Daniel; Friedrich, Oliver; Wiest, Joachim (Cell Viability Assays (2nd Edt.), 2023)
Two-dimensional in vitro culture models are widely being employed for assessing a vast variety of biological questions in different scientific fields. Common in vitro culture models are typically maintained under static conditions, where the surrounding culture medium is replaced every few days—typically every 48 to 72 h—with the aim to remove metabolites and to replenish nutrients. Although this approach is sufficient for supporting cellular survival and proliferation, static culture conditions do mostly not reflect the in vivo situation where cells are continuously being perfused by extracellular fluid, and thus, create a less-physiological environment. In order to evaluate whether the proliferation characteristics of cells in 2D culture maintained under static conditions differ from cells kept in a dynamic environment, in this chapter, we provide a protocol for differential analysis of cellular growth under static versus pulsed-perfused conditions, mimicking continuous replacement of extracellular fluid in the physiological environment. The protocol involves long-term life-cell high-content time-lapse imaging of fluorescent cells at 37 °C and ambient CO2 concentration using multi-parametric biochips applicable for microphysiological analysis of cellular vitality. We provide instructions and useful information for (i) the culturing of cells in biochips, (ii) setup of cell-laden biochips for culturing cells under static and pulsed-perfused conditions, (iii) long-term life-cell high-content time-lapse imaging of fluorescent cells in biochips, and (iv) quantification of cellular proliferation from image series generated from imaging of differentially cultured cells.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Biochip; Cell growth; HEK293; Long-term time-lapse microscopy; Microfluidics; YFPI152L

Assessing viability of extracorporeal preserved muscle transplants using external field stimulation: a novel tool to improve methods prolonging bridge-to-transplantation time. - Taeger, Christian; Friedrich, Oliver; Dragu, Adrian; Weigand, Annika; Hobe, Frieder; Drechsler, Caroline; Geppert, Carol-Immanuel; Arkudas, Andreas; Münch, Frank; Buchholz, Rainer; Pollmann, Charlotte; Schramm, Axel; et al. (Scientific Reports, 2015)
Preventing ischemia-related cell damage is a priority when preserving tissue for transplantation. Perfusion protocols have been established for a variety of applications and proven to be superior to procedures used in clinical routine. Extracorporeal perfusion of muscle tissue though cumbersome is highly desirable since it is highly susceptible to ischemia-related damage. To show the efficacy of different perfusion protocols external field stimulation can be used to immediately visualize improvement or deterioration of the tissue during active and running perfusion protocols. This method has been used to show the superiority of extracorporeal perfusion using porcine rectus abdominis muscles perfused with heparinized saline solution. Perfused muscles showed statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. The combination of extracorporeal perfusion and external field stimulation may improve organ conservation research.

Assessment of Cell Viability in Electrically Excitable Muscle Cells Through Intact Twitch Stimulation - Bauer, Julian; Head, Stewart I.; Friedrich, Oliver (Cell Viability Assays (2nd Edt.), 2023)
Muscle cells (i.e. skeletal muscle fibers) are fully viable and functional when their excitation-contraction (EC) coupling machinery is intact. This involves intact membrane integrity with polarized membrane, functional ion channels for action potential generation and conduction, an intact electro-chemical interface at the level of the fiber’s triad, followed by sarcoplasmic reticulum Ca2+ release, and subsequent activation of the chemico-mechanical interface at the level of the contractile apparatus. The ultimate end result is then a visible twitch contraction upon a brief electrical pulse stimulation. For many biomedical studies involving single muscle cells, intact and viable myofibers are of utmost importance. Thus, a simple global screening method that involves a brief electrical stimulus applied to single muscle fibers and assessment of visible contraction would be of high value. In this chapter, we describe step-by-step protocols to (i) obtain intact single muscle fibers from freshly dissected muscle tissue using an enzymatic digestion procedure and (ii) provide a workflow for the assessment of twitch response of single fibers that can be ultimately classified as viable. For this, we have prepared a unique stimulation pen for which we provide the fabrication guide for do-it-yourself rapid prototyping to eliminate the need for expensive specialized commercial equipment.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Contraction; Electrical stimulator; Enzymatic dissociation; Single fiber; Skeletal muscle; Twitch stimulation

Assessment of Plasmodium falciparum PfMDR1 transport rates using Fluo-4. - Friedrich, Oliver; Reiling, Sarah; Wunderlich, Juliane; Rohrbach, Petra (Journal of cellular and molecular medicine, 2014)
Mutations in the multidrug resistance transporter of Plasmodium falciparum PfMDR1 have been implicated to play a significant role in the emergence of worldwide drug resistance, yet the molecular and biochemical mechanisms of this transporter are not well understood. Although it is generally accepted that drug resistance in P. falciparum is partly associated with PfMDR1 transport activity situated in the membrane of the digestive vacuole, direct estimates of the pump rate of this transport process in the natural environment of the intact host-parasite system have never been analysed. The fluorochrome Fluo-4 is a well-documented surrogate substrate of PfMDR1 and has been found to accumulate by actively being transported into the digestive vacuole of several parasitic strains. In the present study, we designed an approach to use Fluo-4 fluorescence uptake as a measure of compartmental Fluo-4 concentration accumulation in the different compartments of the host-parasite system. We performed a 'reverse Fluo-4 imaging' approach to relate fluorescence intensity to changes in dye concentration rather than Ca(2+) fluctuations and were able to calculate the overall rate of transport for PfMDR1 in Dd2 parasites. With this assay, we provide a powerful method to selectively measure the effect of PfMDR1 mutations on substrate transport kinetics. This will be of high significance for future compound screening to test for new drugs in resistant P. falciparum strains.
Keywords: Plasmodium falciparum; PfMDR1; transport kinetics; Fluo-4; l ive-cell imaging; calcium; pH

Assessment of Population and ECM Production Using Multiphoton Microscopy as an Indicator of Cell Viability. - Vielreicher, Martin; Friedrich, Oliver (Methods in Molecular Biology, 2017)
Multiphoton microscopy allows continuous depth-resolved, nondestructive imaging of scaffold-seeded cells during cell or tissue culture. Spectrally separated images in high resolution can be provided while cells are conserved in their native state. Here we describe the seeding of mesenchymal stem cells to bacterial nanocellulose hydropolymer scaffolds followed by 2-channel imaging of cellular autofluorescence (AF) and collagen-I formation using second harmonic generation (SHG) signals. With this approach the simultaneous observation of the progression of cell morphology and production of extracellular matrix as hallmarks of viability and cell fitness is possible.

ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio

Automated multiscale morphometry of muscle disease from second harmonic generation microscopy using tensor-based image processing. - Garbe, Christoph S.; Buttgereit, Andreas; Schürmann, Sebastian; Friedrich, Oliver (IEEE transactions on bio-medical engineering, 2012)
Practically, all chronic diseases are characterized by tissue remodeling that alters organ and cellular function through changes to normal organ architecture. Some morphometric alterations become irreversible and account for disease progression even on cellular levels. Early diagnostics to categorize tissue alterations, as well as monitoring progression or remission of disturbed cytoarchitecture upon treatment in the same individual, are a new emerging field. They strongly challenge spatial resolution and require advanced imaging techniques and strategies for detecting morphological changes. We use a combined second harmonic generation (SHG) microscopy and automated image processing approach to quantify morphology in an animal model of inherited Duchenne muscular dystrophy (mdx mouse) with age. Multiphoton XYZ image stacks from tissue slices reveal vast morphological deviation in muscles from old mdx mice at different scales of cytoskeleton architecture: cell calibers are irregular, myofibrils within cells are twisted, and sarcomere lattice disruptions (detected as "verniers") are larger in number compared to samples from healthy mice. In young mdx mice, such alterations are only minor. The boundary-tensor approach, adapted and optimized for SHG data, is a suitable approach to allow quick quantitative morphometry in whole tissue slices. The overall detection performance of the automated algorithm compares very well with manual "by eye" detection, the latter being time consuming and prone to subjective errors. Our algorithm outperfoms manual detection by time with similar reliability. This approach will be an important prerequisite for the implementation of a clinical image databases to diagnose and monitor specific morphological alterations in chronic (muscle) diseases.
Keywords: biomedical MRI; cellular biophysics; diseases; harmonic generation; medical image processing; muscle

Bacterial nanocellulose as novel carrier for intestinal epithelial cells in drug delivery studies - Fey, Christina; Betz, Jana; Rosenbaum, Corinna; Kralisch, Dana; Vielreicher, Martin; Friedrich, Oliver; Metzger, Marco; Zdzieblo, Daniela (Materials Science and Engineering C, 2020)
Synthetic cell carriers (A) represent common scaffold structures for the development of cell-based in vitro models of the human intestine but due to their low porosity or unwanted molecular adhesion effects, synthetic carriers can negatively affect cell function. Alternative scaffolds such as natural extracellular matrices (ECMs) (B) were shown to overcome some of the common drawbacks. However, their fabrication is time-consuming, less well standardized and not entirely conform to the 3R principle (replacement, reduction, refinement). Nowadays, biopolymers such as bacterial nanocellulose (BNC) (C) represent interesting scaffold materials for innovative tissue engineering concepts, as they can be generated in a faster and more standardized process workflow without the need for animal material. In this study, we demonstrate the BNC as suitable carrier for the development of Caco-2-based in vitro models of the human intestine. The BNC-based models exhibit organ-specific properties comprising typical cellular morphologies, characteristic protein expression profiles, representative ultrastructural features and the formation of a tight epithelial barrier. The proof of in vivo-like transport activities further validates the high quality of the BNC-based Caco-2 models. In summary, this illustrates the BNC as alternative bioscaffold of non-animal origin to develop functional organ models in vitro.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Bacterial nanocellulose (BNC); Caco-2 cells; Extracellular matrix (ECM); Small intestinal submucosa (SIS); Transwell®-like intestinal models

Bacterial nanocellulose stimulates mesenchymal stem cell expansion and formation of stable collagen-I networks as a novel biomaterial in tissue engineering - Vielreicher, Martin; Kralisch, Dana; Sternal, Fabian; Arkudas, Andreas; Friedrich, Oliver; Völkl, Simon (Scientific Reports, 2018)
Biomimetic scaffolds are of great interest to tissue engineering (TE) and tissue repair as they support important cell functions. Scaffold coating with soluble collagen-I has been used to achieve better tissue integration in orthopaedy, however, as collagen persistence was only temporary such efforts were limited. Adequate coverage with cell-derived ECM collagen-I would promise great success, in particular for TE of mechanically challenged tissues. Here, we have used label-free, non-invasive multiphoton microscopy (MPM) to characterise bacterial nanocellulose (BNC) - a promising biomaterial for bone TE - and their potency to stimulate collagen-I formation by mesenchymal stem cells (MSCs). BNC fleeces were investigated by Second Harmonic Generation (SHG) imaging and by their characteristic autofluorescence (AF) pattern, here described for the first time. Seeded MSCs adhered fast, tight and very stable, grew to multilayers and formed characteristic, wide-spread and long-lasting collagen-I. MSCs used micron-sized lacunae and cracks on the BNC surface as cell niches. Detailed analysis using a collagen-I specific binding protein revealed a highly ordered collagen network structure at the cell-material interface. In addition, we have evidence that BNC is able to stimulate MSCs towards osteogenic differentiation. These findings offer new options for the development of engineered tissue constructs based on BNC.
EVALuna2:34280

Bacterial nanocellulose stimulates mesenchymal stem cell expansion, differentiation and formation of stable collagen-I networks - Vielreicher, Martin; Kralisch, Dana; Völkl, Simon; Friedrich, Oliver (International Conference on Biofabrication (Annual Meeting of the International Society for Biofabrication), 2018)

Beyond endoscopic assessment in inflammatory bowel disease: real-time histology of disease activity by non-linear multimodal imaging. - Chernavskaia, Olga; Heuke, Sandro; Friedrich, Oliver; Schürmann, Sebastian; Atreya, Raja; Stallmach, Andreas; Neurath, Markus; Waldner, Maximilian; Petersen, Iver; Schmitt, Michael; Bocklitz, Thomas; Popp, Juergen; et al. (Scientific Reports, 2016)
Assessing disease activity is a prerequisite for an adequate treatment of inflammatory bowel diseases (IBD) such as Crohn's disease and ulcerative colitis. In addition to endoscopic mucosal healing, histologic remission poses a promising end-point of IBD therapy. However, evaluating histological remission harbors the risk for complications due to the acquisition of biopsies and results in a delay of diagnosis because of tissue processing procedures. In this regard, non-linear multimodal imaging techniques might serve as an unparalleled technique that allows the real-time evaluation of microscopic IBD activity in the endoscopy unit. In this study, tissue sections were investigated using the non-linear multimodal microscopy combination of coherent anti-Stokes Raman scattering (CARS), two-photon excited auto fluorescence (TPEF) and second-harmonic generation (SHG). After the measurement a gold-standard assessment of histological indexes was carried out based on a conventional H&E stain. Subsequently, various geometry and intensity related features were extracted from the multimodal images. An optimized feature set was utilized to predict histological index levels based on a linear classifier. Based on the automated prediction, the diagnosis time interval is decreased. Therefore, non-linear multimodal imaging may provide a real-time diagnosis of IBD activity suited to assist clinical decision making within the endoscopy unit.

Calcium currents during contraction and shortening in enzymatically isolated murine skeletal muscle fibres. - Friedrich, Oliver; Ehmer, Thomas; Fink, Rainer (The Journal of Physiology, 1999)
1. Calcium currents (ICa) were monitored in enzymatically isolated murine toe muscle fibres using the two-microelectrode voltage-clamp technique. ICa was recorded (i) in hypertonic solution to suppress contraction, and (ii) in actively shortening fibres in isotonic solution. 2. In hypertonic solution the threshold potential for ICa was about -30 mV for both 2 and 10 mM external Ca2+ solution. Maximum peak currents measured -12.6 +/- 2.3 nA (mean +/- s.d.; n = 4) in 2 mM Ca2+ and -65 +/- 15 nA (n = 7) in 10 mM Ca2+. The time to peak (TTP) ICa was 96 +/- 22 ms (n = 4) in 2 mM Ca2+ and 132 +/- 13 ms (n = 7) in 10 mM Ca2+. The exponential decay of ICa was similar in 2 and 10 mM Ca2+ with rate constants (tau-1(V)) of 3.7 s-1 (2 mM) and 3.8 s-1 (10 mM) at +10 mV. 3. ICa in isotonic 10 mM Ca2+ solution was recorded by inserting the micropipettes exactly opposite to each other close to the centre of mass of the fibre where negligible contraction-induced movement occurs. 4. In isotonic 10 mM Ca2+ solution ICa had a smaller peak amplitude (-45 +/- 5 nA; n = 7) and faster TTP (82.8 +/- 22.1 ms; n = 7) than in hypertonic solution. The exponential decay of ICa showed a significantly larger tau-1(V) of 6.4 s-1 at +10 mV (P < 0.03). 5. To test for calcium depletion, extracellular Ca2+ was buffered by malic acid in isotonic solution to 9 mM. The decay of ICa had a time constant of 348 +/- 175 ms (n = 14) vs. 107 +/- 24 ms (n = 12; P < 0.001) at 0 mV in unbuffered 10 mM Ca2+ solution. 6. We conclude that calcium depletion from the transverse tubular system contributes significantly to the decay of calcium currents in murine toe muscle fibres under hypertonic as well as isotonic conditions. In the latter, depletion is even more prominent.

Calcium Sensitive Fluorescent Dyes Fluo-4 and Fura Red under Pressure: Behaviour of Fluorescence and Buffer Properties under Hydrostatic Pressures up to 200 MPa. - Schneidereit, Dominik; Vass, H.; Reischl, Barbara; Allen, R. J.; Friedrich, Oliver (PLoS ONE, 2016)
The fluorescent Ca2+ sensitive dyes Fura Red (ratiometric) and Fluo-4 (non-ratiometric) are widely utilized for the optical assessment of Ca2+ fluctuations in vitro as well as in situ. The fluorescent behavior of these dyes is strongly depends on temperature, pH, ionic strength and pressure. It is crucial to understand the response of these dyes to pressure when applying calcium imaging technologies in the field of high pressure bioscience. Therefore, we use an optically accessible pressure vessel to pressurize physiological Ca2+-buffered solutions at different fixed concentrations of free Ca2+ (1 nM to 25.6 μM) and a specified dye concentration (12 μM) to pressures of 200 MPa, and record dye fluorescence intensity. Our results show that Fluo-4 fluorescence intensity is reduced by 31% per 100 MPa, the intensity of Fura Red is reduced by 10% per 100 MPa. The mean reaction volume for the dissociation of calcium from the dye molecules [Formula: see text] is determined to -17.8 ml mol-1 for Fluo-4 and -21.3 ml mol-1 for Fura Red. Additionally, a model is presented that is used to correct for pressure-dependent changes in pH and binding affinity of Ca2+ to EGTA, as well as to determine the influence of these changes on dye fluorescence.

Cannabinoid signalling inhibits sarcoplasmic Ca(2+) release and regulates excitation-contraction coupling in mammalian skeletal muscle. - Olah, Tamas; Bodnar, Dora; Toth, Adrienn; Vincze, Janos; Fodor, Janos; Reischl, Barbara; Kovacs, Adrienn; Ruzsnavszky, Olga; Dienes, Beatrix; Szentesi, Peter; Friedrich, Oliver; Csernoch, Laszlo (The Journal of Physiology, 2016)
KEY POINTS Marijuana was found to cause muscle weakness, although the exact regulatory role of its receptors (CB1 cannabinoid receptor; CB1R) in the excitation-contraction coupling (ECC) of mammalian skeletal muscle remains unknown. We found that CB1R activation or its knockout did not affect muscle force directly, whereas its activation decreased the Ca(2+) -sensitivity of the contractile apparatus and made the muscle fibres more prone to fatigue. We demonstrate that CB1Rs are not connected to the inositol 1,4,5-trisphosphate pathway either in myotubes or in adult muscle fibres. By contrast, CB1Rs constitutively inhibit sarcoplasmic Ca(2+) release and sarcoplasmic reticulum Ca(2+) ATPase during ECC in a Gi/o protein-mediated way in adult skeletal muscle fibres but not in myotubes. These results help with our understanding of the physiological effects and pathological consequences of CB1R activation in skeletal muscle and may be useful in the development of new cannabinoid drugs. ABSTRACT Marijuana was found to cause muscle weakness, although it is unknown whether it affects the muscles directly or modulates only the motor control of the central nervous system. Although the presence of CB1 cannabinoid receptors (CB1R), which are responsible for the psychoactive effects of the drug in the brain, have recently been demonstrated in skeletal muscle, it is unclear how CB1R-mediated signalling affects the contraction and Ca²⁺ homeostasis of mammalian skeletal muscle. In the present study, we demonstrate that in vitro CB1R activation increased muscle fatigability and decreased the Ca(2+) -sensitivity of the contractile apparatus, whereas it did not alter the amplitude of single twitch contractions. In myotubes, CB1R agonists neither evoked, nor influenced inositol 1,4,5-trisphosphate (IP3 )-mediated Ca(2+) transients, nor did they alter excitation-contraction coupling. By contrast, in isolated muscle fibres of wild-type mice, although CB1R agonists did not evoke IP3 -mediated Ca(2+) transients too, they significantly reduced the amplitude of the depolarization-evoked transients in a pertussis-toxin sensitive manner, indicating a Gi/o protein-dependent mechanism. Concurrently, on skeletal muscle fibres isolated from CB1R-knockout animals, depolarization-evoked Ca(2+) transients, as well qas Ca(2+) release flux via ryanodine receptors (RyRs), and the total amount of released Ca(2+) was significantly greater than that from wild-type mice. Our results show that CB1R-mediated signalling exerts both a constitutive and an agonist-mediated inhibition on the Ca(2+) transients via RyR, regulates the activity of the sarcoplasmic reticulum Ca(2+) ATPase and enhances muscle fatigability, which might decrease exercise performance, thus playing a role in myopathies, and therefore should be considered during the development of new cannabinoid drugs.

CAS3D: 3D quantitative morphometry on Second Harmonic Generation image volumes from single skeletal muscle fibers - Schneidereit, Dominik; Bauer, Julian; Mnuskina, Sofia; Nübler, Stefanie; Cacciani, Nicola; Mühlberg, Alexander; Kreiß, Lucas; Ritter, Paul; Schürmann, Sebastian; Larsson, Lars; Friedrich, Oliver (Computers in Biology and Medicine, 2024)
The CAS3D image processing method intuitively applies a combination of Fourier space and real space 3D analysis algorithms to volumetric images of single skeletal muscle fiber Myosin II Second Harmonic Generation (SHG) XYZ image data. Our developed tool automatically quantifies the myofibrillar orientation in muscle samples by determining the cosine angle sum of intensity gradients in 3D (CAS3D) while determining the mean sarcomere length (SL) and sample orientation. The expected CAS3D values could be reproduced from ideal artificial data sets. Applied random noise in artificial images lowers the detected CAS3D value, and for noise levels below 20%, the correlation can be approximated by a linear function with a slope of −0.006 CAS3D/noise%. The deviations in SL and orientation detection were determined on ideal and noisy artificial data sets and were statistically indistinguishable from 0 (null hypothesis t-test P > 0.1). The software was applied to a previously published data set of single skeletal muscle fiber volumetric SHG image data from a rat intensive care unit (ICU) model of ventilator-induced diaphragm dysfunction (VIDD) with treatment regimens involving the small anti-inflammatory molecules BGP-15, vamorolone, or prednisolone. Our method reliably reproduced the results of the previous work and improved the standard deviation of the cosine angle sum detection in all sample groups from a mean of 0.03 to 0.008. This improvement is achieved by applying analysis algorithms to the whole volumetric images in 3D in contrast to the previously common method of slice-wise XY analysis.
CRIS-Team Scopus Importer:2024-07-19
Keywords: 3D image analysis; Quantitative morphometry; Second harmonic generation; Skeletal muscle; Software automation

Cell Viability Assays - Friedrich, Oliver; Gilbert, Daniel (2023)
This updated edition explores assessing cell viability as a measure for cell fitness under conditions of physiological and patho-physiological stress as well as challenging conditions to cellular and tissue homeostasis, and accounts for the ongoing 2D-to-3D development with topics and assays that target cell viability, mobility, and functionality of tissues and organs, natural or bioartificial, in 3D. The book’s contents span a wide range of viability and functionality assays, from impedance spectroscopy to chemiluminescence, fluorescence and label-free optical detection methodologies. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and up-to-date, Cell Viability Assays: Methods and Protocols, Second Edition serves as a valuable resource to the growing community in bioinspired life sciences, biomedical sciences, and biotechnology by providing more standardized protocols to probe the “wellbeing” of cells in various environment
Keywords: Cell fitness; Physiological and patho-physiological stress; 2D environments; 3D assays; Cell function; Biotechnology

Cell Viability Assays - Gilbert, Daniel; Friedrich, Oliver (Springer New York, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.ITC.stmmec.averag
Keywords: Cell rheology; Linear viscoelasticity; Narrow-gap rheometry; Cell monolayer

Changes in plasma membrane Ca-ATPase and stromal interacting molecule 1 expression levels for Ca(2+) signaling in dystrophic mdx mouse muscle. - Cully, Tanya R.; Edwards, Joshua N.; Friedrich, Oliver; Stephenson, D. George; Murphy, Robyn M; Launikonis, Bradley S. (American journal of physiology. Cell physiology, 2012)
The majority of the skeletal muscle plasma membrane is internalized as part of the tubular (t-) system, forming a standing junction with the sarcoplasmic reticulum (SR) membrane throughout the muscle fiber. This arrangement facilitates not only a rapid and large release of Ca(2+) from the SR for contraction upon excitation of the fiber, but has also direct implications for other interdependent cellular regulators of Ca(2+). The t-system plasma membrane Ca-ATPase (PMCA) and store-operated Ca(2+) entry (SOCE) can also be activated upon release of SR Ca(2+). In muscle, the SR Ca(2+) sensor responsible for rapidly activated SOCE appears to be the stromal interacting molecule 1L (STIM1L) isoform of STIM1 protein, which directly interacts with the Orai1 Ca(2+) channel in the t-system. The common isoform of STIM1 is STIM1S, and it has been shown that STIM1 together with Orai1 in a complex with the partner protein of STIM (POST) reduces the activity of the PMCA. We have previously shown that Orai1 and STIM1 are upregulated in dystrophic mdx mouse muscle, and here we show that STIM1L and PMCA are also upregulated in mdx muscle. Moreover, we show that the ratios of STIM1L to STIM1S in wild-type (WT) and mdx muscle are not different. We also show a greater store-dependent Ca(2+) influx in mdx compared with WT muscle for similar levels of SR Ca(2+) release while normal activation and deactivation properties were maintained. Interestingly, the fiber-averaged ability of WT and mdx muscle to extrude Ca(2+) via PMCA was found to be the same despite differences in PMCA densities. This suggests that there is a close relationship among PMCA, STIM1L, STIM1S, Orai1, and also POST expression in mdx muscle to maintain the same Ca(2+) extrusion properties as in the WT muscle.

Characterisation of passive mechanical properties in healthy and infarcted rat myocardium - Martonová, Denisa; Alkassar, Muhannad; Seufert, Julia; Holz, David; Duong, Minh Tuan; Reischl, Barbara; Friedrich, Oliver; Leyendecker, Sigrid (conference, GAMM Annual Meeting, 2021)

Characterization of two different alginate-based bioinks and the influence of melanoma growth within - Schipka, Raphael; Heltmann-Meyer, Stefanie; Schneidereit, Dominik; Friedrich, Oliver; Röder, Jonas; Boccaccini, Aldo R.; Schrüfer, Stefan; Schubert, Dirk W.; Horch, Raymund E.; Boßerhoff, Anja Katrin; Arkudas, Andreas; Kengelbach-Weigand, Annika; et al. (Scientific Reports, 2024)
Extrusion-based bioprinting is an established method in biofabrication. Suitable bioinks have fundamentally different compositions and characteristics, which should be examined, in order to find a perfect model system. Here, we investigate the effect of two alginate-based, yet unalike 3D-printed bioinks, pre-crosslinked alginate-dialdehyde gelatin (ADA-GEL) and a mixture of alginate, hyaluronic acid, and gelatin (Alg/HA/Gel), on the melanoma cell line Mel Im and vice versa in terms of stiffness, shrinkage, cellular behavior and colony formation over 15 days. Rheological stiffness measurements revealed two soft gels with similar storage moduli. The cells did not have a significant impact on the overall stiffness, whereas ADA-GEL (2.5/2.5%) was significantly stiffer than Alg/HA/Gel (0.5/0.1/3%). Regarding the shrinkage of printed constructs, cells had a significant influence, especially in ADA-GEL, which has covalent bonds between the oxidized alginate and gelatin. Multi-photon microscopy exhibited proliferation, cell spreading and migration in ADA-GEL with cell–cell and cell–matrix interaction, dissimilarly to Alg/HA/Gel, in which cells formed spherical, encapsulated colonies. Scanning electron microscopy and histology showed degradation and multi-layered growth on ADA-GEL and fewer examples of escaped cells on Alg/HA/Gel. Both gels serve as proliferation bioink for melanoma with more necrosis in deeper Alg/HA/Gel colonies and differences in spreading and matrix interaction. These findings show the importance of proper characterization of the bioinks for different applications.
CRIS-Team Scopus Importer:2024-06-14
Keywords: 3D-printing; Alginate; Hydrogel; Melanoma; Stiffness

Chloroquine exposure triggers distinct cellular responses in sensitive versus resistant Plasmodium falciparum parasites - Reiling, Sarah J; Krohne, Georg; Friedrich, Oliver; Geary, Timothy G; Rohrbach, Petra (Scientific Reports, 2018)

Clozapine sensing through paper-based microfluidic sensors directly modified via electro-deposition and electro-polymerization - Ghanbari, Mohammad Hossein; Biesalski, Markus; Friedrich, Oliver; Etzold, Bastian (Sensors & Diagnostics, 2024)
Microfluidic electrochemical sensors (μCS) can be portable, highly sensitive, and low-cost but are less frequently studied nor applied. Additionally, simultaneous electro-deposition of gold nanoparticles (ED (AuNPs)) and electro-polymerization of l-cysteine (EP (l-cys)) are introduced for the first time for modifying the surface of the working electrode through a paper-based microfluidic sensor. This study depicts that by employing such modification, the electrochemically active surface area (ECSA) and the electron transfer rate are increased together and result in improved sensitivity. The modified μCS is depicted to enable sensitive voltametric determination of, e.g., clozapine (CLZ), an anti-psychotic drug to treat schizophrenia. The proposed sensor was characterized by different techniques, and several key parameters were optimized. Under the optimum conditions and using square-wave voltametry (SWV), a linear dose-response for a concentration range from 0.5 to 10.0 μM of CLZ was achieved. The limit of detection and sensitivity resulted in 70.0 nM and 0.045 mA cm−2 μM−1, respectively. Besides, this excellent sensitivity combines with high stability, which was tested for six repetitive measurements with a single device resulting in high reproducibility. Additionally, this procedure was validated with measurements of clozapine in human blood plasma, which demonstrated the excellent applicability of the device, rendering it a promising platform for point-of-care diagnostics and environmental monitoring.
CRIS-Team Scopus Importer:2024-11-08

Complex mechanical behavior of human articular cartilage and hydrogels for cartilage repair - Weizel, A.; Distler, Thomas; Schneidereit, Dominik; Friedrich, Oliver; Bräuer, Lars; Paulsen, Friedrich; Detsch, Rainer; Boccaccini, Aldo R.; Budday, Silvia; Seitz, H. (Acta Biomaterialia, 2020)
The mechanical behavior of cartilage tissue plays a crucial role in physiological mechanotransduction processes of chondrocytes and pathological changes like osteoarthritis. Therefore, intensive research activities focus on the identification of implant substitute materials that mechanically mimic the cartilage extracellular matrix. This, however, requires a thorough understanding of the complex mechanical behavior of both native cartilage and potential substitute materials to treat cartilage lesions. Here, we perform complex multi-modal mechanical analyses of human articular cartilage and two surrogate materials, commercially available ChondroFillerliquid, and oxidized alginate-gelatin (ADA-GEL) hydrogels. We show that all materials exhibit nonlinearity and compression-tension asymmetry. However, while hyaline cartilage yields higher stresses in tension than in compression, ChondroFillerliquid and ADA-GEL exhibit the opposite trend. These characteristics can be attributed to the materials’ underlying microstructure: Both cartilage and ChondroFillerliquid contain fibrillar components, but the latter constitutes a bi-phasic structure, where the 60% nonfibrillar hydrogel proportion dominates the mechanical response. Of all materials, ChondroFillerliquid shows the most pronounced viscous effects. The present study provides important insights into the microstructure-property relationship of cartilage substitute materials, with vital implications for mechanically-driven material design in cartilage engineering. In addition, we provide a data set to create mechanical simulation models in the future.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Human articular cartilage; Hydrogels; Mechanical testing; Microstructure; Tissue engineering

Convergence of 3D printed biomimetic wound dressings and adult stem cell therapy. - Shafiee, Abbas; Cavalcanti, Amanda; Saidy, Navid T; Schneidereit, Dominik; Friedrich, Oliver; Ravichandran, Akhilandeshwari; De-Juan-Pardo, Elena M; Hutmacher, Dietmar W (Biomaterials, 2021)
Biomimetically designed medical-grade polycaprolactone (mPCL) dressings are 3D-printed with pore architecture and anisotropic mechanical characteristics that favor skin wound healing with reduced scarring. Melt electrowritten mPCL dressings are seeded with human gingival tissue multipotent mesenchymal stem/stromal cells and cryopreserved using a clinically approved method. The regenerative potential of fresh or frozen cell-seeded mPCL dressing is compared in a splinted full-thickness excisional wound in a rat model over six weeks. The application of 3D-printed mPCL dressings decreased wound contracture and significantly improved skin regeneration through granulation and re-epithelialization compared to control groups. Combining 3D-printed biomimetic wound dressings and precursor cell delivery enhances physiological wound closure with reduced scar tissue formation.

Corrigendum to "A portable low-cost long-term live-cell imaging platform for biomedical research and education" [Biosens. Bioelectron. 64 (2015) 639-649]. - Walzik, Maria P.; Vollmar, Verena; Lachnit, Theresa; Dietz, Helmut; Haug, Susanne; Bachmann, Holger; Fath, Moritz; Aschenbrenner, Daniel; Mofrad, Sepideh Abolpour; Friedrich, Oliver; Gilbert, Daniel (Biosensors and Bioelectronics, 2018)

Corrigendum to "Towards in vitro DT/DNT testing: Assaying chemical susceptibility in early differentiating NT2 cells" [Toxicology 338 (2015) 69-76]. - Menzner, Ann-Katrin; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Toxicology, 2017)

Critical Illness Myopathy (CIM) and Ventilator-Induced Diaphragm Muscle Dysfunction (VIDD): Acquired Myopathies Affecting Contractile Proteins. - Larsson, Lars; Friedrich, Oliver (Comprehensive Physiology, 2016)
Critical care and intensive care units (ICUs) have undergone dramatic changes and improvements in recent years, and critical care is today one of the fastest growing hospital disciplines. Significant improvements in treatments, removal of inefficient and harmful interventions, and introduction of advanced technological support systems have improved survival among critically ill ICU patients. However, the improved survival is associated with an increased number of patients with complications related to modern critical care. Severe muscle wasting and impaired muscle function are frequently observed in immobilized and mechanically ventilated ICU patients. Approximately 30% of mechanically ventilated and immobilized ICU patients for durations of five days and longer develop generalized muscle paralysis of all limb and trunk muscles. These patients typically have intact sensory and cognitive functions, a condition known as critical illness myopathy (CIM). Mechanical ventilation is a lifesaving treatment in critically ill ICU patients; however, the being on a ventilator creates dependence, and the weaning process occupies as much as 40% of the total time of mechanical ventilation. Furthermore, 20% to 30% of patients require prolonged intensive care due to ventilator-induced diaphragm dysfunction (VIDD), resulting in poorer outcomes, and greatly increased costs to health care providers. Our understanding of the mechanisms underlying both CIM and VIDD has increased significantly in the past decade and intervention strategies are presently being evaluated in different experimental models. This short review is restricted CIM and VIDD pathophysiology rather than giving a comprehensive review of all acquired muscle wasting conditions associated with modern critical care. © 2017 American Physiological Society. Compr Physiol 7:105-112, 2017.

Critical illness myopathy in intensive care patients: Pathogenetic concepts and clinical management - Friedrich, Oliver; Hund, Ernst (Anaesthesist, 2006)
Intensive care patients are at increased risk of developing sepsis with multi-organ failure during treatment (severe sepsis) possibly leading to complications of the central and peripheral nervous system. Among these, septic encephalopathy, critical illness polyneuropathy (CIP) and critical illness myopathy (CIM) are the most important. Neuromuscular complications in particular are difficult to diagnose as they mostly become apparent only when sedation has ceased and the awakening patient experiences difficulties in weaning from the respirator and reduced voluntary strength. CIP and CIM are generally self-limiting, however, they greatly prolong ICU stay and rehabilitation, thus nowadays also imposing a real budget threat. The diagnostics, especially the differentiation between CIM and CIP is difficult and a multi-disciplinary approach involving ICU physicians, anesthetists and neurologists is needed. Our knowledge of the causes of the primary ICU myopathy, although rapidly evolving during recent years, is still in its infancy and specific treatment of CIM is not yet available. The present overview summarizes insights into clinical and new diagnostic strategies for early detection of neuromuscular dysfunction in ICU patients. This article focuses on current concepts and results revealing the pathomechanism(s) of CIM and some simple therapeutic or preventive measures have been deduced which are summarized and discussed. © 2006 Springer Medizin Verlag.
Keywords: Antioxidative capacity; Critical illness; Insulin therapy; Myopathy; Pathomechanisms

Critical illness myopathy: Sepsis-mediated failure of the peripheral nervous system - Friedrich, Oliver (European Journal of Anaesthesiology, 2008)
With better survival of critically ill patients, 'de novo' arising neuromuscular complications like critical illness myopathy or polyneuropathy have been increasingly observed. Prolonged hospitalization not only imposes risks like pneumonia or thrombosis on patients but also represents a real budget threat to modern intensive-care medicine. Clinical symptoms like muscle weakness and weaning failure are common to critical illness myopathy and critical illness polyneuropathy and do not allow for distinction. Specific therapies are not yet available, and the quest for the pathomechanisms has proved more complicated than anticipated. Especially for critical illness myopathy, multiple sites of disturbances to the excitation-contraction coupling cascade are possible causes of muscle weakness. The present review summarizes the epidemiological, clinical and diagnostic features of critical illness myopathy and then focuses on current concepts of the presumed pathomechanisms of critical illness myopathy. Sepsis was shown to be a major cause of critical illness myopathy and special emphasis will be placed on how sepsis and inflammatory mediators influence (i) the membrane excitability at the level of voltage-gated ion channels and (ii) the intracellular protein signalling that results in selective loss of myosin protein content and muscle wasting. For (i), critical illness myopathy represents a new type of acquired channelopathy affecting the inactivation properties of Na channels. For (ii), both protein proteolysis and protein build up at the transcriptional level seem to be involved. Findings from different studies are put into a common context to propose a model for cytokine-mediated failure of muscle in severe sepsis. This can open a series of new possible trials to test specific therapeutic strategies in the future. © 2008 European Society of Anaesthesiology.
Keywords: Critical care; Mucular diseases; Myopathy; Neuromuscular diseases; Polyneuropathy; Sepsis

Critical illness myopathy serum fractions affect membrane excitability and intracellular calcium release in mammalian skeletal muscle. - Friedrich, Oliver; Hund, Ernst; Weber, Cornelia; Hacke, Werner; Fink, Rainer (Journal of Neurology, 2004)
The pathogenesis of myopathies occurring in critically ill patients (critical illness myopathy, CIM) is poorly understood. Both local and systemic responses to sepsis and other severe insults to the body are presumed to be involved but the precise mechanisms by which muscle function is impaired are far from clear. To elucidate such mechanisms we investigated the effects of blood serum fractions (5 kDa to 100 kDa molecular weight cut-off, MWCO) from patients with CIM and from control persons on membrane and contractile functions in intact mammalian single skeletal muscle fibres and chemically skinned fibre bundles. In intact fibres, resting membrane potentials were less negative when exposed to CIM serum fractions compared with control serum fractions. Half-width and maximum rise time of action potentials (AP) were smaller in CIM serum low MWCO fractions vs. control serum. Peak amplitudes of fast inward sodium currents (I(Na)) were increased by low MWCO-CIM fractions compared with control sera fractions. Additionally, voltage dependent inactivation of I(Na) was shifted towards more positive potentials by high MWCO fractions of CIM sera. In skinned fibres, pCa-force relations were similar in CIM and control serum fractions but peak force of Ca2+ induced force transients was decreased by low MWCO-CIM vs. control serum fractions. Our results (i) provide the first evidence that serum from CIM patients affects membrane excitability and the excitation-contraction coupling process at the level of the sarcoplasmic reticulum Ca2+ release of mammalian muscle fibres and (ii) also show that even control serum fractions "per se" alter the response to important physiological membrane and contractility parameters compared with physiological saline.

Critical illness myopathy: What is happening? - Friedrich, Oliver (Current Opinion in Clinical Nutrition and Metabolic Care, 2006)
PURPOSE OF REVIEW: The current review focuses on recent studies, both clinical and from basic sciences, which approach possible pathomechanisms of critical illness myopathy in order to better derive potential clinical strategies for a preventive or curative clinical setting. Trends and concepts of clinical diagnosis and handling will be evaluated and their implications for muscle physiology and nutritional/metabolic intervention discussed. RECENT FINDINGS: Conventional electrophysiology was combined with direct muscle stimulation to better differentiate critical illness myopathy from other neuromuscular disorders in critical illness. Muscle weakness was the result of impaired excitation-contraction-coupling at the level of the sarcolemma and the sarcoplasmic reticulum membrane. Critical illness may alter sodium and ryanodine receptor calcium-release channels. Also, increased muscle proteolysis contributes to weakness in critical illness myopathy. Myosin loss is due to the risk factors systemic inflammatory response syndrome/sepsis, steroids and neuromuscular blocking agents. Steroids can also induce necrosis and apoptosis in muscle. Inflammatory mediators aggravated muscle metabolic failure in critical illness myopathy. Ubiquitin-proteasome pathways, cyclooxygenase activation, altered glucose transporter expression, MyoD suppression, impaired respiratory chain enzymes, ATP depletion, glucose toxicity and insulin resistance can all contribute to the critical illness myopathy pathomechanism. SUMMARY: The search for pathomechanisms is an important task for both clinical and basic sciences. Targets for treatment or prevention of critical illness myopathy include systemic inflammatory response, increased proteolysis and reduced antioxidative capacitance in critically ill patients. © 2006 Lippincott Williams & Wilkins.
Keywords: Critical illness; Ec-coupling; Myopathy; Pathomechanism; SIRS; Steroids; Ubiquitin

DAPK1 loss triggers tumor invasion in colorectal tumor cells - Steinmann, Sara; Kunze, Philipp; Hampel, Chuanpit; Eckstein, Markus; Bertram Bramsen, Jesper; Muenzner, Julienne K.; Carlé, Birgitta-Elisabeth; Ndreshkjana, Benardina; Kemenes, Stephan; Gasparini, Pierluigi; Friedrich, Oliver; Andersen, Claus; et al. (Cell Death & Disease, 2019)
Colorectal cancer (CRC) is one of the leading cancer-related causes of death worldwide. Despite the improvement of surgical and chemotherapeutic treatments, as of yet, the disease has not been overcome due to metastasis to distant organs. Hence, it is of great relevance to understand the mechanisms responsible for metastasis initiation and progression and to identify novel metastatic markers for a higher chance of preventing the metastatic disease. The Death-associated protein kinase 1 (DAPK1), recently, has been shown to be a potential candidate for regulating metastasis in CRC. Hence, the aim of the study was to investigate the impact of DAPK1 protein on CRC aggressiveness. Using CRISPR/Cas9 technology, we generated DAPK1-deficient HCT116 monoclonal cell lines and characterized their knockout phenotype in vitro and in vivo. We show that loss of DAPK1 implemented changes in growth pattern and enhanced tumor budding in vivo in the chorioallantoic membrane (CAM) model. Further, we observed more tumor cell dissemination into chicken embryo organs and increased invasion capacity using rat brain 3D in vitro model. The novel identified DAPK1-loss gene expression signature showed a stroma typical pattern and was associated with a gained ability for remodeling the extracellular matrix. Finally, we suggest the DAPK1-ERK1 signaling axis being involved in metastatic progression of CRC. Our results highlight DAPK1 as an anti-metastatic player in CRC and suggest DAPK1 as a potential predictive biomarker for this cancer type.
CRIS-Team Scopus Importer:2019-12-10

Deeper Insight into the Six-Step Domino Reaction of Aldehydes with Malononitrile and Evaluation of Antiviral and Antimalarial Activities of the Obtained Bicyclic Products. - Bock, Christina; Gangajji, Parameshwarappa; Bönisch, Simon; Bauer, Walter; Hutterer, Corina; Leidenberger, Maria; Friedrich, Oliver; Marschall, Manfred; Kappes, Bärbel; Görling, Andreas; Tsogoeva, Svetlana (ChemistryOpen, 2017)
The straightforward and efficient synthesis of complex aza- and carbobicyclic compounds, which are of importance for medicinal chemistry, is a challenge for modern chemical methodology. An unprecedented metal-free six-step domino reaction of aldehydes with malononitrile was presented in our previous study to provide, in a single operation, these bicyclic nitrogen-containing molecules. Presented here is a deeper investigation of this atom-economical domino process by extending the scope of aldehydes, performing post-modifications of domino products, applying bifunctional organocatalysts and comprehensive NMR studies of selected domino products. The thermodynamic aspects of the overall reaction are also demonstrated using DFT methods in conjunction with a semi-empirical treatment of van der Waals interactions. Furthermore, biological studies of seven highly functionalized and artemisinin-containing domino products against human cytomegalovirus (HCMV) and Plasmodium falciparum 3D7 are presented. Remarkably, in vitro tests against HCMV revealed five domino products to be highly active compounds (EC50 0.071-1.8 μm), outperforming the clinical reference drug ganciclovir (EC50 2.6 μm). Against P. falciparum 3D7, three of the investigated artemisinin-derived domino products (EC50 0.72-1.8 nm) were more potent than the clinical drug chloroquine (EC50 9.1 nm).

Deﬁcient zERG channel gating causes short QT syndrome in zebraﬁsh reggae mutants. - Hassel, Daniel; Scholz, Eberhard P; Trano, Nicole; Friedrich, Oliver; Just, Steffen; Meder, Benjamin; Weiss, Daniel L.; Zitron, Edgar; Marquart, Sabine; Vogel, Britta; Karle, Christoph A.; Seemann, Gunnar; et al. (Circulation, 2008)
Background— Genetic predisposition is believed to be responsible for most clinically significant arrhythmias; however, suitable genetic animal models to study disease mechanisms and evaluate new treatment strategies are largely lacking. Methods and Results— In search of suitable arrhythmia models, we isolated the zebrafish mutation reggae (reg), which displays clinical features of the malignant human short-QT syndrome such as accelerated cardiac repolarization accompanied by cardiac fibrillation. By positional cloning, we identified the reg mutation that resides within the voltage sensor of the zebrafish ether-à-go-go–related gene (zERG) potassium channel. The mutation causes premature zERG channel activation and defective inactivation, which results in shortened action potential duration and accelerated cardiac repolarization. Genetic and pharmacological inhibition of zERG rescues recessive reg mutant embryos, which confirms the gain-of-function effect of the reg mutation on zERG channel function in vivo. Accordingly, QT intervals in ECGs from heterozygous and homozygous reg mutant adult zebrafish are considerably shorter than in wild-type zebrafish. Conclusions— With its molecular and pathophysiological concordance to the human arrhythmia syndrome, zebrafish reg represents the first animal model for human short-QT syndrome.

Depolarisation of the plasma membrane in the arsenic trioxide (As2O3)-and anti-CD95-induced apoptosis in myeloid cells. - Nolte, Florian; Friedrich, Oliver; ROjewski, Markus; Fink, Rainer; Schrezenmeier, Hubert; Körper, Sixten (Febs Letters, 2004)
Depolarisation of the plasma membrane has been shown to be actively regulated during lymphocyte-apoptosis. Here, we present data about anti-Fas and As2O3 induced depolarisation of myeloid U-937 cells. Anti-Fas but not As2O3-induced depolarisation was significantly dependent on caspase-activation. Na+-fluxes contributed to the depolarisation in early stages of As2O3-induced apoptosis, whereas the membrane potential in late stages depended on Cl- -fluxes. Cl- -channels also played an important role in the induction of cell shrinkage in As2O3-induced apoptosis. However, none of these ions contributed significantly to anti-Fas induced depolarisation. This indicates the existence of different mechanisms for apoptotic plasma membrane depolarisation within one cell type.

Depth-resolved and label-free imaging of artificial and native tissues with multiphoton microscopy - Vielreicher, Martin; Friedrich, Oliver (Second International Workshop: Molecular Imaging in Medical Research II (EnVision workshops), 2013)

DesR349P Mutation Results in Ultrastructural Disruptions and Compromise of Skeletal Muscle Biomechanics Already at Preclinical Stages in Young Mice before the Onset of Protein Aggregation - Diermeier, Stefanie; Haug, Michael; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhimine, F.; Stehle, Robert; Pfitzer, Gabriele; Winter, L.; et al. (Elsevier (Cell Press) / Biophysical Society, 2016)
Mutations in the extra-sarcomeric protein desmin give rise to protein aggregate myopathies that interfere with cellular function. The R350P mutation is the most common human desminopathy. A murine DesR349P model of human DesR350P desminopathy was previously engineered. In this study, we followed the hypothesis of whether muscle cytoarchitecture and biomechanical properties are already altered in preclinical stages of R349P desminopathy. We applied non-linear second harmonic generation (SHG) and 2-photon fluorescence morphometry analysis to single fibres of fast- and slow-twitch muscle to analyze sarcomeric architecture and nuclear morphology. We found a vast disruption of the lateral sarcomere lattice (indicated by large ‘vernier’ densities) and myofibrillar angular deviations (indicated by cosine angle sums) in single DesR349P fibres. Homozygous fibres were more severely affected than heterozygous. The former showed a marked nuclear pathology with spheric nuclei, increased nuclear number and density. For biomechanics, we assessed active and passive properties. Axial stiffness of DesR349P muscle was much increased, both in fibre and myofibrillar homozygous bundles. Lateral stiffness of the membrane complex in myoblasts was increased in cells heterozygous for DesR349P while homozygous were similar to wt. Caffeine-induced force was compromised in heterozygous fibre bundles but increased in homozygous bundles. This was explained by a marked shift of myofibrillar Ca2+ sensitivity: heterozygous bundles being less sensitive but homozygous more sensitive to Ca2+. This points towards a specific compensatory mechanism in homozygous mutation to cope with otherwise compromised force production already at preclinical stages of desminopathy. Our findings provide a very first complete picture to explain compromised force in heterozygous DesR350P patients: increased muscle stiffness, higher susceptibility towards stretch-induced injury, disrupted myofibrillar alignment and compromised active force productio

Diffuse reflectance spectroscopy and Raman spectroscopy for label-free molecular characterization and automated detection of human cartilage and subchondral bone - Kreiß, Lucas; Hohmann, Martin; Klämpfl, Florian; Schürmann, Sebastian; Dehghani, Faramarz; Schmidt, Michael; Friedrich, Oliver; Büchler, Lorenz (Sensors and Actuators B-Chemical, 2019)
Optical technologies hold potential for bio-medical research as well as the clinical routine, since they allow contact-free, non-destructive access to several clinically relevant features of tissues. In this study, diffuse reflectance spectroscopy and spontaneous Raman spectroscopy have been applied to human hip samples in order to characterize differences between cartilage and adjacent subchondral bone tissue. Mathematical decomposition of absorption and scattering properties is an important aspect in diffuse reflectance data analysis. Here, we present the novel application of Bayesian statistics to this analysis, which can extract probability density spectra of the absorption coefficient and the scattering coefficient. Using this concept of a Bayesian decomposition algorithm for the spectral decomposition, it was possible to find characteristic differences in the relative concentration of melanin and haemoglobin as well as in scattering properties. Furthermore, this allowed a reconstruction of probability density plots for scattering coefficient and absorption coefficient instead of singular values. Complemented by the results of Raman spectroscopy, it was further possible to detect significant differences in the ratio of minerals (such as hydroxyl apatite) to bio-molecules (such as proteins) when comparing bony tissue regions to the surrounding cartilage. Finally, it was possible to use these molecular contrast mechanisms for highly-accurate, automated tissue classification using machine learning algorithms on the level of individual patients.
CRIS-Team Scopus Importer:2019-10-04
Keywords: Bayesian inference; Bone; Cartilage; Diffuse reflectance spectroscopy; Label-free; Machine learning; Raman spectroscopy

Digital staining in optical microscopy using deep learning - a review - Kreiss, Lucas; Jiang, Shaowei; Li, Xiang; Xu, Shiqi; Zhou, Kevin C.; Lee, Kyung Chul; Mühlberg, Alexander; Kim, Kanghyun; Chaware, Amey; Ando, Michael; Barisoni, Laura; Lee, Seung Ah A.; et al. (PhotoniX, 2023)
Until recently, conventional biochemical staining had the undisputed status as well-established benchmark for most biomedical problems related to clinical diagnostics, fundamental research and biotechnology. Despite this role as gold-standard, staining protocols face several challenges, such as a need for extensive, manual processing of samples, substantial time delays, altered tissue homeostasis, limited choice of contrast agents, 2D imaging instead of 3D tomography and many more. Label-free optical technologies, on the other hand, do not rely on exogenous and artificial markers, by exploiting intrinsic optical contrast mechanisms, where the specificity is typically less obvious to the human observer. Over the past few years, digital staining has emerged as a promising concept to use modern deep learning for the translation from optical contrast to established biochemical contrast of actual stainings. In this review article, we provide an in-depth analysis of the current state-of-the-art in this field, suggest methods of good practice, identify pitfalls and challenges and postulate promising advances towards potential future implementations and applications.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Deep learning; Digital staining; Generative models; Image translation; In-silica; Optical microscopy; Pseudo-H& E; Virtual fluorescence; Virtual staining

Dynamic cytoskeletal regulation of cell shape supports resilience of lymphatic endothelium - Schoofs, Hans; Daubel, Nina; Schnabellehner, Sarah; Grönloh, Max L.B.; Palacios Martínez, Sebastián; Halme, Aleksi; Marks, Amanda M.; Jeansson, Marie; Barcos, Sara; Brakebusch, Cord; Benedito, Rui; Engelhardt, Britta; et al. (Nature, 2025)
Lymphatic capillaries continuously take up interstitial fluid and adapt to resulting changes in vessel calibre1, 2–3. The mechanisms by which the permeable monolayer of loosely connected lymphatic endothelial cells (LECs)4 maintains mechanical stability remain elusive. Here we identify dynamic cytoskeletal regulation of LEC shape, induced by isotropic stretch, as crucial for the integrity and function of dermal lymphatic capillaries. We found that the oak leaf-shaped LECs showed a spectrum of VE-cadherin-based junctional configurations at the lobular intercellular interface and a unique cytoskeletal organization, with microtubules at concave regions and F-actin at convex lobes. Multispectral and longitudinal intravital imaging of capillary LEC shape and actin revealed dynamic remodelling of cellular overlaps in vivo during homeostasis and in response to interstitial fluid volume increase. Akin to puzzle cells of the plant epidermis5,6, LEC shape was controlled by Rho GTPase CDC42-regulated cytoskeletal dynamics, enhancing monolayer stability. Moreover, cyclic isotropic stretch increased cellular overlaps and junction curvature in primary LECs. Our findings indicate that capillary LEC shape results from continuous remodelling of cellular overlaps that maintain vessel integrity while preserving permeable cell–cell contacts compatible with vessel expansion and fluid uptake. We propose a bellows-like fluid propulsion mechanism, in which fluid-induced lumen expansion and shrinkage of LEC overlaps are countered by actin-based lamellipodia-like overlap extension to aid vessel constriction.
CRIS-Team Scopus Importer:2025-04-01

Early signs of architectural and biomechanical failure in isolated myofibers and immortalized myoblasts from desmin-mutant knock-in mice - Diermeier, Stefanie; Iberl, Julian; Vetter, Karoline; Haug, Michael; Pollmann, Charlotte; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhamine, Fatiha; et al. (Scientific Reports, 2017)
In striated muscle, desmin intermediate filaments interlink the contractile myofibrillar apparatus with mitochondria, nuclei, and the sarcolemma. The desmin network's pivotal role in myocytes is evident since mutations in the human desmin gene cause severe myopathies and cardiomyopathies. Here, we investigated skeletal muscle pathology in myofibers and myofibrils isolated from young hetero- and homozygous R349P desmin knock-in mice, which carry the orthologue of the most frequent human desmin missense mutation R350P. We demonstrate that mutant desmin alters myofibrillar cytoarchitecture, markedly disrupts the lateral sarcomere lattice and distorts myofibrillar angular axial orientation. Biomechanical assessment revealed a high predisposition to stretch-induced damage in fiber bundles of R349P mice. Notably, Ca(2)(+)-sensitivity and passive myofibrillar tension were decreased in heterozygous fiber bundles, but increased in homozygous fiber bundles compared to wildtype mice. In a parallel approach, we generated and subsequently subjected immortalized heterozygous R349P desmin knock-in myoblasts to magnetic tweezer experiments that revealed a significantly increased sarcolemmal lateral stiffness. Our data suggest that mutated desmin already markedly impedes myocyte structure and function at pre-symptomatic stages of myofibrillar myopathies.
EVALuna2:7360

Effect of insulin insufficiency on ultrastructure and function in skeletal muscle - Kopecky, Chantal; Haug, Michael; Reischl, Barbara; Deshpande, Nandan; Manandhar, Bikash; King, Thomas W.; Lee, Victoria; Wilkins, Marc R.; Morris, Margaret; Polly, Patsie; Friedrich, Oliver; Rye, Kerry Anne; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2023)
Background: Decreased insulin availability and high blood glucose levels, the hallmark features of poorly controlled diabetes, drive disease progression and are associated with decreased skeletal muscle mass. We have shown that mice with β-cell dysfunction and normal insulin sensitivity have decreased skeletal muscle mass. This project asks how insulin deficiency impacts on the structure and function of the remaining skeletal muscle in these animals. Methods: Skeletal muscle function was determined by measuring exercise capacity and specific muscle strength prior to and after insulin supplementation for 28 days in 12-week-old mice with conditional β-cell deletion of the ATP binding cassette transporters ABCA1 and ABCG1 (β-DKO mice). Abca1 and Abcg1 floxed (fl/fl) mice were used as controls. RNAseq was used to quantify changes in transcripts in soleus and extensor digitorum longus muscles. Skeletal muscle and mitochondrial morphology were assessed by transmission electron microscopy. Myofibrillar Ca2+ sensitivity and maximum isometric single muscle fibre force were assessed using MyoRobot biomechatronics technology. Results: RNA transcripts were significantly altered in β-DKO mice compared with fl/fl controls (32 in extensor digitorum longus and 412 in soleus). Exercise capacity and muscle strength were significantly decreased in β-DKO mice compared with fl/fl controls (P = 0.012), and a loss of structural integrity was also observed in skeletal muscle from the β-DKO mice. Supplementation of β-DKO mice with insulin restored muscle integrity, strength and expression of 13 and 16 of the dysregulated transcripts in and extensor digitorum longus and soleus muscles, respectively. Conclusions: Insulin insufficiency due to β-cell dysfunction perturbs the structure and function of skeletal muscle. These adverse effects are rectified by insulin supplementation.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Insulin; Muscle function; Muscle structure; Skeletal muscle

Effects of Adjuvant Exercise and Nutrition Therapy on Muscle Fibre Biomechanics in Gastrointestinal Cancer Patients - Haug, Michael; Schwappacher, Raphaela; Pollmann, Charlotte; Ritter, Paul; Michael, Mena; Herrmann, Hans Joachim; Grützmann, Robert; Mittelstädt, Anke; Neurath, Markus; Zopf, Yurdagül; Friedrich, Oliver (Cancers, 2024)
Patients with aggressive cancer, e.g., gastrointestinal cancer, are prone (≥50% chance) to developing cancer cachexia (CC). Little is known about the effects of CC on the biomechanical function of muscle. A promising prevention strategy was found in the form of a multi-modal therapy combining mild resistance exercise (e.g., whole-body electro-myostimulation, WB-EMS) and a protein-rich diet. In a previous study of ours, this was effective in counteracting the loss of muscle mass, yet a systematic and comprehensive assessment of active and passive single muscle fibre functions was so far absent. This pilot study investigated the biomechanical function of single muscle fibres (rectus abdominis) from the biopsies of conventionally treated (pre-)cachectic cancer ((pre-)CC) patients (m = 9), those receiving the multi-modal therapy comprising WB-EMS training and protein-rich nutrition (m = 3), and a control group (m = 5). Our findings not only align with previous findings showing the absolute force loss in CC that is accelerated by atrophy but also speak in favour of a different, potentially energy- and Ca2+-homeostasis-related effect that compromises muscle contraction (F 0.9 mN vs. F 0.6 mN in control patients). However, myofibrillar Ca2+ sensitivity and the quality of contraction were unaltered (pCa50: 5.6–5.8). Single fibres from the (pre-)CC patients receiving WB-EMS training and protein supplementation were significantly more compliant (p < 0.001 at ≥130% of resting length L0). Those fibres displayed a similar softness to the ones from the control patients (axial compliance 15 m/N at ≥130% L0), while single fibres from the patients with (developing) cachexia were significantly stiffer (axial compliance 7 m/N, p < 0.001 at ≥130% L0). Adjuvant multi-modal therapy (WB-EMS training and nutritional support) contributes to maintaining the axial compliance of single fibres and potentially improves the quality of life for patients at risk of developing CC.
CRIS-Team Scopus Importer:2024-05-03
Keywords: cancer cachexia; multi-modal therapy; protein-rich diet; resistance training; single fibres; skeletal muscle

Effects of Material-Tissue Interactions on Bone Regeneration Outcomes Using Baghdadite Implants in a Large Animal Model - Li, Jiao Jiao; Akey, Austin; Dunstan, Colin; Vielreicher, Martin; Friedrich, Oliver; Bell, David C.; Zreiqat, Hala (Advanced Healthcare Materials, 2018)
Extensive bone loss due to trauma or disease leads to impaired healing. Current bone grafts and substitutes have major drawbacks that limit their effectiveness for treating large bone defects. A number of bone substitutes in development are undergoing preclinical testing, but few studies specifically investigate the in vivo material-tissue interactions that provide an important indicator to long-term implant safety and efficacy. This study is the first of its kind to specifically investigate in vivo material-tissue interactions at the bone-implant interface. Baghdadite scaffolds implanted in critical-sized segmental defects in sheep tibia for 26 weeks are analyzed by focused ion beam scanning electron microscopy, multiphoton microscopy, and histology. The scaffolds are seen to induce extensive bone formation that directly abut the implant surfaces with no evidence of chronic inflammation or fibrous capsule formation. Bone remodeling is influenced by slow in vivo degradation around and within the implant, causing portions of the implant to be incorporated into the newly formed bone. These findings have important implications for predicting the long-term effects of baghdadite ceramics in promoting defect healing, and support the translation of baghdadite scaffolds as a new generation of bone graft substitutes with improved properties for the repair of large bone defects.

Electrically Conductive and 3D-Printable Oxidized Alginate-Gelatin Polypyrrole:PSS Hydrogels for Tissue Engineering - Distler, Thomas; Polley, Christian; Shi, Fukun; Schneidereit, Dominik; Ashton, Mark D.; Friedrich, Oliver; Kolb, Jürgen F.; Hardy, John G.; Detsch, Rainer; Seitz, Hermann; Boccaccini, Aldo R. (Advanced Healthcare Materials, 2021)
Electroactive hydrogels can be used to influence cell response and maturation by electrical stimulation. However, hydrogel formulations which are 3D printable, electroactive, cytocompatible, and allow cell adhesion, remain a challenge in the design of such stimuli-responsive biomaterials for tissue engineering. Here, a combination of pyrrole with a high gelatin-content oxidized alginate-gelatin (ADA-GEL) hydrogel is reported, offering 3D-printability of hydrogel precursors to prepare cytocompatible and electrically conductive hydrogel scaffolds. By oxidation of pyrrole, electroactive polypyrrole:polystyrenesulfonate (PPy:PSS) is synthesized inside the ADA-GEL matrix. The hydrogels are assessed regarding their electrical/mechanical properties, 3D-printability, and cytocompatibility. It is possible to prepare open-porous scaffolds via bioplotting which are electrically conductive and have a higher cell seeding efficiency in scaffold depth in comparison to flat 2D hydrogels, which is confirmed via multiphoton fluorescence microscopy. The formation of an interpenetrating polypyrrole matrix in the hydrogel matrix increases the conductivity and stiffness of the hydrogels, maintaining the capacity of the gels to promote cell adhesion and proliferation. The results demonstrate that a 3D-printable ADA-GEL can be rendered conductive (ADA-GEL-PPy:PSS), and that such hydrogel formulations have promise for cell therapies, in vitro cell culture, and electrical-stimulation assisted tissue engineering.
CRIS-Team Scopus Importer:2021-03-19
Keywords: 3D-printing; biomaterials; electrically conductive hydrogels; oxidized alginate; polypyrrole; tissue engineering

Electrophysiological investigations of peripheral nerves and muscles: a method for looking at cell dysfunction in the critically ill patients - Latronico, Nicola; Friedrich, Oliver (Critical Care, 2019)
Keywords: Muscle weakness; Polyneuropathy; Myopathy; Organ dysfunction; Mitochondrial dysfunction; Energy metabolism

Elementary Ca2+ release events in mammalian skeletal muscle: effects of the anaesthetic drug thiopental. - von Wegner, Frederic; Both, Martin; Fink, Rainer; Friedrich, Oliver (Journal of Muscle Research and Cell Motility, 2006)
We examined the effect of clinically relevant doses of thiopental (10-100 microM) on Ca2+ release from the sarcoplasmic reticulum of chemically skinned skeletal muscle fibres of the mouse. Elementary Ca2+ release events (ECRE) were recorded with confocal microscopy and were detected and analysed by an automated algorithm. Thiopental at 25 microM evoked a marked increase in ECRE frequency (events/100 microm/s) from 0.64 +/- 0.32 to 1.56 +/- 0.38 (P < 0.001). Incubation with 5 microM ryanodine significantly reduced spontaneous and evoked ECRE frequencies to 0.08 +/- 0.08 (P < 0.001) and 0.39 +/- 0.25 (25 microM thiopental, P < 0.001) respectively. Thiopental-evoked ECRE show different morphological characteristics compared to spontaneous events. Maximum relative amplitudes (DeltaF/F0)max and spatial width (full width at half maximum) of the events were substantially increased. Full duration at half maximum was increased and some very long events (200 ms compared to approximately 30 ms standard) were produced. The rise times as an indicator of the channel open time were slightly increased. Furthermore, the occurrence of repetitive ECRE was observed. These events, in contrast to previous observations in amphibian skeletal muscle fibres, displayed a multitude of different release patterns. In particular, a repetitive ECRE mode with successively decaying amplitudes was identified and the inter-event intervals were analysed. Estimation of the underlying Ca2+ release current suggests that during repetitive events with a decaying amplitude a decreasing amount of Ca2+ was released within the individual release event. Possible underlying mechanisms are discussed. In summary, thiopental seems to be a potent RyR1 agonist and substantially alters the gating mechanisms of RyR Ca2+ release channel clusters already in clinically relevant doses, i.e. doses administered during general anaesthesia.

Enhanced muscle shortening and impaired Ca2+ channel function in an acute septic myopathy model. - Friedrich, Oliver; Hund, Ernst; von Wegner, Frederic (Journal of Neurology, 2010)
Myopathies in critically ill patients are increasingly documented. Various animal models of chronic sepsis have been employed to investigate reduced membrane excitability or altered isometric contractility of skeletal muscle. In contrast, immediate changes occurring during acute sepsis are significantly under-characterised; L-type Ca(2+) channel function or isotonic shortening are examples. We recorded slowly activating L-type Ca(2+) currents (I (Ca)) in voltage-clamped single intact mouse skeletal muscle fibres and tested the effects of acute challenge with serum fractions from critical illness myopathy patients (CIM). Using a high-speed camera system, we simultaneously recorded unloaded fibre shortening during isotonic contractions with unprecedented temporal resolution (approximately 1,600 frames/s). Time courses of fibre lengths and shortening velocity were determined from automated imaging algorithms. CIM fractions acutely induced depression of I (Ca) amplitudes with no shifts in I (Ca)-V-relations. Voltage-dependent inactivation was unaltered and I (Ca) activation and inactivation kinetics were prolonged compared to controls. Unexpectedly, maximum unloaded speed of shortening was slightly faster following CIM serum applications, suggesting a direct action of CIM serum on weak-binding-state cross-bridges. Our results are compatible with a model where CIM serum might acutely reduce a fraction of functional L-type Ca(2+) channels and could account for reduced SR Ca(2+) release and force production in CIM patients. Acute increase in isotonic shortening velocity might be an early diagnostic feature suitable for testing in clinical studies. The acute challenge model is also robust against atrophy or fibre type changes that ordinarily would have to be considered in chronic sepsis models.
Keywords: Skeletal muscle; Critical illness myopathy; Patient serum fractions; Ca2+ currents; Muscle shortening; High-speed imaging

Enzymatically dissociated muscle fibers display rapid dedifferentiation and impaired mitochondrial calcium control - Gineste, Charlotte; Youhanna, Sonia; Vorrink, Sabine U.; Henriksson, Sara; Hernández, Andrés; Cheng, Arthur J.; Chaillou, Thomas; Buttgereit, Andreas; Schneidereit, Dominik; Friedrich, Oliver; Hultenby, Kjell; Bruton, Joseph D.; et al. (iScience, 2022)
Cells rapidly lose their physiological phenotype upon disruption of their extracellular matrix (ECM)-intracellular cytoskeleton interactions. By comparing adult mouse skeletal muscle fibers, isolated either by mechanical dissection or by collagenase-induced ECM digestion, we investigated acute effects of ECM disruption on cellular and mitochondrial morphology, transcriptomic signatures, and Ca2+ handling. RNA-sequencing showed striking differences in gene expression patterns between the two isolation methods with enzymatically dissociated fibers resembling myopathic phenotypes. Mitochondrial appearance was grossly similar in the two groups, but 3D electron microscopy revealed shorter and less branched mitochondria following enzymatic dissociation. Repeated contractions resulted in a prolonged mitochondrial Ca2+ accumulation in enzymatically dissociated fibers, which was partially prevented by cyclophilin inhibitors. Of importance, muscle fibers of mice with severe mitochondrial myopathy show pathognomonic mitochondrial Ca2+ accumulation during repeated contractions and this accumulation was concealed with enzymatic dissociation, making this an ambiguous method in studies of native intracellular Ca2+ fluxes.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cell biology; Cellular physiology; Developmental biology; Functional aspects of cell biology

Erratum: Depolarisation of the plasma membrane in the arsenic trioxide (As2O3)- and anti-CD95-induced apoptosis in myeloid cells (FEBS 29005) (FEBS Letters (2004) 578 (85-89) DOI 10.1016/j.febslet.2004.10.075) - Nolte, Florian; Friedrich, Oliver; ROjewski, Markus; Fink, Rainer; Schrezenmeier, Hubert; Körper, Sixten (Febs Letters, 2005)

Establishment and validation of recombinant cell lines for high-throughput DNT testing - Künzel, Katharina; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Acta Physiologica, 2015)

Estimating the 3D pore size distribution of biopolymer networks from directionally biased data. - Lang, Nadine; Münster, Stefan; Metzner, Claus; Krauß, Patrick; Schürmann, Sebastian; Lange, Janina; Aifantis, Katerina E.; Friedrich, Oliver; Fabry, Ben (Biophysical Journal, 2013)
The pore size of biopolymer networks governs their mechanical properties and strongly impacts the behavior of embedded cells. Confocal reflection microscopy and second harmonic generation microscopy are widely used to image biopolymer networks; however, both techniques fail to resolve vertically oriented fibers. Here, we describe how such directionally biased data can be used to estimate the network pore size. We first determine the distribution of distances from random points in the fluid phase to the nearest fiber. This distribution follows a Rayleigh distribution, regardless of isotropy and data bias, and is fully described by a single parameter–the characteristic pore size of the network. The bias of the pore size estimate due to the missing fibers can be corrected by multiplication with the square root of the visible network fraction. We experimentally verify the validity of this approach by comparing our estimates with data obtained using confocal fluorescence microscopy, which represents the full structure of the network. As an important application, we investigate the pore size dependence of collagen and fibrin networks on protein concentration. We find that the pore size decreases with the square root of the concentration, consistent with a total fiber length that scales linearly with concentration.

Evidence for activation of endogenous transporters in Xenopus laevis oocytes expressing the Plasmodium falciparum chloroquine resistance transporter, PfCRT. - Nessler, Susanne; Friedrich, Oliver; Bakouh, Naziha; Fink, Rainer; Sanchez, Cecilia P; Planelles, Gabrielle; Lanzer, Michael (Journal of Biological Chemistry, 2004)
A large body of genetic, reverse genetic, and epidemiological data has linked chloroquine-resistant malaria to polymorphisms within a gene termed pfcrt in the human malarial parasite Plasmodium falciparum. To investigate the biological function of the chloroquine resistance transporter, PfCRT, as well as its role in chloroquine resistance, we functionally expressed this protein in Xenopus laevis oocytes. Our data show that PfCRT-expressing oocytes exhibit a depolarized resting membrane potential and a higher intracellular pH compared with control oocytes. Pharmacological and electrophysiological studies link the higher intracellular pH to an enhanced amiloride-sensitive H(+) extrusion and the low membrane potential to an activated nonselective cation conductance. The finding that both properties are independent of each other, together with the fact that they are endogenously present in X. laevis oocytes, supports a model in which PfCRT activates transport systems. Our data suggest that PfCRT plays a role as a direct or indirect activator or modulator of other transporters.

Extracellular matrix collagen-I fibrillar networks in bone tissue engineering – analysis with SHG and multiphoton microscopy - Vielreicher, Martin; Detsch, Rainer; Boccaccini, Aldo R.; Friedrich, Oliver (5th International Congress on Stem Cells and Tissue Formation (Deutsche Gesellschaft für Zytometrie, DGfZ), 2014)
Question: Bone Tissue Engineering: Do mesenchymal stem cells (MSC`s) form better and more collagen-I fibers in 3D vs 2D cell culture? Methods: MSC`s isolated from rat femur were tested in 2D (monolayers, biomaterial films) vs. 3D systems (pellet, hydrogel or scaffold cultures) and grown in normal or serum-reduced or in osteogenic medium (1% FBS). Bone tissue-relevant biomaterials were cross-linked alginate-gelatin, collagen-I, PCL and PCL-Bioglass. Cells were imaged with label-free and depthresolved multiphoton microscopy by their autofluorescence or nuclear/membrane stainings. Produced collagen-I fibers were detected using second harmonic generation (SHG) and, as control, immunofluorescence (IF). Parallel collagen-I detection occurred using Western Blotting (WB) after solubilization with pepsin at pH2. Results: WB and IF analysis showed that MSC`s formed collagen-I in both 2D and 3D systems in plain and biomaterial containing constructs. Fibrous collagen susceptible to SHG, however, was detected in monolayers (2D) only after stimulation with osteogenic medium. In contrast, clear and strong fiber networks appeared in cell pellets. Depending on culture media these networks differed largely in their morphology and resembled the appearance in native tissue (Fig. 1). Simultaneous SHG/AF imaging at 810nm enabled detailed imaging and 3D reconstructions of the artificial tissues (cells with surrounding collagen-I). Conclusions: MSC`s require a 3D surrounding and high initial cell density to effectively form thick and stable fibers and fiber networks. These are preferably imaged using SHG which preferably detects larger and highly assembled fibers rather than thin fibrils (Vielreicher et al. 2013. J R Soc Interface, 10(86):20130263). The differentiation state of MSC`s has a large effect on the morphology of the formed collagen networks. The collagen fibers formed in 2D cell culture are not comparably stable, putatively due to less and weaker focal adhesion contacts. Studying collagen fiber and ECM networks in general is of high interest in the engineering of artificial tissue

Extracorporeal perfusion - reduced to a one-way infusion. - Taeger, Christian Dirk; Friedrich, Oliver; Horch, Raymund E.; Drechsler, Caroline; Weigand, Annika; Hopf, Fabio; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Wenzel, Carina; Geis, Sebastian; Prantl, Lukas; et al. (Clinical hemorheology and microcirculation, 2017)
BACKGROUND Extracorporeal perfusion (EP) is moving into focus of research in reconstructive and transplantation medicine for the preservation of amputates and free tissue transplants. The idea behind EP is the reduction of ischemia-related cell damage between separation from blood circulation and reanastomosis of the transplant. Most experimental approaches are based on a complex system that moves the perfusate in a circular course. OBJECTIVE AND METHODS In this study, we aimed to evaluate if a simple perfusion by an infusion bag filled with an electrolyte solution can provide acceptable results in terms of flow stability, oxygen supply and viability conservation for EP of a muscle transplant. The results are compared to muscles perfused with a pump system as well as muscles stored under ischemic conditions with a one-time intravasal flushing with Jonosteril. RESULTS With this simple method a sufficient oxygen supply could be achieved and functionality could be maintained between 3.35 times and 4.60 times longer compared to the control group. Annexin V positive nuclei, indicating apoptosis, increased by 9.7% in the perfused group compared to 24.4% in the control group. CONCLUSIONS Overall, by decreasing the complexity of the system, EP by one-way infusion can become more feasible in clinical situation

Fast XYT imaging of elementary calcium release events in muscle with multifocal multiphoton microscopy and wavelet denoising and detection. - von Wegner, Frederic; Both, Martin; Fink, Rainer; Friedrich, Oliver (IEEE Transactions on Medical Imaging, 2007)
We used multifocal multiphoton microscopy to image fast, localized elevations of the cytosolic Ca2+ concentration in two spatial dimensions plus time (XYT). This technique extends the common spatially 1-D XT imaging and allows the acquisition of more than ten times longer time series (>500 images) and ten times larger areas of interest than for previously used confocal XYT imaging techniques due to lower phototoxicity and fast multifocal scanning. We recorded spontaneously occurring elementary Ca2+ release events in chemically permeabilized adult mammalian skeletal muscle fibers using two-photon excitation of the fluorescent dye Fluo-4. The resulting time series were analyzed with an automated denoising and detection algorithm based on the à trous implementation of the discrete wavelet transform. Wavelet coefficient hard-thresholding is used for denoising and event detection is performed across several wavelet scales. The spatiotemporal characteristics of the detected Ca2+ release events are followed throughout the XYT stack and are parametrized using a biophysically valid anisotropic Gaussian event model. The proposed method allows a detailed spatiotemporal analysis of elementary Ca2+ release events underlying the excitation-contraction coupling process in muscle.
Keywords: biomedical optical imaging; calcium; cellular biophysics; image denoising; muscle; optical microscopy; wavelet transforms

From chaos to split-ups - SHG microscopy reveals a specific remodelling mechanism in ageing dystrophic muscle - Buttgereit, Andreas; Weber, Cornelia; Garbe, Christoph S.; Friedrich, Oliver (Journal of Pathology, 2013)
Duchenne muscular dystrophy (DMD) is a common inherited muscle disease showing chronic inflammation and progressive muscle weakness. Absent dystrophin renders sarcolemma more Ca(2+) -permeable, disturbs signalling and triggers inflammation. Sustained degeneration/regeneration cycles render muscle cytoarchitecture susceptible to remodelling. Quantitative morphometry was introduced in living cells using second-harmonic generation (SHG) microscopy of myosin. As the time course of cellular remodelling is not known, we used SHG microscopy in mdx muscle fibres over a wide age range for three-dimensional (3D) rendering and detection of verniers and cosine angle sums (CASs). Wild-type (wt) and transgenic mini-dystrophin mice (MinD) were also studied. Vernier densities (VDs) declined in wt and MinD fibres until adulthood, while in mdx fibres, VDs remained significantly elevated during the life span. CAS values were close to unity in adult wt and MinD fibres, in agreement with tight regular myofibril orientation, while always smaller in mdx fibres. Using SHG 3D morphometry, we identified two types of altered ultrastructure: branched fibres and a novel, previously undetected 'chaotic' fibre type, both of which can be classified by distinct CAS and VD combinations. We present a novel model of tissue remodelling in dystrophic progression with age that involves the transition from normal to chaotic to branched fibres. Our model predicts a 50% contribution of altered cytoarchitecture to progressive force loss with age. We also provide an improved automated image algorithm that is suitable for future ageing studies in human myopathies.
Keywords: muscular dystrophy; microarchitecture; second harmonic generation; cosine angle sum; vernier

GABAmimetic intravenous anaesthetics inhibit spontaneous Ca 2+-oscillations in cultured hippocampal neurons - Sinner, Barbara; Friedrich, Oliver; Zink, Wolfgang; Fink, Rainer; Graf, Bernhard (Acta Anaesthesiologica Scandinavica, 2006)
BACKGROUND Spontaneous Ca2+ -oscillations are a possible mechanism of Ca2+ -mediated signal transduction in neurons. They develop by a periodical interplay of Ca2+, which enters the neuron from the extracellular medium and triggers Ca2+ release from the endoplasmic reticulum (ER). Ca2+ -oscillations are terminated by reuptake into the ER or plasmalemmal extrusion. Spontaneous Ca2+ -oscillations are glutamate dependent and appear to be responsible for neuronal plasticity and integration of information. Here, we examined the role of the gamma-aminobutyric acid (GABAA) receptor on spontaneous Ca2+ -oscillations and studied the effects of the anaesthetics midazolam, thiopental and the non-anesthetic barbituric acid on spontaneous Ca2+ -oscillations. METHODS Hippocampal neuronal cell cultures of 19-day-old embryonic Wistar rats 17-18 days in culture were loaded with the Ca2+ -sensitive dye Fura-2AM. Experiments were performed using dual wave-length excitation fluorescence microscopy and calibration constants were obtained from in situ calibration. RESULTS Spontaneous Ca2+ -oscillations are influenced by the GABAA receptor. The intravenous anaesthetics midazolam and thiopental suppressed the amplitude and frequency reversibly in a dose-dependent manner with EC50 in clinically relevant concentrations. This effect was mediated via the GABAA receptor as it could be reversed by the GABAA receptor antagonist bicuculline. In contrast, the application of barbituric acid had no effects on the spontaneous Ca2+ -oscillations. CONCLUSION Spontaneous Ca2+ -oscillations are influenced by the GABAA receptor. Spontaneous Ca2+ -oscillations might represent an interesting model system to study anaesthetic mechanisms on neuronal information processing.
Keywords: Barbituric acid; GABAa receptor; Midazolam; Spontaneous Ca2+-oscillations; Thiopental

Gelatin methacryloyl is a slow degrading material allowing vascularization and long-term use in vivo - Heltmann-Meyer, Stefanie; Steiner, Dominik; Mueller, Claudia; Schneidereit, Dominik; Friedrich, Oliver; Salehi, Sahar; Engel, Felix; Arkudas, Andreas; Horch, Raymund E. (Biomedical Materials, 2021)
In situ tissue engineering is an emerging field aiming at the generation of ready-to-use three-dimensional tissues. One solution to supply a proper vascularization of larger tissues to provide oxygen and nutrients is the arteriovenous loop (AVL) model. However, for this model, suitable scaffold materials are needed that are biocompatible/non-immunogenic, slowly degradable, and allow vascularization. Here, we investigate the suitability of the known gelatin methacryloyl (GelMA)-based hydrogel for in-situ tissue engineering utilizing the AVL model. Rat AVLs are embedded by two layers of GelMA hydrogel in an inert PTFE chamber and implanted in the groin. Constructs were explanted after 2 or 4 weeks and analyzed. For this purpose, gross morphological, histological, and multiphoton microscopic analysis were performed. Immune response was analyzed based on anti-CD68 and anti-CD163 staining of immune cells. The occurrence of matrix degradation was assayed by anti-MMP3 staining. Vascularization was analyzed by anti-alpha-smooth muscle actin staining, multiphoton microscopy, as well as expression analysis of 53 angiogenesis-related proteins utilizing a proteome profiler angiogenesis array kit. Here we show that GelMA hydrogels are stable for at least 4 weeks in the rat AVL model. Furthermore, our data indicate that GelMA hydrogels are biocompatible. Finally, we provide evidence that GelMA hydrogels in the AVL model allow connective tissue formation, as well as vascularization, introducing multiphoton microscopy as a new methodology to visualize neovessel formation originating from the AVL. GelMA is a suitable material for in situ and in vivo TE in the AVL model.
CRIS-Team WoS Importer:2021-09-17

Genetic linkage of pfmdr1 with food vacuolar solute import in Plasmodium falciparum. - Rohrbach, Petra; Sanchez, Cecilia P; Hayton, Karen; Friedrich, Oliver; Patel, Jigar; Singh Sidhu, Amar Bir; Ferdig, Michael T; Fidock, David A; Lanzer, Michael (EMBO Journal, 2006)
The P-glycoprotein homolog of the human malaria parasite Plasmodium falciparum (Pgh-1) has been implicated in decreased susceptibility to several antimalarial drugs, including quinine, mefloquine and artemisinin. Pgh-1 mainly resides within the parasite's food vacuolar membrane. Here, we describe a surrogate assay for Pgh-1 function based on the subcellular distribution of Fluo-4 acetoxymethylester and its free fluorochrome. We identified two distinct Fluo-4 staining phenotypes: preferential staining of the food vacuole versus a more diffuse staining of the entire parasite. Genetic, positional cloning and pharmacological data causatively link the food vacuolar Fluo-4 phenotype to those Pgh-1 variants that are associated with altered drug responses. On the basis of our data, we propose that Pgh-1 imports solutes, including certain antimalarial drugs, into the parasite's food vacuole. The implications of our findings for drug resistance mechanisms and testing are discussed.

Growing old too early: Skeletal muscle single fiber biomechanics in ageing r349p desmin knock-in mice using the myorobot technology - Pollmann, Charlotte; Haug, Michael; Reischl, Barbara; Prölß, Gerhard; Pöschel, Thorsten; Rupitsch, Stefan; Clemen, Christoph S.; Schröder, Rolf; Friedrich, Oliver (International Journal of Molecular Sciences, 2020)
Muscle biomechanics relies on active motor protein assembly and passive strain transmission through cytoskeletal structures. The desmin filament network aligns myofibrils at the z-discs, provides nuclear–sarcolemmal anchorage and may also serve as memory for muscle repositioning following large strains. Our previous analyses of R349P desmin knock-in mice, an animal model for the human R350P desminopathy, already depicted pre-clinical changes in myofibrillar arrangement and increased fiber bundle stiffness. As the effect of R349P desmin on axial biomechanics in fully differentiated single muscle fibers is unknown, we used our MyoRobot to compare passive visco-elasticity and active contractile biomechanics in single fibers from fast-and slow-twitch muscles from adult to senile mice, hetero-or homozygous for the R349P desmin mutation with wild type littermates. We demonstrate that R349P desmin presence predominantly increased axial stiffness in both muscle types with a pre-aged phenotype over wild type fibers. Axial viscosity and Ca2+-mediated force were largely unaffected. Mutant single fibers showed tendencies towards faster unloaded shortening over wild type fibers. Effects of aging seen in the wild type appeared earlier in the mutant desmin fibers. Our single-fiber experiments, free of extracellular matrix, suggest that compromised muscle biomechanics is not exclusively attributed to fibrosis but also originates from an impaired intermediate filament network.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Biomechatronics; Desminopathy; R349P desmin; Single fibers; Skeletal muscle

Guided Multispectral Optoacoustic Tomography for 3D Imaging of the Murine Colon - Knieling, Ferdinand; Brown, Emma L.; Eckstein, Markus; Thoma, Oana-Maria; Wachter, Felix; Mandelbaum, Henriette; Ludwig, Petra; Claßen, Merle; Oraiopoulou, Mariam Eleni; Rother, Ulrich; Neurath, Markus; Wölfle, Joachim; et al. (Advanced Science, 2025)
Multispectral optoacoustic tomography is a promising medical imaging modality that combines light and sound to provide molecular imaging information at depths of several centimeters, based on the optical absorption of endogenous chromophores, such as hemoglobin. Assessment of inflammatory bowel disease has emerged as a promising clinical application of optoacoustic tomography. In this context, preclinical studies in animal models are essential to identify novel disease-specific imaging biomarkers and understand findings from emerging clinical pilot studies, however to-date, these studies have been limited by the precise identification of the bowel wall. Herein, a transrectal-absorber guide is applied, serving as a high-contrast landmark for 3D optoacoustic tomography of the colon. This study shows that guided multispectral optoacoustic tomography is able to measure changes in blood oxygenation status over the course of acute, chemically-induced colitis in mice and correlates with standard disease activity scores. This novel approach depicts intestinal hemoglobin composition non-invasively during murine inflammation. These results underscore the potential for optoacoustic imaging in translational inflammatory bowel disease research.
CRIS-Team Scopus Importer:2025-01-31
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; multispectral optoacoustic tomography; murine acute colitis; optoacoustic imaging; photoacoustic imaging

High-content method for mechanosignaling studies using IsoStretcher technology and quantitative Ca2+ imaging applied to Piezo1 in cardiac HL-1 cells - Merten, Anna-Lena; Schöler, Ulrike; Guo, Yang; Linsenmeier, Fabian; Martinac, Boris; Friedrich, Oliver; Schürmann, Sebastian (Cellular and Molecular Life Sciences, 2024)
The importance of mechanosensory transduction pathways in cellular signalling has prominently come to focus in the last decade with the discovery of the Piezo ion channel family. Mechanosignaling involving Piezo1 ion channels in the function of the heart and cardiovascular system has only recently been identified to have implications for cardiovascular physiology and pathophysiology, in particular for heart failure (i.e., hypertrophy or dilative cardiomyopathy). These results have emphasized the need for higher throughput methods to study single-cell cardiovascular mechanobiology with the aim of identifying new targets for therapeutic interventions and stimulating the development of new pharmacological agents. Here, we present a novel method to assess mechanosignaling in adherent cardiac cells (murine HL-1 cell line) using a combination of isotropic cell stretch application and simultaneous Ca2+ fluorescence readout with quantitative analysis. The procedure implements our IsoStretcher technology in conjunction with a single-cell- and population-based analysis of Ca2+ signalling by means of automated image registration, cell segmentation and analysis, followed by automated classification of single-cell responses. The method is particularly valuable for assessing the heterogeneity of populations with distinct cellular responses to mechanical stimulation and provides more user-independent unbiased drug response classifications.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Cardiomyocytes; Cell stretching; GsMTx4; Mechanobiology; Mechanosensitive; Mechanotransduction; Yoda1

Highly potent artemisinin-derived dimers and trimers: Synthesis and evaluation of their antimalarial, antileukemia and antiviral activities. - Reiter, Christoph; Fröhlich, Tony; Gruber, Lisa; Hutterer, Corina; Marschall, Manfred; Voigtländer, Cornelia; Friedrich, Oliver; Kappes, Bärbel; Efferth, Thomas; Tsogoeva, Svetlana (Bioorganic & medicinal chemistry, 2015)
New pharmaceutically active compounds can be obtained by modification of existing drugs to access more effective agents in the wake of drug resistance amongst others. To achieve this goal the concept of hybridization was established during the last decade. We employed this concept by coupling two artemisinin-derived precursors to obtain dimers or trimers with increased in vitro activity against Plasmodiumfalciparum 3D7 strain, leukemia cells (CCRF-CEM and multidrug-resistant subline CEM/ADR5000) and human cytomegalovirus (HCMV). Dimer 4 (IC50 of 2.6nM) possess superior antimalarial activity compared with its parent compound artesunic acid(3) (IC50 of 9.0nM). Dimer5 and trimers6 and 7 display superior potency against both leukemia cell lines (IC50 up to 0.002μM for CCRF-CEM and IC50 up to 0.20μM for CEM/ADR5000) and are even more active than clinically used doxorubicin (IC50 1.61μM for CEM/ADR5000). With respect to anti-HCMV activity, trimer6 is the most efficient hybrid (IC50 0.04μM) outperforming ganciclovir (IC50 2.6μM), dihydroartemisinin(IC50 >10μM) and artesunic acid (IC50 3.8μM).
Keywords: Artemisinin-derived hybrids; Artemisinin-derived dimers; Artemisinin-derived trimers; Antimalarial activity; Anticancer activity; Antiviral activity

High-Strength Fiber-Reinforced Composite Hydrogel Scaffolds as Biosynthetic Tendon Graft Material - No, Young Jung; Tarafder, Solaiman; Reischl, Barbara; Ramaswamy, Yogambha; Dunstan, Colin R.; Friedrich, Oliver; Lee, Chang Hun; Zreiqat, Hala (ACS Biomaterials Science and Engineering, 2020)
The development of suitable synthetic scaffolds for use as human tendon grafts to repair tendon ruptures remains a significant engineering challenge. Previous synthetic tendon grafts have demonstrated suboptimal tissue ingrowth and synovitis due to wear particles from fiber-to-fiber abrasion. In this study, we present a novel fiber-reinforced hydrogel (FRH) that mimics the hierarchical structure of the native human tendon for synthetic tendon graft material. Ultrahigh molecular weight polyethylene (UHMWPE) fibers were impregnated with either biosynthetic polyvinyl alcohol/gelatin hydrogel (FRH-PG) or with polyvinyl alcohol/gelatin + strontium-hardystonite (Sr-Ca2ZnSi2O7, Sr-HT) composite hydrogel (FRH-PGS). The scaffolds were fabricated and assessed to evaluate their suitability for tendon graft applications. The microstructure of both FRH-PG and FRH-PGS showed successful impregnation of the hydrogel component, and the tendon scaffolds exhibited equilibrium water content of similar to 70 wt %, similar to the values reported for native human tendon, compared to similar to 50 wt % water content retained in unmodified UHMWPE fibers. The tensile strength of FRH-PG and FRH-PGS (77.0-81.8 MPa) matched the range of human Achilles' tendon tensile strengths reported in the literature. In vitro culture of rat tendon stem cells showed cell and tissue infiltration into both FRH-PG and FRH-PGS after 2 weeks, and the presence of Sr-HT ceramic particles influenced the expression of tenogenic markers. On the other hand, FRH-PG supported the proliferation of murine C2C12 myoblasts, whereas FRH-PGS seemingly did not support it under static culture conditions. In vivo implantation of FRH-PG and FRH-PGS scaffolds into full-thickness rat patellar tendon defects showed good collagenous tissue ingrowth into these scaffolds after 6 weeks. This study demonstrates the potential viability for our FRH-PG and FRH-PGS scaffolds to be used for off-the-shelf biosynthetic tendon graft material.
CRIS-Team WoS Importer:2020-05-05

Hilfsmittel und Verfahren für zellbasiertes high content imaging - Gilbert, Daniel; Friedrich, Oliver; Lesko, Christian; Hartmann, Kristin (BioSpektrum, 2021)
Cell-based high content imaging has become a versatile and powerful method for studying e. g. cellular viability, morphology or physiology. However, high content imaging and its various applications require complex as well as expensive hardware and consumables, limiting its utility and usability. To broaden the applicability of cell-based high content imaging, we have developed tools and assaying techniques being exemplary portrayed in this article.
CRIS-Team Scopus Importer:2021-04-02

Hybrid integration of scalable mechanical and magnetophoretic focusing for magnetic flow cytometry - Reisbeck, Mathias; Richter, Lukas; Helou, Michael Johannes; Arlinghaus, Stephan; Anton, Birgit; van Dommelen, Ignas; Nitzsche, Mario; Bassler, Michael; Kappes, Bärbel; Friedrich, Oliver; Hayden, Oliver (Biosensors and Bioelectronics, 2018)
Time-of-flight (TOF) magnetic sensing of rolling immunomagnetically-labeled cells offers great potential for single cell function analysis at the bedside in even optically opaque media, such as whole blood. However, due to the spatial resolution of the sensor and the low flow rate regime required to observe the behavior of rolling cells, the concentration range of such a workflow is limited. Potential clinical applications, such as testing of leukocyte function, require a cytometer which can cover a cell concentration range of several orders of magnitude. This is a challenging task for an integrated dilution-free workflow, as for high cell concentrations coincidences need to be avoided, while for low cell concentrations sufficient statistics should be provided in a reasonable time-to-result. Here, we extend the spatial bandwidth of a magnetoresistive sensor with an adaptive and integratable workflow concept combining mechanical and magnetophoretic guiding of magnetically labeled targets for in-situ enrichment over a dynamic concentration range of 3 orders of magnitude. We achieve hybrid integration of the enrichment strategy in a cartridge mold and a giant-magnetoresistance (GMR) sensor in a functionalized Quad Flat No-Lead (QFN) package, which allows for miniaturization of the Si footprint for potential low-cost bedside testing. The enrichment results demonstrate that TOF magnetic flow cytometry with adaptive particle focusing can match the clinical requirements for a point-of-care (POC) cytometer and can potentially be of interest for other sheath-less methodologies requiring workflow integration.
Keywords: Giant magnetoresistance; Sensor integration; Point-of-care; Flow cytometry; Magnetophoresis

Hydroxyethyl starch solution for extracorporeal tissue perfusion - Taeger, Christian; Friedrich, Oliver; Drechsler, Caroline; Weigand, Annika; Hobe, Frieder; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Buchholz, Rainer; Horch, Raymund E.; Präbst, Konstantin; Buchholz, Rainer (Clinical hemorheology and microcirculation, 2016)
In the field of free flap transfer in reconstructive surgery, the trans- or replanted tissue always undergoes cell damage during ischemia to a more or less strong extent. In previous studies we already showed that conserving muscle transplants by means of extracorporeal perfusion over a period of 6 hours by using a crystalloid solution for perfusion. However, we observed significant edema formation. In this study we aimed at reducing the edema formation by using an iso-oncotic colloid as perfusion solution. This way we want to evaluate a possible new application of hydroxyl-ethyl starch in an extracorporeal setup to exploit potential benefits of the colloid.Examined parameters include the muscles' functionality with external field stimulation, histological examination and edema formation. Perfused muscles showed a statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. Substituting the electrolyte perfusion solution with a colloidal one shows the tendency to reduce the edema formation but without statistical significance.

IL-1α reversibly inhibits skeletal muscle ryanodine receptor a novel mechanism for critical illness myopathy? - Edwards, Joshua N.; Weber, Cornelia; Liu, Ilon; Reischl, Barbara; Most, Patrick; Wirth-Hücking, Anette; Yi, Bing; Friedrich, Oliver; Voelkers, Mirko; Buttgereit, Andreas; Lang, Roland; Lee, Aven; et al. (American journal of respiratory cell and molecular biology, 2014)
Critical illness myopathies in patients with sepsis or sustained mechanical ventilation prolong intensive care treatment and threaten both patients and health budgets; no specific therapy is available. Underlying pathophysiological mechanisms are still patchy. We characterized IL-1α action on muscle performance in "skinned" muscle fibers using force transducers and confocal Ca fluorescence microscopy for force/Ca transients and Ca sparks. Association of IL-1α with sarcoplasmic reticulum (SR) release channel, ryanodine receptor (RyR) 1, was investigated with coimmunoprecipitation and confocal immunofluorescence colocalization. Membrane integrity was studied in single, intact fibers challenged with IL-1α. IL-1α reversibly stabilized Mg inhibition of Ca release. Low Mg-induced force and Ca transients were reversibly abolished by IL-1a. At normal Mg , IL-1α reversibly increased caffeine-induced force and Ca transients. IL-1α reduced SR Ca leak via RyR1, as judged by (1) increased SR Ca retention, (2) increased IL-1α force transients being reproduced by 25 μM tetracaine, and (3) reduced Ca spark frequencies by IL-1a or tetracaine. Coimmunoprecipitation confirmed RyR1/IL-1 association. RyR1/IL-1 immunofluorescence patterns perfectly colocalized. Long-term, 8-hour IL-1α challenge of intact muscle fibers compromised membrane integrity in approximately 50% of fibers, and confirmed intracellular IL-1α deposition. IL-1α exerts a novel, specific, and reversible interaction mechanism with the skeletal muscle RyR1 macromolecular release complex without the need to act via its membrane IL-1 receptor, as IL-1R membrane expression levels were not detectable in Western blots or immunostaining of single fibers. We present a potential explanation of how the inflammatory mediator, IL-1α, may contribute to muscle weakness in critical illness. Copyright © 2014 by the American Thoracic Society.
Keywords: Critical illness myopathy; Cytokines; IL-1; Ryanodine receptor 1

Impact of prolonged sepsis on neural and muscular components of muscle contractions in a mouse model - Goossens, Chloe; Weckx, Ruben; Derde, Sarah; Van Helleputte, Lawrence; Schneidereit, Dominik; Haug, Michael; Reischl, Barbara; Friedrich, Oliver; Van Den Bosch, Ludo; Van Den Berghe, Greet; Langouche, Lies (Journal of Cachexia, Sarcopenia and Muscle, 2021)
Background Prolonged critically ill patients frequently develop debilitating muscle weakness that can affect both peripheral nerves and skeletal muscle. In-depth knowledge on the temporal contribution of neural and muscular components to muscle weakness is currently incomplete.
CRIS-Team WoS Importer:2021-01-29

Improved stability of polyclonal antibodies: A case study with lyophilization-conserved antibodies raised against epitopes from the malaria parasite Plasmodium falciparum - Simon, Nina; Sperber, Christine; Voigtländer, Cornelia; Born, Julia; Gilbert, Daniel; Seyferth, Stefan; Lee, Geoffrey; Kappes, Bärbel; Friedrich, Oliver (European Journal of Pharmaceutical Sciences, 2020)
Antibodies can be produced as polyclonal (pAb) or monoclonal (mAb) liquid formulations with limited shelf-life. For pAbs, unlike mAbs, only little is known about excipients and lyophilization affecting antibody stability upon reconstitution. We used a model pAb directed against Plasmodium falciparum (Pf) pyridoxal 5′-phosphate synthase 2 (Pdx2) to systemically study effects of bulking agents (amino acids, phosphate buffers, salt solutions), sugar(alcohols), surfactants and protein additions (bovine serum albumin, BSA) in liquid pAb formulations (isolated or in combinations) on the activity to detect the antigen in Pf extracts by Western blots. Repeated freeze-thaw cycles (20x) and extended room temperature storage markedly compromised pAb stability, the former being ameliorated by addition of cryoprotectants (glycerol, sucrose). Lyophilization of pure liquid pAb formulation markedly decreased antibody reactivity upon reconstitution which was not preserved by most bulking agents tested (e.g., histidine, arginine, acetate). Among the tested salt solutions (NaCl, Ringer, PBS), phosphate buffered saline had the largest lyoprotective potential, alongside sucrose, but not trehalose or maltitol. Among combinations of excipients, PBS, sucrose, low concentration BSA and Tween potently preserved PfPdx2 stability. Results for PBS were transferable to PfEnolase pAb, indicating that some of the formulations investigated here might be a low-cost solution for more general applicability to pAbs.
CRIS-Team Scopus Importer:2019-11-15

Improving alginate printability for biofabrication: establishment of a universal and homogeneous pre-crosslinking technique - Hazur, Jonas; Detsch, Rainer; Karakaya, Emine; Kaschta, Joachim; Teßmar, Jörg; Schneidereit, Dominik; Friedrich, Oliver; Schubert, Dirk W.; Boccaccini, Aldo R. (Biofabrication, 2020)
Many different biofabrication approaches as well as a variety of bioinks have been developed by researchers working in the field of tissue engineering. A main challenge for bioinks often remains the difficulty to achieve shape fidelity after printing. In order to overcome this issue, a homogeneous pre-crosslinking technique, which is universally applicable to all alginate-based materials, was developed. In this study, the Young's Modulus after post-crosslinking of selected hydrogels, as well as the chemical characterization of alginate in terms of M/G ratio and molecular weight, were determined. With our technique it was possible to markedly enhance the printability of a 2% (w/v) alginate solution, without using a higher polymer content, fillers or support structures. 3D porous scaffolds with a height of around 5 mm were printed. Furthermore, the rheological behavior of different pre-crosslinking degrees was studied. Shear forces on cells as well as the flow profile of the bioink inside the printing nozzle during the process were estimated. A high cell viability of printed NIH/3T3 cells embedded in the novel bioink of more than 85% over a time period of two weeks could be observed.
CRIS-Team Scopus Importer:2020-07-24
Keywords: alginate; bioink; bioprinting; pre-crosslinking; printability; rheology; shape fidelity

Influence of passive mechanical properties in healthy and infarcted rat myocardium on the cardiac cycle - Martonová, Denisa; Alkassar, Muhannad; Seufert, Julia; Holz, David; Duong, Minh Tuan; Reischl, Barbara; Friedrich, Oliver; Leyendecker, Sigrid (Proc. Appl. Math. Mech. (PAMM), 2021)

Inhibiting Interleukin 36 Receptor Signaling Reduces Fibrosis in Mice with Chronic Intestinal Inflammation - Scheibe, Kristina; Kersten, Christina; Schmied, Anabel; Vieth, Michael; Primbs, Tatjana; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Claussen, Jing; Klimowicz, Alexander C.; Zheng, Jie; Baum, Patrick; Meyer, Sebastian; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Intestinal fibrosis is a long-term complication in inflammatory bowel diseases (IBD) frequently resulting in functional damage, bowel obstruction, and surgery. Interleukin 36 (IL36) is a group of cytokines in the IL1 family with inflammatory effects. We studied expression of IL36 and its receptor, interleukin 1 receptor like 2 (IL1RL2 or IL36R) in development of intestinal fibrosis in human tissues and mice. METHODS: We obtained intestinal tissues from 92 patients with Crohn´s disease (CD), 48 patients with ulcerative colitis (UC), and 26 patients without inflammatory bowel diseases (controls). Tissues were analyzed by histology to detect fibrosis and immunohistochemistry to determine the distribution of fibroblasts and levels of IL36R ligands. Human and mouse fibroblasts were incubated with IL36 or control medium, and transcriptome-wide RNA sequences were analyzed. Mice were given neutralizing antibodies against IL36R and we studied intestinal tissues from Il1rl2-/- mice; colitis and fibrosis was induced in mice by repetitive administration of DSS or TNBS. Bone marrow cells were transplanted from Il1rl2-/- to irradiated wild-type mice and intestinal tissues were analyzed. Antibodies against IL36R were applied to mice with established chronic colitis and fibrosis and intestinal tissues were studied. RESULTS: Mucosal and submucosal tissues from patients with CD or UC had higher levels of collagens including type VI collagen compared to tissues from controls. In tissues from patients with fibrostenotic CD, significantly higher levels of IL36A were noted, which correlated with high numbers of activated fibroblasts that expressed alpha smooth muscle actin. IL36R activation of mouse and human fibroblasts resulted in expression of genes that regulate fibrosis and tissue remodeling, as well as expression of collagen type VI. Il1rl2-/- mice and mice given injections of an antibody against IL36R developed less severe colitis and fibrosis following administration of DSS or TNBS, but bone marrow cells from Il1rl2-/- mice did not prevent induction of colitis and fibrosis. Injection of antibodies against IL36R significantly reduced established fibrosis in mice with chronic intestinal inflammation. CONCLUSION: We found higher levels of IL36A in fibrotic intestinal tissues from patients with IBD, compared with controls. IL36 induced expression of genes that regulate fibrogenesis in fibroblasts. Inhibition or knockout of the IL36R in mice reduces chronic colitis and intestinal fibrosis. Agents designed to block IL36R signaling could be developed for prevention and treatment of intestinal fibrosis in patients with IBD.
EVALuna2:35123

Inhibiting PGGT1B Disrupts Function of RHOA, Resulting in T-cell Expression of Integrin α4β7 and Development of Colitis in Mice - Lopez Posadas, Rocío; Fastancz, Petra; Martínez-Sánchez, Luz del Carmen; Panteleev-Ivlev, Julia; Thonn, Veronika; Kisseleva, Tatyana; Becker, Lukas S.; Schulz-Kuhnt, Anja; Zundler, Sebastian; Wirtz, Stefan; Atreya, Raja; Carlé, Birgitta-Elisabeth; et al. (Gastroenterology, 2019)
Background & Aims: It is not clear how regulation of T-cell function is altered during development of inflammatory bowel diseases (IBD). We studied the mechanisms by which geranylgeranyltransferase-mediated prenylation controls T-cell localization to the intestine and chronic inflammation. Methods: We generated mice with T-cell–specific disruption of the geranylgeranyltransferase type I, beta subunit gene (Pggt1b), called Pggt1bΔCD4 mice, or the ras homolog family member A gene (Rhoa), called RhoaΔCD4 mice. We also studied mice with knockout of CDC42 or RAC1 and wild-type mice (controls). Intestinal tissues were analyzed by histology, multiphoton and confocal microscopy, and real-time polymerase chain reaction. Activation of CDC42, RAC1, and RHOA were measured with G-LISA, cell fractionation, and immunoblots. T cells and lamina propria mononuclear cells from mice were analyzed by flow cytometry or transferred to Rag1–/– mice. Mice were given injections of antibodies against integrin alpha4beta7 or gavaged with the RORC antagonist GSK805. We obtained peripheral blood and intestinal tissue samples from patients with and without IBD and analyzed them by flow cytometry. Results: Pggt1bΔCD4 mice developed spontaneous colitis, characterized by thickening of the intestinal wall, edema, fibrosis, accumulation of T cells in the colon, and increased expression of inflammatory cytokines. Compared with control CD4+ T cells, PGGT1B-deficient CD4+ T cells expressed significantly higher levels of integrin alpha4beta7, which regulates their localization to the intestine. Inflammation induced by transfer of PGGT1B-deficient CD4+ T cells to Rag1–/– mice was blocked by injection of an antibody against integrin alpha4beta7. Lamina propria of Pggt1bΔCD4 mice had increased numbers of CD4+ T cells that expressed RORC and higher levels of cytokines produced by T-helper 17 cells (granulocyte-macrophage colony-stimulating factor, interleukin [IL]17A, IL17F, IL22, and tumor necrosis factor [TNF]). The RORC inverse agonist GSK805, but not antibodies against IL17A or IL17F, prevented colitis in Pggt1bΔCD4 mice. PGGT1B-deficient CD4+ T cells had decreased activation of RHOA. RhoAΔCD4 mice had a similar phenotype to Pggt1bΔCD4 mice, including development of colitis, increased numbers of CD4+ T cells in colon, increased expression of integrin alpha4beta7 by CD4+ T cells, and increased levels of IL17A and other inflammatory cytokines in lamina propria. T cells isolated from intestinal tissues from patients with IBD had significantly lower levels of PGGT1B than tissues from individuals without IBD. Conclusion: Loss of PGGT1B from T cells in mice impairs RHOA function, increasing CD4+ T-cell expression of integrin alpha4beta7 and localization to colon, resulting in increased expression of inflammatory cytokines and colitis. T cells isolated from gut tissues from patients with IBD have lower levels of PGGT1B than tissues from patients without IBD.
CRIS-Team Scopus Importer:2019-10-08
Keywords: IBD; Immune Regulation; Mouse Models; Prenylation

Inhibitory control over Ca(2+) sparks via mechanosensitive channels is disrupted in dystrophin deficient muscle but restored by mini-dystrophin expression. - Teichmann, Martin D. H.; von Wegner, Frederic; Fink, Rainer; Chamberlain, Jeffrey S.; Launikonis, Bradley S.; Martinac, Boris; Friedrich, Oliver (PLoS ONE, 2008)
BACKGROUND In dystrophic skeletal muscle, osmotic stimuli somehow relieve inhibitory control of dihydropyridine receptors (DHPR) on spontaneous sarcoplasmic reticulum elementary Ca(2+) release events (ECRE) in high Ca(2+) external environments. Such 'uncontrolled' Ca(2+) sparks were suggested to act as dystrophic signals. They may be related to mechanosensitive pathways but the mechanisms are elusive. Also, it is not known whether truncated dystrophins can correct the dystrophic disinhibition. METHODOLOGY/PRINCIPAL FINDINGS We recorded ECRE activity in single intact fibers from adult wt, mdx and mini-dystrophin expressing mice (MinD) under resting isotonic conditions and following hyper-/hypo-osmolar external shock using confocal microscopy and imaging techniques. Isotonic ECRE frequencies were small in wt and MinD fibers, but were markedly increased in mdx fibers. Osmotic challenge dramatically increased ECRE activity in mdx fibers. Sustained osmotic challenge induced marked exponential ECRE activity adaptation that was three times faster in mdx compared to wt and MinD fibers. Rising external Ca(2+) concentrations amplified osmotic ECRE responses. The eliminated ECRE suppression in intact osmotically stressed mdx fibers was completely and reversibly resuscitated by streptomycine (200 microM), spider peptide GsMTx-4 (5 microM) and Gd(3+) (20 microM) that block unspecific, specific cationic and Ca(2+) selective mechanosensitive channels (MsC), respectively. ECRE morphology was not substantially altered by membrane stress. During hyperosmotic challenge, membrane potentials were polarised and a putative depolarisation through aberrant MsC negligible excluding direct activation of ECRE through tubular depolarisation. CONCLUSIONS/SIGNIFICANCE Dystrophin suppresses spontaneous ECRE activity by control of mechanosensitive pathways which are suggested to interact with the inhibitory DHPR loop to the ryanodine receptor. MsC-related disinhibition prevails in dystrophic muscle and can be resuscitated by transgenic mini-dystrophin expression. Our results have important implications for the pathophysiology of DMD where abnormal MsC in dystrophic muscle confer disruption of microdomain Ca(2+) homeostasis. MsC blockers should have considerable therapeutic potential if more muscle specific compounds can be found.

In mammalian skeletal muscle, phosphorylation of TOMM22 by protein kinase CSNK2/CK2 controls mitophagy - Kravic, Bojana; Harbauer, Angelika B.; Romanello, Vanina; Simeone, Luca; Vögtle, F. Nora; Kaiser, Tobias; Straubinger, Marion; Huraskin, Danyil; Böttcher, Martin; Cerqua, Cristina; Martin, Eva Denise; Poveda-Huertes, Daniel; et al. (Autophagy, 2017)
In yeast, Tom22 the central component of the TOMM (translocase of outer mitochondrial membrane) receptor complex is responsible for the recognition and translocation of synthesized mitochondrial precursor proteins, and its protein kinase CK2-dependent phosphorylation is mandatory for TOMM complex biogenesis and proper mitochondrial protein import. In mammals, the biological function of protein kinase CSNK2/CK2 remains vastly elusive and it is unknown whether CSNK2-dependent phosphorylation of TOMM protein subunits has a similar role as that in yeast. To address this issue, we used a skeletal muscle-specific Csnk2b/Ck2?-conditional knockout (cKO) mouse model. Phenotypically, these skeletal muscle Csnk2b cKO mice showed reduced muscle strength and abnormal metabolic activity of mainly oxidative muscle fibers, which point towards mitochondrial dysfunction. Enzymatically, active muscle lysates from skeletal muscle Csnk2b cKO mice phosphorylate murine TOMM22, the mammalian ortholog of yeast Tom22, to a lower extent than lysates prepared from controls. Mechanistically, CSNK2-mediated phosphorylation of TOMM22 changes its binding affinity for mitochondrial precursor proteins. However, in contrast to yeast, mitochondrial protein import seems not to be affected in vitro using mitochondria isolated from muscles of skeletal muscle Csnk2b cKO mice. PINK1, a mitochondrial health sensor that undergoes constitutive import under physiological conditions, accumulates within skeletal muscle Csnk2b cKO fibers and labels abnormal mitochondria for removal by mitophagy as demonstrated by the appearance of mitochondria-containing autophagosomes through electron microscopy. Mitophagy can be normalized by either introduction of a phosphomimetic TOMM22 mutant in cultured myotubes, or by in vivo electroporation of phosphomimetic Tomm22 into muscles of mice. Importantly, transfection of the phosphomimetic Tomm22 mutant in muscle cells with ablated Csnk2b restored their oxygen consumption rate comparable to wild-type levels. In sum, our data show that mammalian CSNK2-dependent phosphorylation of TOMM22 is a critical switch for mitophagy and reveal CSNK2-dependent physiological implications on metabolism, muscle integrity and behavior.
EVALuna2:25775

'In situ' high pressure confocal Ca2+-fluorescence microscopy in skeletal muscle: A new method to study pressure limits in mammalian cells - Friedrich, Oliver; von Wegner, Frederic; Hartmann, M.; Frey, Benjamin; Sommer, Karl; Ludwig, Horst; Fink, Rainer (Undersea & Hyperbaric Medicine, 2006)
We combined 'in situ' high pressure microscopy with confocal laser scanning microscopy to directly study Ca2+ homeostasis in intact mammalian (murine) skeletal muscle fibres during high pressure exposure up to 35 MPa. Cytosolic Fluo-4 and mitochondrial Rhod-2 Ca2+ fluorescence were simultaneously monitored. To separate changes in Ca2+ and direct/indirect effects of pressure on the dye, experiments in permeabilized ('skinned') muscle fibres were performed at a fixed Ca2+ concentration. Normalized Fluo-4 fluorescence sharply declined up to 10 MPa but showed a plateau between 10 MPa and -35 MPa. In the intact fibre, Fluo-4 fluorescence exponentially decreased during pressurization to 35 MPa with a pressure constant of pi-5 MPa whereas mitochondrial Rhod-2 fluorescence exponentially increased with a four-fold larger pi. Holding the pressure at 35 MPa almost did not change Fluo-4 fluorescence. However, Rhod-2 fluorescence started to decrease after -40 min. Upon decompression, Rhod-2 and Fluo-4 fluorescence increased exponentially with similar pi. However, initial Fluo-4 fluorescence values were not restored. Our results are in agreement with pressure induced Ca2+ leakage from the sarcoplasmic reticulum. Ca2+ might then be taken up in large amounts by mitochondria preventing cytosolic increase in Ca2+. Prolonged pressure applications (-40 min at 35 MPa) seem to destabilize mitochondrial function with release of Ca2+ from mitochondria back into the cytosol and eventually mechanical activation resulting in irreversible contractures. The pressure induced disturbance of Ca2+ homeostasis might have important implications for the pressure exposure limits and/or dive profiles of deep sea mammal

In vitro cell stretching technology (IsoStretcher) as an approach to unravel Piezo1-mediated cardiac mechanotransduction - Guo, Yang; Merten, Anna-Lena; Schöler, Ulrike; Yu, Ze Yan; Cvetkovska, Jasmina; Fatkin, Diane; Feneley, Michael P.; Martinac, Boris; Friedrich, Oliver (Progress in Biophysics & Molecular Biology, 2021)
The transformation of electrical signals into mechanical action of the heart underlying blood circulation results in mechanical stimuli during active contraction or passive filling distention, which conversely modulate electrical signals. This feedback mechanism is known as cardiac mechano-electric coupling (MEC). The cardiac MEC involves complex activation of mechanical biosensors initiating short-term and long-term effects through Ca2+ signals in cardiomyocytes in acute and chronic pressure overload scenarios (e.g. cardiac hypertrophy). Although it is largely still unknown how mechanical forces alter cardiac function at the molecular level, mechanosensitive channels, including the recently discovered family of Piezo channels, have been thought to play a major role in the cardiac MEC and are also suspected to contribute to development of cardiac hypertrophy and heart failure. The earliest reports of mechanosensitive channel activity recognized that their gating could be controlled by membrane stretch. In this article, we provide an overview of the stretch devices, which have been employed for studies of the effects of mechanical stimuli on muscle and heart cells. We also describe novel experiments examining the activity of Piezo1 channels under multiaxial stretch applied using polydimethylsiloxane (PDMS) stretch chambers and IsoStretcher technology to achieve isotropic stretching stimulation to cultured HL-1 cardiac muscle cells which express an appreciable amount of Piezo1.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Cell stretching device; HL-1; Mechanosensitive ion channel; Mechanotransduction; Piezo1; Polydimethylsiloxane (PDMS)

In Vivo Assessment of Deep Vascular Patterns in Murine Colitis Using Optoacoustic Mesoscopic Imaging - Bühler, Adrian; Brown, Emma L.; Nedoschill, Emmanuel; Eckstein, Markus; Ludwig, Petra; Wachter, Felix; Mandelbaum, Henriette; Raming, Roman; Oraiopoulou, Mariam Eleni; Paulus, Lars-Philip; Rother, Ulrich; Friedrich, Oliver; et al. (Advanced Science, 2024)
The analysis of vascular morphology and functionality enables the assessment of disease activity and therapeutic effects in various pathologies. Raster-scanning optoacoustic mesoscopy (RSOM) is an imaging modality that enables the visualization of superficial vascular networks in vivo. In murine models of colitis, deep vascular networks in the colon wall can be visualized by transrectal absorber guide raster-scanning optoacoustic mesoscopy (TAG-RSOM). In order to accelerate the implementation of this technology in translational studies of inflammatory bowel disease, an image-processing pipeline for TAG-RSOM data has been developed. Using optoacoustic data from a murine model of chemically-induced colitis, different image segmentation methods are compared for visualization and quantification of deep vascular patterns in terms of vascular network length and complexity, blood volume, and vessel diameter. The presented image-processing pipeline for TAG-RSOM enables label-free in vivo assessment of changes in the vascular network in murine colitis with broad applications for inflammatory bowel disease research.
CRIS-Team Scopus Importer:2024-11-01
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; murine acute colitis; optoacoustic imaging; photoacoustic imaging; raster-scanning optoacoustic mesoscopy; vessel morphology analysis

Ketamine stereoselectively inhibits spontaneous Ca2+-oscillations in cultured hippocampal neurons. - Sinner, Barbara; Friedrich, Oliver; Zink, Wolfgang; Martin, Eike O.; Fink, Rainer; Graf, Bernhard M. (Anesthesia and Analgesia, 2005)
Spontaneous Ca2+-oscillations are a result of periodic increases and decreases of cytosolic Ca2+. In neurons, they are thought to possess integrative properties because amplitude and frequency influence axon outgrowth, neuronal growth cone migration, and long distant wiring within the developing cortex. Ketamine stereoisomers differ in their affinities for the N-methyl-D-aspartic acid receptor and analgesic and anesthetic effects. Using a dual-excitation Ca2+ ratiometric fluorescence technique with the Ca2+-sensitive dye fura-2 AM, we detected spontaneous Ca2+-oscillations in neurons of hippocampal cell cultures. Spontaneous Ca2+-oscillations development is dependent on external Ca2+, and their amplitude and frequency increased in Mg2+-free solution. Ca2+-oscillations are glutamate dependent because blocking of the N-methyl-D-aspartic acid, alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic, or kainate receptor resulted in a complete disruption of the oscillations. The ketamine stereoisomers dose-dependently and reversibly suppressed the amplitude and frequency of the spontaneous Ca2+-oscillations. This effect was highly stereoselective with the S+ isomer being nearly four times more potent than the R(-) enantiomer. These results correlate well with the clinical anesthetic and analgesic potency of the stereoisomers and therefore our experimental approach might represent a model system to study mechanisms of anesthetic action on Ca2+-dependent integration of neuronal information.

Label-free analysis of experimental lung fibrosis using multiphoton microscopy and Raman spectroscopy - Ganzleben, Ingo; Kreiß, Lucas; Mühlberg, Alexander; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (EUROPEAN RESPIRATORY JOURNAL, 2021)
CRIS-Team WoS Importer:2022-02-25

Label-free analysis of inflammatory tissue remodeling in murine lung tissue based on multiphoton microscopy, Raman spectroscopy and machine learning - Kreiß, Lucas; Ganzleben, Ingo; Mühlberg, Alexander; Ritter, Paul; Schneidereit, Dominik; Becker, Christoph; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; Waldner, Maximilian (Journal of Biophotonics, 2022)
Inflammatory fibrotic tissue remodeling can lead to severe morbidity. Histopathology grading requires extraction of biopsies and elaborate tissue processing. Label-free optical technologies can provide diagnostic readout without preparation and artificial stainings and show potential for in vivo applications. Here, we present an integration of Raman spectroscopy (RS) and multiphoton microscopy for joint investigation of the bio-chemical composition and morphological features related to cellular components and connective tissue. Both modalities show that collagen signatures were significantly increased in a murine fibrosis model. Furthermore, autofluorescence signatures assigned to immune cells show high correlation with disease severity. RS indicates increased levels of elastin and lipids. Further, we investigated the effect of joint data sets on prediction performance in machine learning models. Although binary classification did not benefit from adding more features, multi-class classification was improved by integrated data sets.
CRIS-Team WoS Importer:2022-07-08

Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

Label-free, high-throughput detection of P-falciparum infection in sphered erythrocytes with digital holographic microscopy - Ugele, Matthias; Weniger, Markus; Leidenberger, Maria; Huang, Yiwei; Bassler, Michael; Friedrich, Oliver; Kappes, Bärbel; Hayden, Oliver; Richter, Lukas (Lab on A Chip, 2018)
Effective malaria treatment requires rapid and accurate diagnosis of infecting species and actual parasitemia. Despite the recent success of rapid tests, the analysis of thick and thin blood smears remains the gold standard for routine malaria diagnosis in endemic areas. For non-endemic regions, sample preparation and analysis of blood smears are an issue due to low microscopy expertise and few cases of imported malaria. Automation of microscopy results could be beneficial to quickly confirm suspected infections in such conditions. Here, we present a label-free, high-throughput method for early malaria detection with the potential to reduce inter-observer variation by reducing sample preparation and analysis effort. We used differential digital holographic microscopy in combination with two-dimensional hydrodynamic focusing for the label-free detection of P. falciparum infection in sphered erythrocytes, with a parasitemia detection limit of 0.01%. Moreover, the achieved differentiation of P. falciparum ring-, trophozoite- and schizont life cycle stages in synchronized cultures demonstrates the potential for future discrimination of even malaria species.

Label-Free High-Throughput Leukemia Detection by Holographic Microscopy - Ugele, Matthias; Weniger, Markus; Stanzel, Manfred; Bassler, Michael; Krause, Stefan; Friedrich, Oliver; Hayden, Oliver; Richter, Lukas (Advanced Science, 2018)
Complete blood count and differentiation of leukocytes (DIFF) belong to the most frequently performed laboratory diagnostic tests. Here, a flow cytometry-based method for label-free DIFF of untouched leukocytes by digital holographic microscopy on the rich phase contrast of peripheral leukocyte images, using highly controlled 2D hydrodynamic focusing conditions is reported. Principal component analysis of morphological characteristics of the reconstructed images allows classification of nine leukocyte types, in addition to different types of leukemia and demonstrates disappearance of acute myeloid leukemia cells in remission. To exclude confounding effects, the classification strategy is tested by the analysis of 20 blinded clinical samples. Here, 70% of the specimens are correctly classified with further 20% classifications close to a correct diagnosis. Taken together, the findings indicate a broad clinical applicability of the cytometry method for automated and reagent-free diagnosis of hematological disorders.
EVALuna2:35096

Label-free imaging of inflammatory bowel disease using multiphoton microscopy. - Schürmann, Sebastian; Försch, Sebastian; Atreya, Raja; Neumann, Helmut; Friedrich, Oliver; Neurath, Markus; Waldner, Maximilian (Gastroenterology, 2013)
Multiphoton microscopy (MPM) became one of the most important optical in vivo imaging techniques for basic research during recent years. In comparison with single photon excitation during confocal microscopy, MPM provides a superior effective resolution in thick tissue samples and an increased penetration depth.1 Because of the effects of nonlinear optics, various molecular components can be discriminated with MPM in vivo and in vitro without the need to apply fluorophores. The detection of these molecules is based on specific autofluorescence or second harmonic generation (SHG) signals generated by multiphoton excitation.

Label-Free In Vivo Histopathology of Experimental Colitis via 3-Channel Multiphoton Endomicroscopy - Kreiß, Lucas; Thoma, Oana Maria; Dilipkumar, Ashwathama; Carlé, Birgitta-Elisabeth; Longequeue, Pascal; Kunert, Timo; Rath, Timo; Hildner, Kai; Neufert, Clemens; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; et al. (Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Label-Free Multiphoton Endomicroscopy for Minimally Invasive In Vivo Imaging - Dilipkumar, Ashwathama; Al-Shemmary, Alaa; Kreiß, Lucas; Cvecek, Kristian; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Menezes, Jean Gonzales; Thoma, Oana-Maria; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; Friedrich, Oliver; et al. (Advanced Science, 2019)
Multiphoton microscopy of cellular autofluorescence and second harmonic generation from collagen facilitates imaging of living cells and tissues without the need for additional fluorescent labels. Here, a compact multiphoton endomicroscope for label-free in vivo imaging in small animals via side-viewing needle objectives is presented. Minimal invasive imaging at cellular resolution is performed in colonoscopy of mice without surgical measures and without fluorescent dyes as a contrast agent. The colon mucosa is imaged repeatedly in the same animal in a mouse model of acute intestinal inflammation to study the process of inflammation at the tissue level within a time period of ten days, demonstrating the capabilities of label-free endomicroscopy for longitudinal studies for the first time.
CRIS-Team Scopus Importer:2019-05-02
Keywords: endoscopy; inflammatory bowel disease; multiphoton microscopy; optical imaging

Levosimendan’s Effects on Length-Dependent Activation in Murine Fast-Twitch Skeletal Muscle - Haug, Michael; Michael, Mena; Ritter, Paul; Kovbasyuk, Larisa; Vazakidou, Maria Eleni; Friedrich, Oliver (International Journal of Molecular Sciences, 2024)
Levosimendan’s calcium sensitizing effects in heart muscle cells are well established; yet, its potential impact on skeletal muscle cells has not been evidently determined. Despite controversial results, levosimendan is still expected to interact with skeletal muscle through off-target sites (further than troponin C). Adding to this debate, we investigated levosimendan’s acute impact on fast-twitch skeletal muscle biomechanics in a length-dependent activation study by submersing single muscle fibres in a levosimendan-supplemented solution. We employed our MyoRobot technology to investigate the calcium sensitivity of skinned single muscle fibres alongside their stress–strain response in the presence or absence of levosimendan (100 µM). While control data are in agreement with the theory of length-dependent activation, levosimendan appears to shift the onset of the ‘descending limb’ of active force generation to longer sarcomere lengths without notably improving myofibrillar calcium sensitivity. Passive stretches in the presence of levosimendan yielded over twice the amount of enlarged restoration stress and Young’s modulus in comparison to control single fibres. Both effects have not been described before and may point towards potential off-target sites of levosimendan.
CRIS-Team Scopus Importer:2024-06-21
Keywords: calcium sensitivity; levosimendan; MyoRobot; single muscle fibre; stress–strain

Long-term NMDA receptor inhibition affects NMDA receptor expression and alters glutamatergic activity in developing rat hippocampal neurons. - Sinner, Barbara; Friedrich, Oliver; Lindner, Regina; Bundscherer, Anika; Graf, Bernhard (Toxicology, 2015)
Ketamine and its stereoisomer S(+)-ketamine are widely used for sedation in pediatric anesthesia and intensive care medicine. Numerous experimental studies indicate that ketamine is potentially toxic to the developing brain. Here, we examined the long-term effects of NMDA receptor blockade on NMDA receptor subunit expression, alterations in neuronal Ca(2+)-oscillations and apoptosis. Hippocampal neurons, 15 days in culture, were exposed to either S(+)-ketamine or the NMDA receptor blocker MK801 for 24h. Cytosolic Ca(2+)-concentration was determined by fluorescence microscopy and the expression of the NMDA subunits NR1, NR2A and 2B was assessed by qRT-PCR, whereas Western blots and activated Caspase-3 served to measure the extent of apoptosis. Long-term incubation with MK801 or higher doses of S(+)-ketamine resulted in a dose-dependent decreased ability of MK801 to reduce amplitude and frequency of the Ca(2+)-oscillations 15min following washout of the drug. This was accompanied by an increase in NR1 mRNA but not the NR2A and B subunit expression at the same time point. 24h following washout of the specific drug, a significant elevation of the pro-apoptotic marker BAX, as well as activated Caspase-3 positive neurons, could be detected in cultures exposed to 100μM MK801 and 25μM S(+)-ketamine. Here, we show that long-term blockade of the NMDA receptor in developing rat hippocampal neurons significantly increased NR1 subunit expression, and that this was associated with an alteration in neuronal activity. Apoptosis was only induced 24h after withdrawal of long-term blockade for high doses of S(+)-ketamine.
Keywords: Anesthetics; Developing brain; Ca2+-oscillations

L-type Ca2+ channel function is linked to dystrophin expression in mammalian muscle. - Friedrich, Oliver; von Wegner, Frederic; Chamberlain, Jeffrey S.; Fink, Rainer; Rohrbach, Petra (PLoS ONE, 2008)
BACKGROUND In dystrophic mdx skeletal muscle, aberrant Ca2+ homeostasis and fibre degeneration are found. The absence of dystrophin in models of Duchenne muscular dystrophy (DMD) has been connected to altered ion channel properties e.g. impaired L-type Ca2+ currents. In regenerating mdx muscle, 'revertant' fibres restore dystrophin expression. Their functionality involving DHPR-Ca2+-channels is elusive. METHODS AND RESULTS We developed a novel 'in-situ' confocal immuno-fluorescence and imaging technique that allows, for the first time, quantitative subcellular dystrophin-DHPR colocalization in individual, non-fixed, muscle fibres. Tubular DHPR signals alternated with second harmonic generation signals originating from myosin. Dystrophin-DHPR colocalization was substantial in wt fibres, but diminished in most mdx fibres. Mini-dystrophin (MinD) expressing fibres successfully restored colocalization. Interestingly, in some aged mdx fibres, colocalization was similar to wt fibres. Most mdx fibres showed very weak membrane dystrophin staining and were classified 'mdx-like'. Some mdx fibres, however, had strong 'wt-like' dystrophin signals and were identified as 'revertants'. Split mdx fibres were mostly 'mdx-like' and are not generally 'revertants'. Correlations between membrane dystrophin and DHPR colocalization suggest a restored putative link in 'revertants'. Using the two-micro-electrode-voltage clamp technique, Ca2+-current amplitudes (i(max)) showed very similar behaviours: reduced amplitudes in most aged mdx fibres (as seen exclusively in young mdx mice) and a few mdx fibres, most likely 'revertants', with amplitudes similar to wt or MinD fibres. Ca2+ current activation curves were similar in 'wt-like' and 'mdx-like' aged mdx fibres and are not the cause for the differences in current amplitudes. i(max) amplitudes were fully restored in MinD fibres. CONCLUSIONS We present evidence for a direct/indirect DHPR-dystrophin interaction present in wt, MinD and 'revertant' mdx fibres but absent in remaining mdx fibres. Our imaging technique reliably detects single isolated 'revertant' fibres that could be used for subsequent physiological experiments to study mechanisms and therapy concepts in DMD.

Magnetic fingerprints of rolling cells for quantitative flow cytometry in whole blood. - Reisbeck, Mathias; Helou, Michael Johannes; Richter, Lukas; Kappes, Bärbel; Friedrich, Oliver; Hayden, Oliver (Scientific Reports, 2016)
Over the past 50 years, flow cytometry has had a profound impact on preclinical and clinical applications requiring single cell function information for counting, sub-typing and quantification of epitope expression. At the same time, the workflow complexity and high costs of such optical systems still limit flow cytometry applications to specialized laboratories. Here, we present a quantitative magnetic flow cytometer that incorporates in situ magnetophoretic cell focusing for highly accurate and reproducible rolling of the cellular targets over giant magnetoresistance sensing elements. Time-of-flight analysis is used to unveil quantitative single cell information contained in its magnetic fingerprint. Furthermore, we used erythrocytes as a biological model to validate our methodology with respect to precise analysis of the hydrodynamic cell diameter, quantification of binding capacity of immunomagnetic labels, and discrimination of cell morphology. The extracted time-of-flight information should enable point-of-care quantitative flow cytometry in whole blood for clinical applications, such as immunology and primary hemostasis.

Magnetic Tissue Engineering of the Vocal Fold Using Superparamagnetic Iron Oxide Nanoparticles - Poettler, Marina; Fliedner, Anna; Bergmann, Julia; Bui, Linh Katrin; Mühlberger, Marina; Braun, Christian; Graw, Matthias; Janko, Christina; Friedrich, Oliver; Alexiou, Christoph; Lyer, Stefan (Tissue Engineering: Parts A, B, and C, 2019)
Losing one's ability to speak, because of tissue deficiency at the vocal fold (VF), leads to serious impairment in the quality of life. Until now, there is no successful approach for regenerating the VF. The aim of this study was to show the advantage of magnetic nanoparticles in the generation of scaffold-free three-dimensional (3D) VF cell constructs by magnetic tissue engineering (MTE). Rabbit VF fibroblasts were used to establish MTE: after cellular uptake of superparamagnetic iron oxide nanoparticles (SPIONs), cells can be controlled with a magnetic field thereby forming solid 3D cell structures. To transfer this method into human cells, SPIONs were adapted accordingly and tested for their influence on human VF (hVF) cells and for their ability to perform MTE with hVF cells. Of interest, the cell number and the magnet's shape influence the form of the rabbit VF cell construct. After successful characterization of hVF cells, biocompatibility analyses revealed no significant influence of SPIONs on them, thus 3D hVF cell constructs could be successfully generated by MTE. These basic results are important to develop MTE as an innovative method to regenerate functional VFs. We expect that in vivo studies, including MTE as an elegant, far-field controlled and touchless technology, will translate MTE VF bioconstructs into reconstructive laryngeal medicine. Impact Statement This study aims at nanotechnology for regenerative medicine by magnetic tissue engineering (MTE). New approaches for vocal fold (VF) reconstruction are desperately needed. Superparamagnetic iron oxide nanoparticles offer innovative, scaffold-free potentials for tissue engineering: MTE. By using MTE we could generate functional multilayered human VF cell constructs, which can consequently be used to regenerate the voice in patients with VF injuries.
CRIS-Team WoS Importer:2019-05-14

Measuring average rheological quantities of cell monolayers in the linear viscoelastic regime - Dakhil, Haider; Gilbert, Daniel; Malhotra, Deepika; Limmer, Anja; Engelhardt, Hannes; Amtmann, Anette; Hansmann, Jan; Hübner, Holger; Buchholz, Rainer; Friedrich, Oliver; Wierschem, Andreas (Rheologica Acta, 2016)
During the last decades, the rheology of cells has been studied almost entirely in single cells. While cell-to-cell variation is typically very large and most studies were carried out in the nonlinear viscoelastic regime, we quantify average linear viscoelastic cell properties like storage and loss moduli and normal stress in monolayers of different cell types showing that murine 3T6 fibroblasts, human fibroblasts, and HeLa cells differ considerably in their storage modulus. To this end, we modified a commercial rheometer to set up a parallel-disk configuration at gap widths of a few micrometers and optically detected the cell concentration in the gap. This enables studying the linear viscoelastic behavior of the cells and permits quantifying the impact of drugs affecting the cytoskeleton or the extracellular matrix connection. Thus, due to its high-content approach, without the need of treating the samples in the rheometer, this envisions the use of this method as a fast diagnostic tool. The method also allows for quantitatively studying of the impact of pre-stress on the storage and loss moduli of the cells.
Keywords: Cell rheology; Linear viscoelasticity; Narrow-gap rheometry; Parallel-disk configuration; Cell monolayer; Biochemical treatment; Pre-stress; Primary cells; Cell lines

MechAnalyze: An Algorithm for Standardization and Automation of Compression Test Analysis - Kahl, Melanie; Schneidereit, Dominik; Bock, Nathalie; Friedrich, Oliver; Hutmacher, Dietmar W.; Meinert, Christoph (Tissue Engineering - Part C: Methods, 2021)
The mechanical properties of hydrogels, as well as native and engineered tissues are key parameters frequently assessed in biomaterial science and tissue engineering research. However, a lack of standardized methods and user-independent data analysis has impacted the research community for many decades and contributes to poor reproducibility and comparability of datasets, representing a significant issue often neglected in publications. In this study, we provide a software package, MechAnalyze, facilitating the standardized and automated analysis of force-displacement data generated in unconfined compression tests. Using comparative studies of datasets analyzed manually and with MechAnalyze, we demonstrate that the software reliably determines the compressive moduli, failure stress and failure strain of hydrogels, as well as engineered and native tissues, while providing an intuitive user interface that requires minimal user input. MechAnalyze provides a fast and user-independent data analysis method and advances process standardization, reproducibility, and comparability of data for the mechanical characterization of biomaterials as well as native and engineered tissues. Mechanical properties of hydrogels are crucial parameters in the development of new materials for tissue engineering. However, manual assessment is tedious, not standardized and suffers under user-to-user bias. Hence, the here presented stand-alone software package provides analysis and statistics of force-displacement and material geometry data to determine the compressive moduli, failure stress, and failure strain in a standardized, robust, and automated fashion. MechAnalyze will substantially support biomechanical testing of hydrogels as well as engineered and native tissues and will thus, be of appreciable value to a broad target group in regenerative medicine, tissue engineering, but also life sciences and biomedicine.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Compression test; Hydrogel; Mechanical characterization; Reproducibility

Mechanical properties of cell- and microgel bead-laden oxidized alginate-gelatin hydrogels - Distler, Thomas; Kretzschmar, Lena; Schneidereit, Dominik; Girardo, Salvatore; Goswami, Ruchi; Friedrich, Oliver; Detsch, Rainer; Guck, Jochen; Boccaccini, Aldo R.; Budday, Silvia (Biomaterials Science, 2021)
3D-printing technologies, such as biofabrication, capitalize on the homogeneous distribution and growth of cells inside biomaterial hydrogels, ultimately aiming to allow for cell differentiation, matrix remodeling, and functional tissue analogues. However, commonly, only the mechanical properties of the bioinks or matrix materials are assessed, while the detailed influence of cells on the resulting mechanical properties of hydro- gels remains insufficiently understood. Here, we investigate the properties of hydrogels containing cells and spherical PAAm microgel beads through multi-modal complex mechanical analyses in the small- and large- strain regimes. We evaluate the individual contributions of different filler concentrations and a non-fibrous oxi- dized alginate-gelatin hydrogel matrix on the overall mechanical behavior in compression, tension, and shear. Through material modeling, we quantify parameters that describe the highly nonlinear mechanical response of soft composite materials. Our results show that the stiffness significantly drops for cell- and bead concen- trations exceeding four million per milliliter hydrogel. In addition, hydrogels with high cell concentrations (≥6 mio ml−1) show more pronounced material nonlinearity for larger strains and faster stress relaxation. Our findings highlight cell concentration as a crucial parameter influencing the final hydrogel mechanics, with implications for microgel bead drug carrier-laden hydrogels, biofabrication, and tissue engineering.

Mechano-regulation of the beating heart at the cellular level - Mechanosensitive channels in normal and diseased heart - Friedrich, Oliver; Wagner, Sören; Battle, Andrew; Schürmann, Sebastian; Martinac, Boris (Progress in Biophysics & Molecular Biology, 2012)
The heart as a contractile hollow organ finely tunes mechanical parameters such as stroke volume, stroke pressure and cardiac output according to filling volumes, filling pressures via intrinsic and neuronal routes. At the cellular level, cardiomyocytes in beating hearts are exposed to large mechanical stress during successive heart beats. Although the mechanisms of excitation-contraction coupling are well established in mammalian heart cells, the putative contribution of mechanosensitive channels to Ca homeostasis, Ca signaling and force generation has been primarily investigated in relation to heart disease states. For instance, transient receptor potential channels (TRPs) are up-regulated in animal models of congestive heart failure or hypertension models and seem to play a vital role in pathological Ca overload to cardiomyocytes, thus aggravating the pathology of disease at the cellular level. Apart from that, the contribution of mechanosensitive channels (MsC) in the normal beating heart to the downstream force activation cascade has not been addressed. We present an overview of the current literature and concepts of mechanosensitive channel involvement in failing hearts and cardiomyopathies and novel data showing a likely contribution of Ca influx via mechanosensitive channels in beating normal cardiomyocytes during systolic shortening. © 2012 Elsevier Ltd.
Keywords: Calcium homeostasis; Cardiomyocytes; Heartbeat; Mechanosensitive channel; Transient receptor potential channel

Membrane ion conductances of mammalian skeletal muscle in the post-decompression state after high-pressure treatment. - Friedrich, Oliver; Kress, Kai; Ludwig, Horst; et al. (Journal of Membrane Biology, 2002)
Exposure of excitable tissues to hyperbaric environments has been shown to alter membrane ion conductances, but only little is known about the state of the membranes of intact cells in the post-decompression phase following a prolonged high-pressure treatment. Furthermore, almost nothing is known about high-pressure effects on skeletal muscle membranes. Therefore, we investigated changes to the input resistances, membrane potentials and voltage-gated membrane currents for sodium (INa), potassium (IK) and calcium (ICa) ions under voltage-clamp conditions in enzymatically isolated intact mammalian single fibers following a 3-hr high-pressure treatment up to 25 MPa at +4 degrees C. After a 3-hr 20 MPa treatment, the input resistance was increased but declined again for treatments with higher pressures. The resting membrane potentials were depolarized in the post-decompression phase following a 20-MPa high-pressure treatment; this could be explained by an increase in the Na+- over K+-permeability ratio and in intracellular [Na+]i. Following a 10-MPa high-pressure treatment, INa, IK and ICa amplitudes were similar compared to controls but were significantly reduced by 25 to 35% after a 3-hr 20-MPa high-pressure treatment. Interestingly, the voltage-dependent inactivation of INa and ICa seemed to be more stable at high pressures compared to the activation parameters, as no significant changes were found up to a 20-MPa treatment. For higher pressure applications (e.g., 25 MPa), there seemed to be a marked loss of membrane integrity and INa, IK and ICa almost disappeared.

Methods in Molecular Biology, Cell Viability Assays, Methods and Protocols - Gilbert, Daniel; Friedrich, Oliver (Humana Press, 2017)
This volume provides an overview of commonly used methods and protocols for cell fitness indicators. Chapters detail biochemical, fluorescence and luminescence-based strategies, computational, and label-free methodologies for assaying cellular viability by means of e.g. viscoelastic properties, impedance and multiphoton microscopy. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory  protocols, and tips on troubleshooting and avoiding known pitfalls.
Keywords: Misestimation; enzyme; cell proliferation; phenotyping; cell imaging

Microarchitecture is severely compromised but motor protein function is preserved in dystrophic mdx skeletal muscle. - Friedrich, Oliver; Both, Martin; Weber, Cornelia; Schürmann, Sebastian; Teichmann, Martin D. H.; von Wegner, Frederic; Fink, Rainer; Vogel, M.; Chamberlain, Jeffrey S.; Garbe, Christoph S. (Biophysical Journal, 2010)
Progressive force loss in Duchenne muscular dystrophy is characterized by degeneration/regeneration cycles and fibrosis. Disease progression may involve structural remodeling of muscle tissue. An effect on molecular motorprotein function may also be possible. We used second harmonic generation imaging to reveal vastly altered subcellular sarcomere microarchitecture in intact single dystrophic mdx muscle cells (approximately 1 year old). Myofibril tilting, twisting, and local axis deviations explain at least up to 20% of force drop during unsynchronized contractile activation as judged from cosine angle sums of myofibril orientations within mdx fibers. In contrast, in vitro motility assays showed unaltered sliding velocities of single mdx fiber myosin extracts. Closer quantification of the microarchitecture revealed that dystrophic fibers had significantly more Y-shaped sarcomere irregularities ("verniers") than wild-type fibers (approximately 130/1000 microm(3) vs. approximately 36/1000 microm(3)). In transgenic mini-dystrophin-expressing fibers, ultrastructure was restored (approximately 38/1000 microm(3) counts). We suggest that in aged dystrophic toe muscle, progressive force loss is reflected by a vastly deranged micromorphology that prevents a coordinated and aligned contraction. Second harmonic generation imaging may soon be available in routine clinical diagnostics, and in this work we provide valuable imaging tools to track and quantify ultrastructural worsening in Duchenne muscular dystrophy, and to judge the beneficial effects of possible drug or gene therapies.

Microdomain Ca2+ dynamics in mammalian muscle following prolonged high pressure treatments - Schnee, Sarah; von Wegner, Frederic; Schürmann, Sebastian; Ludwig, Horst; Fink, Rainer; Friedrich, Oliver (Journal of Physics : Conference Series, 2008)
High pressure (HP) applications are an important thermodynamic tool to influence cellular processes. Especially processes that undergo large volume changes, e.g. opening or closing of ion channels, are in particular susceptible to HP treatments. Such volume changes are extremely difficult to assess for intracellular ion channels, like ryanodine receptors (RyR) residing in the membrane of organelles. In skeletal muscle, RyR act as Ca release channels. We previously showed that plasmalemmal Na and Ca ion channels were irreversibly altered after prolonged 20 MPa treatments. Here, changes in microdomain Ca levels due to elementary Ca release events (ECRE) were monitored using confocal fluorescence microscopy. We studied ECRE in mammalian skeletal muscle following 3 h HP treatments up to 30 MPa to clarify whether RyR induced intracellular microdomain Ca dynamics was more susceptible to HP treatment compared to surface membrane ion currents. ECRE frequencies exponentially declined with pressure. ECRE amplitudes and rise times (RT) were quite robust towards HP treatments. In contrast, spatial and temporal ECRE extension showed a tendency towards larger values up to 20 MPa but declined for higher pressures. Activation volumes for pressure-induced persistent ECRE alterations were zero for RT but showed a bimodal behavior for event duration. It seems that although ECRE frequencies are markedly reduced, ECRE morphology is less affected by HP. In particular, RyR opening time is practically unaltered and the observed morphological ECRE changes might reflect alterations in local Ca buffers and Ca concentration profiles rather than involvement of RyR in mammalian skeletal muscle. © 2008 IOP Publishing Ltd.

Mini-dystrophin restores L-type calcium currents in skeletal muscle of transgenic mdx mice. - Friedrich, Oliver; Both, Martin; Gillis, Jean-Marie; Chamberlain, Jeffrey S.; Fink, Rainer (The Journal of Physiology, 2004)
L-type calcium currents (iCa) were recorded using the two-microelectrode voltage-clamp technique in single short toe muscle fibres of three different mouse strains: (i) C57/SV129 wild-type mice (wt); (ii) mdx mice (an animal model for Duchenne muscular dystrophy; and (iii) transgenically engineered mini-dystrophin (MinD)-expressing mdx mice. The activation and inactivation properties of iCa were examined in 2- to 18-month-old animals. Ca2+ current densities at 0 mV in mdx fibres increased with age, but were always significantly smaller compared to age-matched wild-type fibres. Time-to-peak (TTP) of iCa was prolonged in mdx fibres compared to wt fibres. MinD fibres always showed similar TTP and current amplitudes compared to age-matched wt fibres. In all three genotypes, the voltage-dependent inactivation and deactivation of iCa were similar. Intracellular resting calcium concentration ([Ca2+]i) and the distribution of dihydropyridine binding sites were also not different in young animals of all three genotypes, whereas iCa was markedly reduced in mdx fibres. We conclude, that dystrophin influences L-type Ca2+ channels via a direct or indirect linkage which may be disrupted in mdx mice and may be crucial for proper excitation-contraction coupling initiating Ca2+ release from the sarcoplasmic reticulum. This linkage seems to be fully restored in the presence of mini-dystrophin.

Motor protein function in skeletal abdominal muscle of cachectic cancer patients. - Taskin, Sultan; Stumpf, Vera I.; Bachmann, Jeannine; Weber, Cornelia; Martignoni, Marc E.; Friedrich, Oliver (Journal of cellular and molecular medicine, 2014)
Cachexia presents with ongoing muscle wasting, altering quality of life in cancer patients. Cachexia is a limiting prognostic factor for patient survival and health care costs. Although animal models and human trials have shown mechanisms of motorprotein proteolysis, not much is known about intrinsic changes of muscle functionality in cancer patients suffering from muscle cachexia, and deeper insights into cachexia pathology in humans are needed. To address this question, rectus abdominis muscle samples were collected from several surgical control, non-cachectic and cachectic cancer patients and processed for skinned fibre biomechanics, molecular in vitro motility assays, myosin isoform protein compositions and quantitative ubiquitin polymer protein analysis. In pre-cachectic and cachectic cancer patient samples, maximum force was significantly compromised compared with controls, but showed an unexpected increase in myofibrillar Ca(2+) sensitivity consistent with a shift from slow to fast myosin isoform expression seen in SDS-PAGE analysis and in vitro motility assays. Force deficit was specific for 'cancer', but not linked to presence of cachexia. Interestingly, quantitative ubiquitin immunoassays revealed no major changes in static ubiquitin polymer protein profiles, whether cachexia was present or not and were shown to mirror profiles in control patients. Our study on muscle function in cachectic patients shows that abdominal wall skeletal muscle in cancer cachexia shows signs of weakness that can be partially attributed to intrinsic changes to contractile motorprotein function. On protein levels, static ubiquitin polymeric distributions were unaltered, pointing towards evenly up-regulated ubiquitin protein turnover with respect to ubiquitin conjugation, proteasome degradation and de-ubiquitination.
Keywords: muscle cachexia; cancer; contractility; myosin isoforms; motility assay

Motor protein function in skeletal muscle-a multiple scale approach to contractility. - von Wegner, Frederic; Schürmann, Sebastian; Fink, Rainer; Vogel, M.; Friedrich, Oliver (IEEE transactions on medical imaging, 2009)
We present an approach to skeletal muscle contractility and its regulation over different scales ranging from biomechanical studies in intact muscle fibers down to the motility and interaction of single motor protein molecules. At each scale, shortening velocities as a measure for weak cross-bridge cycling rates are extracted and compared. Experimental approaches include transmitted light microscopy, second harmonic generation imaging of contracting myofibrils, and fluorescence microscopy of single molecule motility. Each method yields image sequences that are analyzed with automated image processing algorithms to extract the contraction velocity. Using this approach, we show how to isolate the contribution of the motor proteins actin and myosin and their modulation by regulatory proteins from the concerted action of electro-mechanical activation on a more complex cellular scale. The advantage of this approach is that averaged contraction velocities can be determined on the different scales ranging from isolated motor proteins to sarcomere levels in myofibrils and myofibril arrays within the cellular architecture. Our results show that maximum shortening velocities during in situ electrical activation of sarcomere contraction in intact single muscle cells can substantially deviate from sliding velocities obtained in oriented in vitro motility assays of isolated motor proteins showing that biophysical contraction kinetics not simply translate linearly between contractility scales. To adequately resolve the very fast initial mechanical activation kinetics of shortening at each scale, it was necessary to implement high-speed imaging techniques. In the case of intact fibers and single molecule motility, we achieved a major increase in temporal resolution up to frame rates of 200-1000 fps using CMOS image sensor technology. The data we obtained at this unprecedented temporal resolution and the parameters extracted can be used to validate results obtained from computational models of motor protein interaction and skeletal muscle contractility in health and muscle disease. Our approach is feasible to explain the possible underlying mechanisms that contribute to different shortening velocities at different scales and complexities.
Keywords: biomechanics; biomedical optical imaging; cellular biophysics; high-speed optical techniques; molecular biophysics; muscle; optical microscopy; proteins

Multiphoton microscopy analysis of extracellular collagen I network formation by mesenchymal stem cells. - Vielreicher, Martin; Gellner, Monika; Rottensteiner, Ulrike; Horch, Raymund E.; Arkudas, Andreas; Friedrich, Oliver (Journal of Tissue Engineering and Regenerative Medicine, 2015)
Collagen I is the major fibrous extracellular component of bone responsible for its ultimate tensile strength. In tissue engineering, one of the most important challenges for tissue formation is to get cells interconnected via a strong and functional extracellular matrix (ECM), mimicking as closely as possible the natural ECM geometry. Still missing in tissue engineering are: (a) a versatile, high-resolution and non-invasive approach to evaluate and quantify different aspects of ECM development within engineered biomimetic scaffolds online; and (b) deeper insights into the mechanism whereby cellular matrix production is enhanced in 3D cell-scaffold composites, putatively via enhanced focal adhesion linkage, over the 2D setting. In this study, we developed sensitive morphometric detection methods for collagen I-producing and bone-forming mesenchymal stem cells (MSCs), based on multiphoton second harmonic generation (SHG) microscopy, and used those techniques to compare collagen I production capabilities in 2D- and 3D-arranged cells. We found that stimulating cells with 1% serum in the presence of ascorbic acid is superior to other medium conditions tested, including classical osteogenic medium. In contrast to conventional 2D culture, having MSCs packed closely in a 3D environment presumably stimulates cells to produce strong and complex collagen I networks with defined network structures (visible in SHG images) and improves collagen production. Copyright © 2015 John Wiley & Sons, Lt

Multiphoton Microscopy Reveals DAPK1‐Dependent Extracellular Matrix Remodeling in a Chorioallantoic Membrane (CAM) Model - Kunze, Philipp; Kreiß, Lucas; Novosadová, Vendula; Roehe, Adriana V.; Steinmann, Sara; Prochazka, Jan; Geppert, Carol-Immanuel; Hartmann, Arndt; Schürmann, Sebastian; Friedrich, Oliver; Schneider-Stock, Regine (Cancers, 2022)
Cancer cells facilitate tumor growth by creating favorable tumor micro‐environments (TME), altering homeostasis and immune response in the extracellular matrix (ECM) of surrounding tissue. A potential factor that contributes to TME generation and ECM remodeling is the cytoskeleton‐associated human death‐associated protein kinase 1 (DAPK1). Increased tumor cell motility and de‐adhesion (thus, promoting metastasis), as well as upregulated plasminogen-signaling, are shown when functionally analyzing the DAPK1 ko‐related proteome. However, the systematic investigation of how tumor cells actively modulate the ECM at the tissue level is experimentally challenging since animal models do not allow direct experimental access while artificial in vitro scaffolds cannot simulate the entire complexity of tissue systems. Here, we used the chorioallantoic membrane (CAM) assay as a natural, collagen‐rich tissue model in combination with all‐optical experimental access by multiphoton microscopy (MPM) to study the ECM remodeling potential of colorectal tumor cells with and without DAPK1 in situ and even in vivo. This approach demonstrates the suitability of the CAM assay in combination with multiphoton microscopy for studying collagen remodeling during tumor growth. Our results indicate the high ECM remodeling potential of DAPK1 ko tumor cells at the tissue level and support our findings from proteomics.
CRIS-Team Scopus Importer:2022-05-20
Keywords: collagen; colon cancer; ECM remodeling; MPM; uPAR

Multiresolution transform denoising and segmentation of single molecule motility image series - Friedrich, Oliver; von Wegner, Frederic; Ober, Tobias; Weber, Cornelia; Fink, Rainer; Vogel, Martin (Molecular Imaging, 2007)
We present a multiresolution transform-based method for the extraction of moving filament trajectories from single molecule motility data. Noise-corrupted fluorescence image series are denoised using the multiscale median transform and trajectories are detected in the denoised data set. The presented method reduces noise more efficiently than 2D-anisotropic diffusion and several wavelet based techniques. Fibre trajectories are extracted by segmentation of the denoised image stacks and non-crossing trajectories are unambiguously identified combining the information of 2D (XY) and 3D (XYT) segmentation. The algorithm is applied and evaluated using experimental data sets - image sequences of fluorescently labeled F-actin molecules and their 2D-trajectories on a myosin coated surface. This so-called 'motility assay' is used to analyse kinetics, biochemical regulation and pharmacological modulation of these biologically relevant molecules. The presented method improves signal-to-background discrimination, facilitates filament identification and finally, may contribute to significantly improve the performance of this assa
Keywords: Actin-myosin motility assay; Denoising; Multiresolution transform; Segmentation; Single molecule microscopy

Murine Metatarsus Bone and Joint Collagen-I Fiber Morphologies and Networks Studied With SHG Multiphoton Imaging - Vielreicher, Martin; Bozec, Aline; Schett, Georg; Friedrich, Oliver (Frontiers in Bioengineering and Biotechnology, 2021)
Chronic inflammatory disease of bones and joints (e.g., rheumatoid arthritis, gout, etc.), but also acute bone injury and healing, or degenerative resorptive processes inducing osteoporosis, are associated with structural remodeling that ultimately have impact on function. For instance, bone stability is predominantly orchestrated by the structural arrangement of extracellular matrix fibrillar networks, i.e., collagen-I, -IV, elastin, and other proteins. These components may undergo distinct network density and orientation alterations that may be causative for decreased toughness, resilience and load bearing capacity or even increased brittleness. Diagnostic approaches are usually confined to coarse imaging modalities of X-ray or computer tomography that only provide limited optical resolution and lack specificity to visualize the fibrillary collagen network. However, studying collagen structure at the microscopic scale is of considerable interest to understand the mechanisms of tissue pathologies. Multiphoton Second Harmonic Generation (SHG) microscopy, is able to visualize the sterical topology of the collagen-I fibrillar network in 3D, in a minimally invasive and label-free manner. Penetration depths exceed those of conventional visible light imaging and can be further optimized through employing decalcification or optical clearing processing ex vivo. The goal of this proof-of-concept study was to use SHG and two-photon excited fluorescence (2-PEF) imaging to mainly characterize the fibrillary collagen organization within ex vivo decalcified normal mouse metatarsus bone and joint. The results show that the technique resolved the fibrillar collagen network of complete bones and joints with almost no artifacts and enabled to study the complex collagen-I networks with various fiber types (straight, crimped) and network arrangements of mature and woven bone with high degree of detail. Our imaging approach enabled to identify cavities within both cortical and trabecular bone architecture as well as interfaces with sharply changing fiber morphology and network structure both within bone, in tendon and ligament and within joint areas. These possibilities are highly advantageous since the technology can easily be applied to animal models, e.g., of rheumatoid arthritis to study structural effects of chronic joint inflammation, and to many others and to compare to the structure of human bone.
CRIS-Team Scopus Importer:2021-07-09
Keywords: bone and joint diseases; bone microstructure; collagen fiber morphology; collagen-I fibrillar networks; multiphoton SHG microscopy; remodeling 3D Morphology

MyoBio: An automated bioreactor system technology for standardized perfusion-decellularization of whole skeletal muscle - Ritter, Paul; Cai, Aijia; Reischl, Barbara; Fiedler, Maren; Prölß, Gerhard; Frie, Benjamin; Kretzschmar, Elke; Michael, Mena; Hartmann, Kristin; Lesko, Christian; Salti, Hatiham; Arkudas, Andreas; et al. (IEEE transactions on bio-medical engineering, 2022)
Objective: Decellularizing solid organs is a promising top-down process to produce acellular bio-scaffolds for 'de novo' regrowth or application as tissue 'patches' that compensate, e.g., large volumetric muscle loss in reconstructive surgery. Therefore, generating standardized acellular muscle scaffolds marks a pressing area of need. Although animal muscle decellularization protocols were established, those are mostly manually performed and lack defined bioreactor environments and metrologies to assess decellularization quality in real-time. To close this gap, we engineered an automated bioreactor system to provide chemical decellularization solutions to immersed whole rat gastrocnemius medialis muscle through perfusion of the main feeding arteries. Results: Perfusion control is adjustable according to decellularization quality feedback. This was assessed both from (i) ex situ assessment of sarcomeres/nuclei through multiphoton fluorescence and label-free Second Harmonic Generation microscopy and DNA quantification, along with (ii) in situ assessment of the samples passive mechanical elasticity. Conclusion: We find DNA and sarcomere-free constructs after 72 h of 0.1% SDS perfusion-decellularization. Furthermore, passive elasticity can be implemented as additional online decellularization quality measure, noting a threefold elasticity decrease in acellular constructs. Significance: Our MyoBio represents a novel and useful automated bioreactor environment for standardized and controlled generation of acellular whole muscle scaffolds as a valuable source for regenerative medicine.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Biological systems; Biomechatronics; bioreactors; Biotechnology; decellularization; Inductors; Muscles; Plastics; skeletal muscle; Surgery; Tendons; tissue engineering

Myofibrillar Lattice Remodeling Is a Structural Cytoskeletal Predictor of Diaphragm Muscle Weakness in a Fibrotic mdx (mdx Cmah(-/-)) Model - Ritter, Paul; Nübler, Stefanie; Buttgereit, Andreas; Smith, Lucas R.; Mühlberg, Alexander; Bauer, Julian; Michael, Mena; Kreiß, Lucas; Haug, Michael; Barton, Elisabeth; Friedrich, Oliver (International Journal of Molecular Sciences, 2022)
Duchenne muscular dystrophy (DMD) is a degenerative genetic myopathy characterized by complete absence of dystrophin. Although the mdx mouse lacks dystrophin, its phenotype is milder compared to DMD patients. The incorporation of a null mutation in the Cmah gene led to a more DMD-like phenotype (i.e., more fibrosis). Although fibrosis is thought to be the major determinant of 'structural weakness', intracellular remodeling of myofibrillar geometry was shown to be a major cellular determinant thereof. To dissect the respective contribution to muscle weakness, we assessed biomechanics and extra- and intracellular architecture of whole muscle and single fibers from extensor digitorum longus (EDL) and diaphragm. Despite increased collagen contents in both muscles, passive stiffness in mdx Cmah(-/-) diaphragm was similar to wt mice (EDL muscles were twice as stiff). Isometric twitch and tetanic stresses were 50% reduced in mdx Cmah(-/-) diaphragm (15% in EDL). Myofibrillar architecture was severely compromised in mdx Cmah(-/-) single fibers of both muscle types, but more pronounced in diaphragm. Our results show that the mdx Cmah(-/-) genotype reproduces DMD-like fibrosis but is not associated with changes in passive visco-elastic muscle stiffness. Furthermore, detriments in active isometric force are compatible with the pronounced myofibrillar disarray of the dystrophic background.
CRIS-Team WoS Importer:2022-09-30

MyoRobot 2.0: An advanced biomechatronics platform for automated, environmentally controlled skeletal muscle single fiber biomechanics assessment employing inbuilt real-time optical imaging - Haug, Michael; Meyer, Charlotte; Reischl, Barbara; Prölß, Gerhard; Nübler, Stefanie; Schürmann, Sebastian; Schneidereit, Dominik; Heckel, Michael; Pöschel, Thorsten; Rupitsch, Stefan; Friedrich, Oliver (Biosensors and Bioelectronics, 2019)
We present an enhanced version of our previously engineered MyoRobot system for reliable, versatile and automated investigations of skeletal muscle or linear polymer material (bio)mechanics. That previous version already replaced strenuous manual protocols to characterize muscle biomechanics properties and offered automated data analysis. Here, the system was further improved for precise control over experimental temperature and muscle single fiber sarcomere length. Moreover, it also now features the calculation of fiber cross-sectional area via on-the-fly optical diameter measurements using custom-engineered microscope optics. With this optical systems integration, the MyoRobot 2.0 allows to tailor a wealth of recordings for relevant physiological parameters to be sequentially executed in living single myofibers. Research questions include assessing temperature-dependent performance of active or passive biomechanics, or automated control over length-tension or length-velocity relations. The automatically obtained passive stress-strain relationships and elasticity modules are important parameters in (bio)material science. From the plethora of possible applications, we validated the improved MyoRobot 2.0 by assessing temperature-dependent myofibrillar Ca 2+ sensitivity, passive axial compliance and Young's modulus. We report a Ca 2+ desensitization and a narrowed dynamic range at higher temperatures in murine M. extensor digitorum longus single fibers. In addition, an increased axial mechanical compliance in single muscle fibers with Young's moduli between 40 - 60 kPa was found, compatible with reported physiological ranges. These applications demonstrate the robustness of our MyoRobot 2.0 for facilitated single muscle fiber biomechanics assessment.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Axial compliance; Biomechatronics; Biosensor; Ca2+ sensitivity; EDL; MyoRobot; Sarcomere length; Single fiber; Skeletal muscle; Temperature control; Young's modulus

NA+- and K+-channels as molecular targets of the alkaloid ajmaline in skeletal muscle fibres. - Friedrich, Oliver; von Wegner, Frederic; Wink, Michael; Fink, Rainer (British Journal of Pharmacology, 2007)
BACKGROUND AND PURPOSE Ajmaline is a widely used antiarrhythmic drug. Its action on voltage-gated ion channels in skeletal muscle is not well documented and we have here elucidated its effects on Na(+) and K(+) channels. EXPERIMENTAL APPROACH Sodium (I(Na)) and potassium (I(K)) currents in amphibian skeletal muscle fibres were recorded using 'loose-patch' and two-microelectrode voltage clamp techniques (2-MVC). Action potentials were generated using current clamp. KEY RESULTS Under 'loose patch' clamp conditions, the IC(50) for I(Na) was 23.2 microM with Hill-coefficient h=1.21. For I(K), IC(50) was 9.2 microM, h=0.87. Clinically relevant ajmaline concentrations (1-3 microM) reduced peak I(Na) by approximately 5% but outward I(K) values were reduced by approximately 20%. Na(+) channel steady-state activation and fast inactivation were concentration-dependently shifted towards hyperpolarized potentials ( approximately 10 mV at 25 microM). Inactivation curves were markedly flattened by ajmaline. Peak-I(K) under maintained depolarisation was reduced to approximately 30% of control values by 100 microM ajmaline. I(K) activation time constants were increased at least two-fold. Lower concentrations (10 or 25 microM) reduced steady-state-I(K) slightly but peak-I(K) significantly. Action potential generation threshold was increased by 10 microM ajmaline and repolarisation prolonged. CONCLUSIONS AND IMPLICATIONS Ajmaline acts differentially on Na(+) and K(+) channels in skeletal muscle. This suggests at least multiple sites of action including the S4 subunit. Our data may provide a first insight into specific mechanisms of ajmaline-ion channel interaction in tissues other than cardiac muscle and could suggest possible side-effects that need to be further evaluated.
Keywords: skeletal muscle; ajmaline; loose-patch; sodium channel; potassium channel

Nano- and micro-patterned S-, H-, and X-PDMS for cell-based applications: Comparison of wettability, roughness, and cell-derived parameters - Scharin-Mehlmann, Marina; Häring, Aaron; Rommel, Mathias; Dirnecker, Tobias; Friedrich, Oliver; Frey, Lothar; Gilbert, Daniel (Frontiers in Bioengineering and Biotechnology, 2018)
Keywords: Cell morphology; Cell viability; AFM; Water contact angle measurement; Wettability; HFF-1 cells; Nano-micrometer-patterned PDMS

Natural NADH and FAD Autofluorescence as Label-Free Biomarkers for Discriminating Subtypes and Functional States of Immune Cells - Lemire, Sarah; Thoma, Oana-Maria; Kreiß, Lucas; Völkl, Simon; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (International Journal of Molecular Sciences, 2022)
Immune cell activity is a major factor for disease progression in inflammatory bowel diseases (IBD). Classifying the type and functional state of immune cells is therefore crucial in clinical diagnostics of IBD. Label-free optical technologies exploiting NADH and FAD autofluorescence, such as multiphoton microscopy, have been used to describe tissue morphology in healthy and inflamed colon samples. Nevertheless, a strategy for the identification of single immune cell subtypes within the tissue is yet to be developed. This work aims to initiate an understanding of autofluorescence changes depending on immune cell type and activation state. For this, NADH and FAD autofluorescence signals of different murine immune cell subtypes under native conditions, as well as upon in vitro stimulation and cell death, have been evaluated. Autofluorescence was assessed using flow cytometry and multiphoton microscopy. Our results reveal significantly increased NADH and FAD signals in innate immune cells compared to adaptive immune cells. This allowed identification of relative amounts of neutrophils and CD4+ T cells in mixed cell suspensions, by using NADH signals as a differentiation marker. Furthermore, in vitro stimulation significantly increased NADH and FAD autofluorescence in adaptive immune cells and macrophages. Cell death induced a significant drop in NADH autofluorescence, while FAD signals were hardly affected. Taken together, these results demonstrate the value of autofluorescence as a tool to characterize immune cells in different functional states, paving the way to the label-free clinical classification of IBD in the future.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Cell autofluorescence; FAD; Flow cytometry; Immune cells; Inflammatory bowel diseases; Multiphoton microscopy; NADH

New efficient artemisinin derived agents against human leukemia cells, human cytomegalovirus and Plasmodium falciparum: 2nd generation 1,2,4-trioxane-ferrocene hybrids. - Reiter, Christoph; Fröhlich, Tony; Zeino, Maen; Marschall, Manfred; Bahsi, Hanife; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Hampel, Frank; Efferth, Thomas; Tsogoeva, Svetlana (European journal of medicinal chemistry, 2015)
In our ongoing search for highly active hybrid molecules exceeding their parent compounds in anticancer, antimalaria as well as antiviral activity and being an alternative to the standard drugs, we present the synthesis and biological investigations of 2nd generation 1,2,4-trioxane-ferrocene hybrids. In vitro tests against the CCRF-CEM leukemia cell line revealed di-1,2,4-trioxane-ferrocene hybrid 7 as the most active compound (IC50 of 0.01 μM). Regarding the activity against the multidrug resistant subline CEM/ADR5000, 1,2,4-trioxane-ferrocene hybrid 5 showed a remarkable activity (IC50 of 0.53 μM). Contrary to the antimalaria activity of hybrids 4-8 against Plasmodium falciparum 3D7 strain with slightly higher IC50 values (between 7.2 and 30.2 nM) than that of their parent compound DHA, hybrids 5-7 possessed very promising activity (IC50 values lower than 0.5 μM) against human cytomegalovirus (HCMV). The application of 1,2,4-trioxane-ferrocene hybrids against HCMV is unprecedented and demonstrated here for the first time.
Keywords: Artemisinin; Ferrocene; Hybrid; Cancer; Malaria; Human cytomegalovirus

New factors contributing to dynamic calcium regulation in the skeletal muscle triad-a crowded place - Friedrich, Oliver; Fink, Rainer; von Wegner, Frederic (Biophysical Reviews, 2010)
Skeletal muscle is a highly organized tissue that has to be optimized for fast signalling events conveying electrical excitation to contractile response. The site of electro-chemico-mechanical coupling is the skeletal muscle triad where two membrane systems, the extracellular t-tubules and the intracellular sarcoplasmic reticulum, come into very close contact. Structure fits function here and the signalling proteins DHPR and RyR1 were the first to be discovered to bridge this gap in a conformational coupling arrangement. Since then, however, new proteins and more signalling cascades have been identified just in the last decade, adding more diversity and fine tuning to the regulation of excitation-contraction coupling (ECC) and control over Ca store content. The concept of Ca entry into working skeletal muscle has become attractive again with the experimental evidence summarized in this review. Store-operated Ca entry (SOCE), excitation-coupled Ca entry (ECCE), action-potential-activated Ca current (APACC), and retrograde EC-coupling (ECC) are new concepts additional to the conventional orthograde ECC; they have provided fascinating new insights into muscle physiology. In this review, we discuss the discovery of these pathways, their potential roles, and the signalling proteins involved that show that the triad may become a crowded place in time. © 2009 International Union for Pure and Applied Biophysics (IUPAB) and Springer.
Keywords: Action-potential-activated Ca2+ entry; Ca2+ sparks; DHPR; Excitation-coupled Ca2+ entry; Retrograde coupling; RyR; Skeletal muscle; Store-operated Ca2+ entry; T-system; Triad

New oleoyl hybrids of natural antioxidants: Synthesis and in vitro evaluation as inducers of apoptosis in colorectal cancer cells - Carullo, Gabriele; Mazzotta, Sarah; Koch, Anna Maria; Hartmann, Kristin; Friedrich, Oliver; Gilbert, Daniel; Vega-Holm, Margarita; Schneider-Stock, Regine; Aiello, Francesca (Antioxidants, 2020)
Nowadays, the beneficial role of a healthy lifestyle, particularly emphasizing the quality of foods and cancer management, is accepted worldwide. Polyphenols and oleic acid play a key role in this context, but are still scarcely used as anti-cancer agents due to their bio-accessibility limits. Therefore, we aimed to synthesize a set of new oleoyl-hybrids of quercetin, morin, pinocembrin, and catechin to overcome the low bioavailability of polyphenols, throughout a bio-catalytic approach using pancreatic porcine lipase as a catalyst. The in vitro assays, using a wide panel of human cancer cell lines showed, mainly for two novel regioisomer oleoyl-hybrids of quercetin, a remarkable increase in apoptotic cell populations. We suggested that the DNA damage shown as GH2AX signals might be the major cause of apoptotic cell death. Finally, we demonstrated convincing data about two novel polyphenol-based hybrids displaying a highly selective anti-cancer cytotoxicity and being superior compared to their reference/parental compounds.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Apoptosis; Colorectal cancer; Cytotoxicity; DNA damage; HCT-116; Oleic acid; Pancreatic porcine lipase; Polyphenol hybrids; Quercetin

Nichtinvasive Hochleistungstechnik zur Gewebeuntersuchung. Multiphotonen-Mikroskopie stellt Kollagen-I-Netzwerk in Knochen dar - Vielreicher, Martin; Friedrich, Oliver (Orthopädie & Rheuma, 2016)
Knochengewebe besteht zu überwiegenden Anteilen aus stabilisierenden, hochorganisiert angeordneten Kollagen-I-Netzwerken, Knochenzellen und an Kollagen angelagerte Hydroxylapatit-Kristalle. Trotz ihrer überragenden Bedeutung sind die Möglichkeiten der hochaufgelösten Darstellung der Kollagen-Faserbün-del im Wesentlichen auf REM-Aufnahmen begrenzt, welche die Integrität der Proben artifiziell verändern können. Die Multiphotonen-Mikroskopie bietet einen neuen, tiefenaufgelösten und nichtinvasiven – damit lebendes Gewebe nicht beeinträchtigenden – Ansatz zur Darstellung von Kollagen I und Zellen.<br

Numerical analysis of Ca2+ depletion in the transverse tubular system of mammalian muscle. - Friedrich, Oliver; Ehmer, Thomas; Uttenweiler, Dietmar; Vogel, Martin; Barry, Peter H; Fink, Rainer (Biophysical Journal, 2001)
Calcium currents were recorded in contracting and actively shortening mammalian muscle fibers. In order to characterize the influence of extracellular calcium concentration changes in the small unstirred lumina of the transverse tubular system (TTS) on the time course of the slow L-type calcium current (I(Ca)), we have combined experimental measurements of I(Ca) with quantitative numerical simulations of Ca2+ depletion. I(Ca) was recorded both in calcium-buffered and unbuffered external solutions using the two-microelectrode voltage clamp technique (2-MVC) on short murine toe muscle fibers. A simulation program based on a distributed TTS model was used to calculate the effect of ion depletion in the TTS. The experimental data obtained in a solution where ion depletion is suppressed by a high amount of a calcium buffering agent were used as input data for the simulation. The simulation output was then compared with experimental data from the same fiber obtained in unbuffered solution. Taking this approach, we could quantitatively show that the calculated Ca2+ depletion in the transverse tubular system of contracting mammalian muscle fibers significantly affects the time-dependent decline of Ca2+ currents. From our findings, we conclude that ion depletion in the tubular system may be one of the major effects for the I(Ca) decline measured in isotonic physiological solution under voltage clamp conditions.

One arm is enough, two might actually be worse–when dystrophic muscle cells grow old. - Friedrich, Oliver (Experimental physiology, 2010)

Optical prediction of single muscle fiber force production using a combined biomechatronics and second harmonic generation imaging approach - Schneidereit, Dominik; Nübler, Stefanie; Prölß, Gerhard; Reischl, Barbara; Schürmann, Sebastian; Müller, Oliver J.; Friedrich, Oliver (Light: Science & Applications, 2018)
Skeletal muscle is an archetypal organ whose structure is tuned to match function. The magnitude of order in muscle fibers and myofibrils containing motor protein polymers determines the directed force output of the summed force vectors and, therefore, the muscle’s power performance on the structural level. Structure and function can change dramatically during disease states involving chronic remodeling. Cellular remodeling of the cytoarchitecture has been pursued using noninvasive and label-free multiphoton second harmonic generation (SHG) microscopy. Hereby, structure parameters can be extracted as a measure of myofibrillar order and thus are suggestive of the force output that a remodeled structure can still achieve. However, to date, the parameters have only been an indirect measure, and a precise calibration of optical SHG assessment for an exerted force has been elusive as no technology in existence correlates these factors. We engineered a novel, automated, high-precision biomechatronics system into a multiphoton microscope allows simultaneous isometric Ca2+-graded force or passive viscoelasticity measurements and SHG recordings. Using this MechaMorph system, we studied force and SHG in single EDL muscle fibers from wt and mdx mice; the latter serves as a model for compromised force and abnormal myofibrillar structure. We present Ca2+-graded isometric force, pCa-force curves, passive viscoelastic parameters and 3D structure in the same fiber for the first time. Furthermore, we provide a direct calibration of isometric force to morphology, which allows noninvasive prediction of the force output of single fibers from only multiphoton images, suggesting a potential application in the diagnosis of myopathies.<br

Optimized Method of 3D Scaffold Seeding, Cell Cultivation, and Monitoring Cell Status for Bone Tissue Engineering - Krolinski, Adrian; Sommer, Kai Peter; Wiesner, Johanna; Friedrich, Oliver; Vielreicher, Martin (Cell Viability Assays (2nd Edt.), 2023)
The cultivation of cells in 3D systems is commonly regarded to be more physiological than in 2D as it comes much closer to the natural situation in tissues in many different aspects. However, 3D cell culture is much more complex. Cells within the pores of a printed 3D scaffold face a special situation concerning cell-material interaction and cell adhesion, cell proliferation, and supply of medium and oxygen into the core of the scaffolds. Biological assays (for cell proliferation, viability, and activity) have been validated primarily for 2D cell cultures and need to be adapted for 3D cultures. Likewise, in imaging, a number of points need to be taken into account in order to get a clear picture of the cells in 3D scaffolds, preferably with the method of multiphoton microscopy. Here, we describe a method for pretreatment and cell seeding of porous inorganic composite scaffolds (α-TCP/HA) for bone tissue engineering and for cultivation of the cell-scaffold constructs. The analytical methods described are the cell proliferation assay and the ALP activity assay. A step-by-step protocol is provided here that safely tackles typical difficulties that arise with this 3D cell-scaffold setting. In addition, MPM imaging of cells is described both with and without labeling. The combination of biochemical assays and imaging provides valuable insights into the possibilities of analysis with this 3D cell-scaffold system.
CRIS-Team Scopus Importer:2023-05-26
Keywords: 3D scaffolds; Cell adhesion; Cell proliferation; Cell seeding; Collagen-I formation; Multiphoton imaging; Osteogenic differentiation; Quantitative assays; Scaffold population; Second harmonic generation (SHG)

Optimizing neuronal differentiation of human pluripotent NT2 stem cells in monolayer cultures. - Abolpour Mofrad, Sepideh; Künzel, Katharina; Friedrich, Oliver; Gilbert, Daniel (Development, growth & differentiation, 2016)
Human pluripotent embryonal carcinoma (NT2) cells are increasingly considered as a suitable model for in vitro developmental toxicity and neurotoxicity (DT/DNT) studies as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and allow toxicity testing at different stages of maturation. However, differentiation of NT2 cells is not straightforward. There are different protocols available in the literature reporting varying results with regard to differentiation efficiency, expression of neuronal markers and morphological characteristics of differentiated cells. Yet, the efficiency of available protocols has not been systematically compared. To address this question, we quantified the number and size of cell cluster formed during differentiation using published and modified protocols and analyzed the abundance of neuronal and non-neuronal expression markers using immunocytochemistry. In the course of the experiments we observed that differentiation results strongly depend on the cell density at differentiation-initiation as well as on the type of used cell culture plastic ware. Based on those observations and the results from our comparative analysis, we created our own optimized and robust protocol that reproducibly reveals differentiated cells with high yield. We conclude that our method may be superior to differentiation of NT2 cells for systematic in vitro-based primary screening for developmental toxicants and neurotoxicants at different stages of maturation over previous protocols used. Our approach will also contribute to reduce animal testing in the context of the 3Rs.

Orai1 and Stim1 regulate normal and hypertrophic growth in cardiomyocytes. - Völkers, Mirko; Salz, Mareen; Herzog, Nicole; Frank, Derk; Dolatabadi, Nima; Frey, Norbert; Gude, Natalie; Friedrich, Oliver; Koch, Walter J.; Katus, Hugo; Sussmann, Marc A.; Most, Patrick (Journal of molecular and cellular cardiology, 2010)
Cardiac hypertrophy is an independent risk for heart failure (HF) and sudden death. Deciphering signalling pathways dependent on extracellular calcium (Ca(2+)) influx that control normal and pathological cardiac growth may enable identification of novel therapeutic targets. The objective of the present study is to determine the role of the Ca(2+) release-activated Ca(2+) (CRAC) channel Orai1 and stromal interaction molecule 1 (Stim1) in postnatal cardiomyocyte store operated Ca(2+) entry (SOCE) and impact on normal and hypertrophic postnatal cardiomyocyte growth. Employing a combination of siRNA-mediated gene silencing, cultured neonatal rat ventricular cardiomyocytes together with indirect immunofluorescence, epifluorescent Ca(2+) imaging and site-specific protein phosphorylation and real-time mRNA expression analysis, we show for the first time that both Orai1 and Stim1 are present in cardiomyocytes and required for SOCE due to intracellular Ca(2+) store depletion by thapsigargin. Stim1-KD but not Orai1-KD significantly decreased diastolic Ca(2+) levels and caffeine-releasable Ca(2+) from the sarcoplasmic reticulum (SR). Conversely, Orai1-KD but not Stim1-KD significantly diminished basal NRCM cell size, anp and bnp mRNA levels and activity of the calcineurin (CnA) signalling pathway although diminishing both Orai1 and Stim1 proteins similarly attenuated calmodulin kinase II (CamKII) and ERK1/2 activity under basal conditions. Both Orai1- and Stim1-KD completely abrogated phenylephrine (PE) mediated hypertrophic NRCM growth and enhanced natriuretic factor expression by inhibiting G(q)-protein conveyed activation of the CamKII and ERK1/2 signalling pathway. Interestingly, only Orai1-KD but not Stim1-KD prevented Gq-mediated CaN-dependent prohypertrophic signalling. This study shows for the first time that both Orai1 and Stim1 have a key role in cardiomyocyte SOCE regulating both normal and hypertrophic postnatal cardiac growth in vitro.
Keywords: Stim1; Orai1; Hypertrophy; Cardiac; Calcium

Partner, Neighbor, Housekeeper and Dimension: 3D versus 2D Glomerular Co-Cultures Reveal Drawbacks of Currently Used Cell Culture Models - Rederer, Anna; Rose, Victoria; Krüger, René; Schmittutz, Linda; Swierzy, Izabela; Fischer, Lena; Thievessen, Ingo; Bauer, Julian; Friedrich, Oliver; Schiffer, Mario; Müller-Deile, Janina (International Journal of Molecular Sciences, 2023)
Signaling-pathway analyses and the investigation of gene responses to different stimuli are usually performed in 2D monocultures. However, within the glomerulus, cells grow in 3D and are involved in direct and paracrine interactions with different glomerular cell types. Thus, the results from 2D monoculture experiments must be taken with caution. We cultured glomerular endothelial cells, podocytes and mesangial cells in 2D/3D monocultures and 2D/3D co-cultures and analyzed cell survival, self-assembly, gene expression, cell–cell interaction, and gene pathways using live/dead assay, time-lapse analysis, bulk-RNA sequencing, qPCR, and immunofluorescence staining. Without any need for scaffolds, 3D glomerular co-cultures self-organized into spheroids. Podocyte- and glomerular endothelial cell-specific markers and the extracellular matrix were increased in 3D co-cultures compared to 2D co-cultures. Housekeeping genes must be chosen wisely, as many genes used for the normalization of gene expression were themselves affected in 3D culture conditions. The transport of podocyte-derived VEGFA to glomerular endothelial cells confirmed intercellular crosstalk in the 3D co-culture models. The enhanced expression of genes important for glomerular function in 3D, compared to 2D, questions the reliability of currently used 2D monocultures. Hence, glomerular 3D co-cultures might be more suitable in the study of intercellular communication, disease modelling and drug screening ex vivo.
Created from Fastlane, Scopus look-up
Keywords: 3D co-culture; bulk-RNA sequencing; cell culture model; cell matrix; cell–cell communication; glomerular spheroids

Passive mechanical properties in healthy and infarcted rat left ventricle characterised via a mixture model - Martonová, Denisa; Alkassar, Muhannad; Seufert, Julia; Holz, David; Duong, Minh Tuan; Reischl, Barbara; Friedrich, Oliver; Leyendecker, Sigrid (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
During the cardiac cycle, electrical excitation is coupled with mechanical response of the myocardium. Besides the active contraction, passive mechanics plays an important role, and its behaviour differs in healthy and diseased hearts as well as among different animal species. The aim of this study is the characterisation of passive mechanical properties in healthy and infarcted rat myocardium by means of mechanical testing and subsequent parameter fitting. Elasticity assessments via uniaxial extension tests are performed on healthy and infarcted tissue samples from left ventricular rat myocardium. In order to fully characterise the orthotropic cardiac tissue, our experimental data are combined with other previously published tests in rats – shear tests on healthy myocardium and equibiaxial tests on infarcted tissue. In a first step, we calibrate the Holzapfel-Ogden strain energy function in the healthy case. Sa far, this orthotropic constitutive law for the passive myocardium has been fitted to experimental data in several species, however there is a lack of an appropriate parameter set for the rat. With our determined parameters, a finite element simulation of the end-diastolic filling is performed. In a second step, we propose a model for the infarcted tissue. It is represented as a mixture of intact myocardium and a transversely isotropic scar structure. In our mechanical experiments, the tissue after myocardial infarction shows significantly stiffer behaviour than in the healthy case, and the stiffness correlates with the amount of fibrosis. A similar relationship is observed in the computational simulation of the end-diastolic filling. We conclude that our new proposed material model can capture the behaviour of two kinds of tissues – healthy and infarcted rat myocardium, and its calibration with the fitted parameters represents the experimental data well.<br
CRIS-Team Scopus Importer:2021-04-09
Keywords: Fibrosis; Holzapfel-Ogden strain energy; Incompressibility; Myocardial infarction; Parameter fitting; Passive mechanics; Rat left ventricle

Performance of scientific cameras with different sensor types in measuring dynamic processes in fluorescence microscopy. - Jung, Jasmin; Weisenburger, S; Albert, S; Gilbert, Daniel; Friedrich, Oliver; Eulenburg, Volker; Kornhuber, Johannes; Groemer, Teja W. (Microscopy research and technique, 2013)
The plethora of available scientific cameras of different types challenges the biologically oriented experimenter when picking the appropriate camera for his experiment. In this study, we chose to investigate camera performances in a typical nonsingle molecule situation in life sciences, that is, quantitative measurements of fluorescence intensity changes from video data with typically skewed intensity distributions. Here, intensity profile dynamics of pH-sensors upon triggered changes of pH-environments in living cells served as a model system. The following camera types were tested: sCMOS, CCD (scientific and nonscientific) and EM-CCD (back- and front-illuminated). We found that although the EM-CCD cameras achieved the best absolute spatial SNR (signal-to-noise ratio) values, the sCMOS was at least of equal performance when the spatial SNR was related to the effective dynamic range, and it was superior in terms of temporal SNR. In the measurements of triggered intensity changes, the sCMOS camera had the advantage that it used the smallest fraction of its dynamic range when depicting intensity changes, and thus featured the best SNR at full usage of its dynamic range.

PfMDR1 Transport Rates Assessed in Intact Isolated Plasmodium falciparum Digestive Vacuoles Reflect Functional Drug Resistance Relationship with pfmdr1 Mutations - Simon, Nina; Voigtländer, Cornelia; Kappes, Bärbel; Rohrbach, Petra; Friedrich, Oliver (Pharmaceuticals, 2022)
Drug resistance often emerges from mutations in solute transporters. Single amino acid exchanges may alter functionality of transporters with ‘de novo’ ability to transport drugs away from their site of action. The PfMDR1 transporter (or P-glycoprotein 1) is located in the membrane of the digestive vacuole (DV), functions as an ATP-dependent pump, and transports substrates into the DV. In this study, four strains of Plasmodium falciparum, carrying various pfmdr1 gene mutations, were analysed for their transport characteristics of Fluo-4 in isolated DVs of parasites. To obtain quantitative estimates for PfMDR1 DV surface expression, PfMDR1 protein amounts on each strain’s DV membrane were evaluated by quantitative ELISA. Fluo-4, acting as a substrate for PfMDR1, was applied in DV uptake assays (‘reverse Ca2+ imaging’). Viable DVs were isolated from trophozoite stages with preserved PfMDR1 activity. This newly developed assay enabled us to measure the number of Fluo-4 molecules actively transported into isolated DVs per PfMDR1 molecule. The drug-resistant strain Dd2 presented the highest transport rates, followed by K1 and the drug-sensitive strain 3D7, compatible with their copy numbers. With this assay, an evaluation of the probability of resistance formation for newly developed drugs can be implemented in early stages of drug development.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Drug resistance; Fluo-4; P-glycoprotein 1; PfMDR1; Plasmodium falciparum; Transport protein

Physical activity and advanced cancer: evidence of exercise-sensitive genes regulating prostate cancer cell proliferation and apoptosis - Schwappacher, Raphaela; Schink, Kristin; Sologub, Svetlana; Dieterich, Walburga; Reljic, Dejan; Friedrich, Oliver; Herrmann, Hans J.; Neurath, Markus; Zopf, Yurdagül (The Journal of Physiology, 2020)
Key points: Physical activity is known to protect against cancer. The resistance exercise method whole-body electromyostimulation (WB-EMS) has a significant anti-cancer effect. WB-EMS-conditioned serum from advanced prostate cancer patients decreased human prostate carcinoma cell growth and viability in vitro. Multiplex analysis revealed that genes associated with human prostate cancer cell proliferation and apoptosis are sensitive for exercise. Feasible exercise should be part of multimodal anti-cancer therapies, also for physically weakened patients. Abstract: Regular physical activity is known to protect against cancer development. In cancer survivors, exercise reduces the risk of cancer recurrence and mortality. However, the link between exercise and decreased cancer risk and improved survival is still not well understood. Serum from exercising healthy individuals inhibits proliferation and activates apoptosis in various cancer cells, suggesting that mechanisms regulating cancer cell growth are affected by exercise. For the first time, we analysed serum from advanced-stage cancer patients with prostate (exercise group n = 8; control group n = 10) or colorectal (exercise n = 6; control n = 6) cancer, after a 12-week whole-body electromyostimulation training (20 min/session, 2×/week; frequency 85 Hz; pulse width 350 µs; 6 s stimulation, 4 s rest), a tolerable, yet effective, resistance exercise for physically weakened patients. We report that serum from these advanced cancer patients inhibits proliferation and enhances apoptosis of human prostate and colon cancer cells in vitro using cell growth and death assays (5-bromo-2′-deoxyuridine incorporation, cell counting, DNA fragmentation). Exercise-mimicking electric pulse stimulation of human primary myotubes showed that electric pulse stimulation-conditioned myotube medium also impairs human cancer cell viability. Gene expression analysis using a multiplex array of cancer-associated genes and subsequent quantitative RT-PCR revealed the presence of exercise-sensitive genes in human prostate cancer cells that potentially participate in the exercise-mediated regulation of malignant cell growth and apoptosis. Our data document the strong efficiency of the anti-oncogenic effects of physical activity and will further support the application of regular therapeutic exercise during cancer disease.
CRIS-Team Scopus Importer:2020-08-07
Keywords: apoptosis; cancer cells; colorectal cancer; electric pulse stimulation; exercise; gene expression; physical activity; proliferation; prostate cancer; whole-body electromyostimulation

PiezoGRIN: A High-Pressure Chamber Incorporating GRIN Lenses for High-Resolution 3D-Microscopy of living Cells and Tissues - Schneidereit, Dominik; Schürmann, Sebastian; Friedrich, Oliver (Advanced Science, 2018)
A high‐pressure optical chamber, PiezoGRIN, that facilitates label‐free 3D high‐resolution live‐cell multiphoton microscopy in thick tissue samples is presented. A set of two Gradient Index (GRIN) rod lenses is integrated into the chamber as an optical guide and allows for the adjustment of the focal plane through the sample providing a field of view volume of 450 × 450 × 500 µm (x, y, z). An optical lateral resolution of 0.8 µm is achieved by using two‐photon excitation with 150 fs pulses of a 810 nm titanium–sapphire laser at hydrostatic pressures up to 200 MPa. With the PiezoGRIN setup, it is possible to follow pressure‐induced changes in subcellular structure of unstained vital mouse skeletal muscle tissue up to 200 µm below the tissue surface.<br
Keywords: second harmonic generation; skeletal muscle; high pressure; multiphoton microscopy

Portoporator©: A portable low-cost electroporation device for gene transfer to cultured cells in biotechnology, biomedical research and education - Schmitt, Max; Friedrich, Oliver; Gilbert, Daniel (Biosensors and Bioelectronics, 2019)
Electroporation has been a widely established method for delivering DNA and other material into cells in vitro. Conventional electroporation infrastructure is typically immobile, non-customizable, non-transparent regarding the characteristics of output pulses, and expensive. Here, we describe a portable electroporator for DNA delivery into bacterial cells that can quickly be reconstructed using 3D desktop printing and off-the-shelf components. The device is light weight (700 g), small (70 x 180 x 210 mm) and extremely low-cost (< EUR 130). We provide the electrical circuitry and a detailed parts list for rebuilding the device. We characterize the properties of generated pulses and apply the system for gene delivery into bacterial Dh5a cells. We analyze the transformation efficiency based on the optical density of cell suspensions at 595 nm and on quantitative analysis of images obtained from bacterial cell-grown agar plates using colony forming units as well as confluence as indicators. We demonstrate time-dependency of the transformation efficiency using single pulses of 500 V between 1 and 1000 ms duration and we show that commercially available electroporation cuvettes of 1 mm gap size reveal higher transformation rates compared to cuvettes with 2 mm gap. We benchmark the transformation efficiency obtained using our platform with data from a heat shock-based transformation protocol and with data from a commercially available electroporator and show that our system reveals comparable results as the other techniques in the applied configurations. While this work focuses on genetic manipulation of bacterial cells, the device may also be applicable for delivery of genetic material small molecule or nanomaterials into other cell types, including mammalian cells.
CRIS-Team WoS Importer:2019-04-16
Keywords: 3D printing; Arduino; Dh5α; Electroporation; Transformation

Preaged remodeling of myofibrillar cytoarchitecture in skeletal muscle expressing R349P mutant desmin - Diermeier, Stefanie; Buttgereit, Andreas; Schürmann, Sebastian; Winter, Lilli; Xu, Hongyang; Murphy, Robyn M.; Clemen, Christoph S.; Schröder, Rolf; Friedrich, Oliver (Neurobiology of Aging, 2017)
The majority of hereditary and acquired myopathies are clinically characterized by progressive muscle weakness. We hypothesized that ongoing derangement of skeletal muscle cytoarchitecture at the single fiber level may precede and be responsible for the progressive muscle weakness. Here, we analyzed the effects of aging in wild-type (wt) and heterozygous (het) and homozygous (hom) R349P desmin knock-in mice. The latter harbor the ortholog of the most frequently encountered human R350P desmin missense mutation. We quantitatively analyzed the subcellular cytoarchitecture of fast- and slow-twitch muscles from young, intermediate, and aged wt as well as desminopathy mice. We recorded multiphoton second harmonic generation and nuclear fluorescence signals in single muscle fibers to compare aging-related effects in all genotypes. The analysis of wt mice revealed that the myofibrillar cytoarchitecture remained stable with aging in fast-twitch muscles, whereas slow-twitch muscle fibers displayed structural derangements during aging. In contrast, the myofibrillar cytoarchitecture and nuclear density were severely compromised in fast- and slow-twitch muscle fibers of hom R349P desmin mice at all ages. Het mice only showed a clear degradation in their fiber structure in fast-twitch muscles from the adult to the presenescent age bin. Our study documents distinct signs of normal and R349P mutant desmin-related remodeling of the 3D myofibrillar architecture during aging, which provides a structural basis for the progressive muscle weakness.
EVALuna2:7375

Pressure, the nervous system and ion channels: Are humans too complicated? - Friedrich, Oliver (Undersea & Hyperbaric Medicine, 2010)

Proliferation characteristics of cells cultured under periodic versus static conditions. - Gilbert, Daniel; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Wiest, Joachim (Cytotechnology, 2019)
In vitro culture models have become an indispensable tool for assessing a vast variety of biological questions in many scientific fields. However, common in vitro cultures are maintained under static conditions, which do not reflect the in vivo situation and create a non-physiological environment. To assess whether the growth characteristics of cells cultured at pulsed-perfused versus static conditions differ, we observed the growth of differentially cultured cells in vitro by life-cell time-lapse imaging of recombinant HEK293YFPI152L cells, stably expressing yellow fluorescent protein. Cells were grown for 30 h at 37 °C and ambient CO2 concentration in biochips mounted into a custom-designed 3D printed carrier and were imaged at a rate of ten images per hour using a fluorescence microscope with environment control infrastructure. Cells in one chip were maintained under static conditions whereas cells in another chip were recurrently perfused with fresh media. Generated image series were quantitatively analyzed using a custom-modified cell detection software. Imaging data averaged from four biological replicates per culturing condition demonstrate that cells cultured under conventional conditions exhibit an exponential growth rate. In contrast, cells cultured in periodic mode exhibited a non-exponential growth rate. Our data clearly indicate differential growth characteristics of cells cultured under periodic versus static conditions highlighting the impact of the culture conditions on the physiology of cells in vitro.
Keywords: Biochip; Cell growth; HEK293; Long-term time-lapse microscopy; Microfluidics; YFPI152L

Prolonged high-pressure treatments in mammalian skeletal muscle result in loss of functional sodium channels and altered calcium channel kinetics. - Friedrich, Oliver; Kress, Kai; Hartmann, Martin; Frey, Benjamin; Sommer, Karl; Ludwig, Horst; Fink, Rainer (Cell Biochemistry and Biophysics, 2006)
Activation and inactivation of ion channels involve volume changes from conformational rearrangements of channel proteins. These volume changes are highly susceptible to changes in ambient pressure. Depending on the pressure level, channel function may be irreversibly altered by pressure. The corresponding structural changes persist through the post-decompression phase. High-pressure applications are a useful tool to evaluate the pressure dependence as well as pressure limits for reversibility of such alterations. Mammalian cells are only able to tolerate much lower pressures than microorganisms. Although some limits for pressure tolerance in mammalian cells have been evaluated, the mechanisms of pressure-induced alteration of membrane physiology, in particular of channel function, are unknown. To address this question, we recorded fast inward sodium (I(Na)) and slowly activating L-type calcium (I(Ca)) currents in single mammalian muscle fibers in the post-decompression phase after a prolonged 3-h, high-pressure treatment of up to 20 MPa. I(Na) and I(Ca) peak amplitudes were markedly reduced after pressure treatment at 20 MPa. This was not from a general breakdown of membrane integrity as judged from in situ high-pressure fluorescence microscopy. Membrane integrity was preserved even for pressures as high as 35 MPa at least for pressure applications of shorter durations. Therefore, the underlying mechanisms for the observed amplitude reductions have to be determined from the activation (time-to-peak [TTP]) and inactivation (tau(dec)) kinetics of I(Na) and I(Ca). No major changes in I(Na) kinetics, but marked increases, both in TTP and tau(dec) for I(Ca), were detected after 20 MPa. The apparent molecular volume changes (activation volumes) deltaV(double dagger) for the pressure-dependent irreversible alteration of channel gating approached zero for Na+ channels. For Ca2+ channels, deltaV(double dagger) was very large, with approx 2.5-fold greater values for channel activation than inactivation (approx 210 A3). We conclude, that in skeletal muscle, high pressure differentially and irreversibly affects the gating properties and the density of functional Na+ and Ca2+ channels. Based on these results, a model of high pressure-induced alterations to the channel conformation is proposed.

Protocol for Cell Colonization and Comprehensive Monitoring of Osteogenic Differentiation in 3D Scaffolds Using Biochemical Assays and Multiphoton Imaging - Sommer, Kai Peter; Krolinski, Adrian; Mirkhalaf, Mohammad; Zreiqat, Hala; Friedrich, Oliver; Vielreicher, Martin (International Journal of Molecular Sciences, 2023)
The goal of bone tissue engineering is to build artificial bone tissue with properties that closely resemble human bone and thereby support the optimal integration of the constructs (biografts) into the body. The development of tissues in 3D scaffolds includes several complex steps that need to be optimized and monitored. In particular, cell–material interaction during seeding, cell proliferation and cell differentiation within the scaffold pores play a key role. In this work, we seeded two types of 3D-printed scaffolds with pre-osteoblastic MC3T3-E1 cells, proliferated and differentiated the cells, before testing and adapting different assays and imaging methods to monitor these processes. Alpha-TCP/HA (α-TCP with low calcium hydroxyapatite) and baghdadite (Ca3ZrSi2O9) scaffolds were used, which had comparable porosity ( 50%) and pore sizes ( 300–400 µm). Cell adhesion to both scaffolds showed 95% seeding efficiency. Cell proliferation tests provided characteristic progression curves over time and increased values for α-TCP/HA. Transmitted light imaging displayed a homogeneous population of scaffold pores and allowed us to track their opening state for the supply of the inner scaffold regions by diffusion. Fluorescence labeling enabled us to image the arrangement and morphology of the cells within the pores. During three weeks of osteogenesis, ALP activity increased sharply in both scaffolds, but was again markedly increased in α-TCP/HA scaffolds. Multiphoton SHG and autofluorescence imaging were used to investigate the distribution, morphology, and arrangement of cells; collagen-I fiber networks; and hydroxyapatite crystals. The collagen-I networks became denser and more structured during osteogenic differentiation and appeared comparable in both scaffolds. However, imaging of the HA crystals showed a different morphology between the two scaffolds and appeared to arrange in the α-TCP/HA scaffolds along collagen-I fibers. ALP activity and SHG imaging indicated a pronounced osteo-inductive effect of baghdadite. This study describes a series of methods, in particular multiphoton imaging and complementary biochemical assays, to validly measure and track the development of bone tissue in 3D scaffolds. The results contribute to the understanding of cell colonization, growth, and differentiation, emphasizing the importance of optimal media supply of the inner scaffold regions.<br
Keywords: bone cells; 3D-printed scaffolds; biograft; osteogenesis; collagen-I; mineralization; biochemical assays; imaging

Quantification of human complement factor H binding to asexual malaria blood stages by an enzyme-linked immunosorbent assay - Simon, Nina; Friedrich, Oliver; Kappes, Bärbel (Vaccine, 2018)
Keywords: Complement system; ELISA validation; Asexual blood stages; Surface binding; Human factor H; Malaria

Quantitative calcium measurements in subcellular compartments of Plasmodium falciparum-infected erythrocytes - Rohrbach, Petra; Friedrich, Oliver; Hentschel, Joachim; Plattner, Helmut; Fink, Rainer; Lanzer, Michael (Journal of Biological Chemistry, 2005)
The acidic food vacuole exerts several important functions during intraerythrocytic development of the human malarial parasite Plasmodium falciparum. Hemoglobin taken up from the host erythrocyte is degraded in the food vacuole, and the heme liberated during this process is crystallized to inert hemozoin. Several antimalarial drugs target food vacuolar pathways, such as hemoglobin degradation and heme crystallization. Resistance and sensitization to some antimalarials is associated with mutations in food vacuolar membrane proteins. Other studies suggest a role of the food vacuole in ion homeostasis, and release of Ca from the food vacuole may mediate adopted physiological responses. To investigate whether the food vacuole is an intracellular Ca store, which in turn may affect other physiological functions in which this organelle partakes, we have investigated total and exchangeable Ca within the parasite's food vacuole using x-ray microanalysis and quantitative confocal live cell Ca imaging. Apparent free Ca concentrations of ∼90, ∼350, and ∼400 nM were found in the host erythrocyte cytosol, the parasite cytoplasm, and the food vacuole, respectively. In our efforts to determine free intracellular Ca concentrations, we evaluated several Ca-sensitive fluorochromes in a live cell confocal setting. We found that the ratiometric Ca indicator Fura-Red provides reliable determinations, whereas measurements using the frequently used Fluo-4 are compromised due to problems arising from phototoxicity, photobleaching, and the strong pH dependence of the dye. Our data suggest that the food vacuole contains only moderate amounts of Ca, disfavoring a role as a major intracellular Ca store. © 2005 by The American Society for Biochemistry and Molecular Biology, Inc.

Quantitative Live-Cell Ca2+ Imaging During Isotropic Cell Stretch - Schöler, Ulrike; Merten, Anna-Lena; Schürmann, Sebastian; Friedrich, Oliver (Cell Viability Assays (2nd Edt), 2023)
Cell viability of many cell types strongly relies on their ability to adjust to mechanical conditions and alterations. Cellular mechanisms for sensing and responding to mechanical forces and pathophysiological variations in these processes have become an emerging research field in recent years. An important signaling molecule involved in mechanotransduction as in many cellular processes is Ca2+. New experimental methods to probe cellular Ca2+ signaling live under conditions of mechanical stimulation facilitate new insights into previously overlooked aspects of mechanical regulation of cells. Here, we describe a protocol for using Ca2+ imaging in combination with a cell stretching device, the IsoStretcher. Cells grown on elastic membranes can be isotopically stretched in-plane, and their intracellular Ca2+ level can be accessed online on the single cell level using fluorescent calcium indicator dyes. We show a protocol for functional screening of mechanosensitive ion channels and related drug screenings using BJ cells, a foreskin fibroblast cell line that strongly reacts to acute mechanical stimulation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Calcium imaging; Cell stretching; Image processing; IsoStretcher; Mechanobiology; Mechanosignaling; Mechanotransduction

Quantitative Ratiometric Ca(2+) Imaging to Assess Cell Viability. - Friedrich, Oliver; Head, Stewart (Methods in Molecular Biology, 2017)
Viability of cells is strongly related to their Ca(2+) homeostasis. Ca(2+) signal fluctuations can be on a slow time scale, e.g., in non-excitable cells, but also in the range of tens of milliseconds for excitable cells, such as nerve and muscle. Muscle fibers respond to electrical stimulation with Ca(2+) transients that exceed their resting basal level about 100 times. Fluorescent Ca(2+) dyes have become an indispensable means to monitor Ca(2+) fluctuations in living cells online. Fluorescence intensity of such "environmental dyes" relies on a buffer-ligand interaction which is not only governed by laws of mass action but also by binding and unbinding kinetics that have to be considered for proper Ca(2+) kinetics and amplitude validation. The concept of Ca(2+) dyes including the different approaches using ratiometric and non-ratiometric dyes, the way to correctly choose dyes according to their low-/high-affinity properties and kinetics as well as staining techniques, and in situ calibration are reviewed and explained. We provide detailed protocols to apply ratiometric Fura-2 imaging of resting Ca(2+) and Ca(2+) fluctuations during field-stimulation in single isolated skeletal muscle cells and how to translate fluorescence intensities into absolute Ca(2+) concentrations using appropriate calibration techniques.

Rapid Ca2+ flux through the transverse tubular membrane, activated by individual action potentials in mammalian skeletal muscle. - Launikonis, Bradley S.; Stephenson, D. George; Friedrich, Oliver (The Journal of Physiology, 2009)
Periods of low frequency stimulation are known to increase the net Ca(2+) uptake in skeletal muscle but the mechanism responsible for this Ca(2+) entry is not known. In this study a novel high-resolution fluorescence microscopy approach allowed the detection of an action potential-induced Ca(2+) flux across the tubular (t-) system of rat extensor digitorum longus muscle fibres that appears to be responsible for the net uptake of Ca(2+) in working muscle. Action potentials were triggered in the t-system of mechanically skinned fibres from rat by brief field stimulation and t-system [Ca(2+)] ([Ca(2+)](t-sys)) and cytoplasmic [Ca(2+)] ([Ca(2+)](cyto)) were simultaneously resolved on a confocal microscope. When initial [Ca(2+)](t-sys) was > or = 0.2 mM a Ca(2+) flux from t-system to the cytoplasm was observed following a single action potential. The action potential-induced Ca(2+) flux and associated t-system Ca(2+) permeability decayed exponentially and displayed inactivation characteristics such that further Ca(2+) entry across the t-system could not be observed after 2-3 action potentials at 10 Hz stimulation rate. When [Ca(2+)](t-sys) was closer to 0.1 mM, a transient rise in [Ca(2+)](t-sys) was observed almost concurrently with the increase in [Ca(2+)](cyto) following the action potential. The change in direction of Ca(2+) flux was consistent with changes in the direction of the driving force for Ca(2+). This is the first demonstration of a rapid t-system Ca(2+) flux associated with a single action potential in mammalian skeletal muscle. The properties of this channel are inconsistent with a flux through the L-type Ca(2+) channel suggesting that an as yet unidentified t-system protein is conducting this current. This action potential-activated Ca(2+) flux provides an explanation for the previously described Ca(2+) entry and accumulation observed with prolonged, intermittent muscle activity.

Rapid prototype of a portable long-term live-cell imaging system for biomedical research and education - Abolpour Mofrad, Sepideh; Walzik, Maria P.; Vollmar, Verena; Lachnit, Theresa; Bachmann, Holger; Aschenbrenner, Daniel; Friedrich, Oliver; Gilbert, Daniel (Wiley-Blackwell, 2014)

Redox Balance Differentially Affects Biomechanics in Permeabilized Single Muscle Fibres—Active and Passive Force Assessments with the Myorobot - Michael, Mena; Kovbasyuk, Larisa; Ritter, Paul; Reid, Michael B.; Friedrich, Oliver; Haug, Michael (Cells, 2022)
An oxidizing redox state imposes unique effects on the contractile properties of muscle. Permeabilized fibres show reduced active force generation in the presence of H2O2. However, our knowledge about the muscle fibre’s elasticity or flexibility is limited due to shortcomings in assessing the passive stress–strain properties, mostly due to technically limited experimental setups. The MyoRobot is an automated biomechatronics platform that is well-capable of not only investigating calcium responsiveness of active contraction but also features precise stretch actuation to examine the passive stress–strain behaviour. Both were carried out in a consecutive recording sequence on the same fibre for 10 single fibres in total. We denote a significantly diminished maximum calcium-saturated force for fibres exposed to ≥500 µM H2O2, with no marked alteration of the pCa50 value. In contrast to active contraction (e.g., maximum isometric force activation), passive restoration stress (force per area) significantly increases for fibres exposed to an oxidizing environment, as they showed a non-linear stress–strain relationship. Our data support the idea that a highly oxidizing environment promotes non-linear fibre stiffening and confirms that our MyoRobot platform is a suitable tool for investigating redox-related changes in muscle biomechanics.
CRIS-Team Scopus Importer:2022-12-23
Keywords: calcium sensitivity; MyoRobot; passive stiffness; redox balance; single muscle fibre

Regulation of murine cardiac contractility by activation of α(1A)-adrenergic receptor-operated Ca(2+) entry. - Mohl, Marion C.; Iismaa, Siiri E.; Xiao, Xiao-Hui; Friedrich, Oliver; Wagner, Sören; Nikolova-Krstevski, Vesna; Wu, Jianxin; Yu, Ze-Yan; Feneley, Michael; Fatkin, Diane; Allen, David G.; Graham, Robert M. (Cardiovascular Research, 2011)
AIMS Sympathetic regulation of cardiac contractility is mediated in part by α(1)-adrenergic receptors (ARs), and the α(1A)-subtype has been implicated in the pathogenesis of cardiac hypertrophy. However, little is known about α(1A)-AR signalling pathways in ventricular myocardium. The aim of this study was to determine the signalling pathway that mediates α(1A)-AR-coupled cardiac contractility. METHODS AND RESULTS Using a transgenic model of enhanced cardiac α(1A)-AR expression and signalling (α(1A)-H mice), we identified a receptor-coupled signalling pathway that enhances Ca(2+) entry and increases contractility. This pathway involves α(1A)-AR-activated translocation of Snapin and the transient receptor potential canonical 6 (TRPC6) channel to the plasma membrane. In ventricular cardiomyocytes from α(1A)-H and their non-transgenic littermates (or WTs), stimulation with α(1A)-AR-specific agonists resulted in increased [Ca(2+)](i), which was dose-related and proportional to the level of α(1A)-AR expression. Blockade of TRPC6 inhibited the α(1A)-AR-mediated increase in [Ca(2+)](i) and contractility. External Ca(2+) entry, underlying the [Ca(2+)](i) increase, was not due to store-operated Ca(2+) entry but to a receptor-operated mechanism of Ca(2+) entry resulting from α(1A)-AR activation. CONCLUSION These findings indicate that Ca(2+) entry via the α(1A)-AR-Snapin-TRPC6-pathway plays an important role in physiological regulation of cardiac contractility and may be an important target for augmenting cardiac performance.
Keywords: alpha(1A)-AR; TRPC; Cardiac contractile function; Cell signalling; Calcium cycling

Resting membrane potentials recorded on-site in intact skeletal muscles from deep sea fish (Sigmops gracile) salvaged from depths up to 1.000 m. - von Wegner, Frederic; Koyama, Sumihiro; Miwa, Tetsuya; Friedrich, Oliver (Marine Biotechnology, 2008)
The effect of elevated ambient pressures in deep sea fish residing at certain bottom depths or even covering different depth levels during migration is poorly understood. Elevated pressures are known to influence membrane properties of various excitable tissues in many species. Reliable results on membrane properties require freshly isolated living cells and short decompression times. During a scientific cruise south of Japan, deep sea fish were sampled from depths up to 1.000 m by using the intelligent operative net sampling system IONESS. On-site electrophysiological recordings of resting membrane potentials were performed in freshly isolated skeletal muscles from Sigmops gracile. Experiments were conducted at various extracellular K+ concentrations to derive relative membrane ion permeabilities and estimate intracellular K+ concentrations [K+]i in the muscles studied. With increasing sampling depth, a tendency for depolarized resting membrane potentials was observed. This could be explained by an increase in relative Na+ over K+ resting membrane permeabilities. Fish samples from deeper sites also had larger [K+]i values compared with shallower sites. This study represents a first approach to perform sophisticated physiological live-cell experiments on board a fully operating ship. These data are expected to more realistically reflect the physiological state of biological preparations residing in the deep se
Keywords: Deep sea fish; Skeletal muscle; Resting membrane potential; High pressure; Sigmops gracile

Reversibility of high pressure effects on the contractility of skeletal muscle. - Friedrich, Oliver; Kress, Kai; Ludwig, Horst; Fink, Rainer (Journal of Muscle Research and Cell Motility, 2001)
High pressure application has been extensively used to thermodynamically influence complex physiological processes such as membrane ion conductances and the mechanism of muscle contraction. However, little is known about the reversibility of high pressure effects on intact cells. Therefore, we studied the reversibility of 3 h pressure applications up to 25 MPa at +4 degrees C to intact murine skeletal muscle. Functional mechanical properties were tested in extensor digitorum muscle fibres skinned following a high pressure exposure. Calcium activated force and stiffness were nearly unchanged following pressure applications up to 20 MPa, whereas for higher pressures we found a marked reduction of peak force, a decline of activation kinetics, an increase of relaxation stiffness but still unchanged peak stiffness. The rigor kinetics showed a similar behaviour as the activation kinetics. pCa-force relations remained unchanged up to 20 MPa but were shifted towards smaller pCa values for higher pressures. In conclusion there is a rather sharp high pressure limit of 20 MPa above of which pressure application results in a substantial irreversible loss of contractile functionality in differentiated muscle which may at least partly be explained by changes in the Ca2+ regulatory process. This is supported by a degradation of the 37 kDa band, i.e. Troponin T, shown by SDS gel electrophoresis. However, the general stability of the other bands does not indicate a substantial increase of unspecific protease activity following a high pressure treatment up to 25 MPa.

S100A1 decreases calcium spark frequency and alters their spatial characteristics in permeabilized adult ventricular cardiomyocytes. - Völkers, Mirko; Loughrey, Christopher M.; MacQuaide, Niall; Remppis, Björn Andrew; DeGeorge, Brent R.; von Wegner, Frederic; Friedrich, Oliver; Fink, Rainer; Koch, Walter J.; Smith, Godfrey L.; Most, Patrick (Cell Calcium, 2007)
S100A1, a Ca2+-sensor protein of the EF-hand type, exerts positive inotropic effects in the heart via enhanced cardiac ryanodine receptor (RyR2) activity. Here we report that S100A1 protein (0.1microM) interacts with the RyR2 in resting permeabilized cardiomyocytes at free Ca2+-levels comparable to diastolic Ca2+-concentrations ( approximately 150nM). Alterations of RyR2 function due to S100A1 binding was assessed via analysis of Ca2+-spark characteristics. Ca2+-spark frequency, amplitude and duration were all reduced upon perfusion with 0.1microM S100A1 protein by 38%, 14% and 18%, respectively. Most likely, these effects were conveyed through the S100A1 C-terminus (S100A1-ct; amino acids 75-94) as the corresponding S100A1-ct peptide (0.1microM) inhibited S100A1 protein binding to the RyR2 and similarly attenuated frequency, amplitude and duration of Ca2+-sparks by 52%, 8% and 26%, respectively. Accordingly, the sarcoplasmic reticulum (SR) Ca2+-content was slightly increased but the stoichiometry of other accessory RyR2 modulators (sorcin/FKBP12.6) remained unaltered by S100A1. Hence, we propose S100A1 as a novel inhibitory modulator of RyR2 function at diastolic Ca2+-concentrations in rabbit ventricular cardiomyocytes.
Keywords: S100A1; Calcium; Sparks; Ryanodine receptor

S100A1 DNA-based Inotropic Therapy Protects Against Proarrhythmogenic Ryanodine Receptor 2 Dysfunction. - Ritterhoff, Julia; Völkers, Mirko; Seitz, Andreas; Spaich, Kristin; Gao, Erhe; Peppel, Karsten; Pleger, Sven; Zimmermann, Wolfram; Friedrich, Oliver; Fink, Rainer; Koch, Walter; Katus, Hugo; et al. (Molecular Therapy, 2015)
Restoring expression levels of the EF-hand calcium (Ca(2+)) sensor protein S100A1 has emerged as a key factor in reconstituting normal Ca(2+) handling in failing myocardium. Improved sarcoplasmic reticulum (SR) function with enhanced Ca(2+) resequestration appears critical for S100A1's cyclic adenosine monophosphate-independent inotropic effects but raises concerns about potential diastolic SR Ca(2+) leakage that might trigger fatal arrhythmias. This study shows for the first time a diminished interaction between S100A1 and ryanodine receptors (RyR2s) in experimental HF. Restoring this link in failing cardiomyocytes, engineered heart tissue and mouse hearts, respectively, by means of adenoviral and adeno-associated viral S100A1 cDNA delivery normalizes diastolic RyR2 function and protects against Ca(2+)- and β-adrenergic receptor-triggered proarrhythmogenic SR Ca(2+) leakage in vitro and in vivo. S100A1 inhibits diastolic SR Ca(2+) leakage despite aberrant RyR2 phosphorylation via protein kinase A and calmodulin-dependent kinase II and stoichiometry with accessory modulators such as calmodulin, FKBP12.6 or sorcin. Our findings demonstrate that S100A1 is a regulator of diastolic RyR2 activity and beneficially modulates diastolic RyR2 dysfunction. S100A1 interaction with the RyR2 is sufficient to protect against basal and catecholamine-triggered arrhythmic SR Ca(2+) leak in HF, combining antiarrhythmic potency with chronic inotropic actions.

Scanning multi photon microscopy of SHG signals from single myofibrils of mammalian skeletal muscle - Vogel, Martin; Schürmann, Sebastian; Friedrich, Oliver; von Wegner, Frederic; Both, Martin; Fink, Rainer (Multiphoton Microscopy in the Biomedical Sciences VI, 2006)
We have recently shown that intrinsic, chromophore free Second Harmonic Generation (SHG) signals can be obtained from myofibrillar structures of mammalian skeletal muscle (Both et al. 2003, Proc. SPIE 5139: 112-120; Both et al. 2004, JBO 9(5):882-892). Here, we report experiments at the level of single myofibrils (diameters 1 to 2 μm) to characterize the spatial dependency of the hyperpolarizability chi(2) and to generate a map of this tensor in myofibrillar structures. Myofibrils are the smallest functional sub cellular contractile structures of muscle. They are organized in a regular sarcomer pattern with a periodicity of 2 to 3 μm. Single myofibrils were obtained from mammalian skeletal muscle using a combined chemical and mechanical fractionation. The SHG signals were recorded with an inverse laser scanning microscope (Leica SP2). A ps laser source (Ti:Sa laser, Tsunami, Spectra Physics) tuned to 880 nm was used to excite the sample through an objective of high NA (1.2NA, 63x). The laser source was linearly polarized and the axis of polarization could be adjusted in steps of degrees with a half-wave plate. The forward scattered SHG signal was collected with a matching objective placed above the preparation. The SHG signals depend both on polarization and location within the myofibrillar structures. The SHG signals seem to arise from the myosin molecules. In conclusion, SHG imaging allows to monitor the myofibrillar structure with two photon resolution.
Keywords: Mammalian skeletal muscle; Myofibril; Second harmonic generation; Skeletal and cardiac myopathies

Screen printed 3D microfluidic paper-based and modifier-free electroanalytical device for clozapine sensing - Ghanbari, Mohammad Hossein; Biesalski, Markus; Friedrich, Oliver; Etzold, Bastian (Analyst, 2024)
The increasing demand in healthcare for accessible and cost-effective analytical tools is driving the development of reliable platforms to the customization of therapy according to individual patient drug serum levels, e.g. of anti-psychotics in schizophrenia. A modifier-free microfluidic paper-based electroanalytical device (μPED) holds promise as a portable, sensitive, and affordable solution. While many studies focus on the working electrode catalysts, improvements by engineering aspects e.g. of the electrode arrangement are less reported. In our study, we demonstrate the enhanced capabilities of the 3D electrode layout of μPED compared to 2D μPED arrangements. We especially show that screen printing can be employed to prepare 3D μPEDs. We conducted a comparison of different 2D and 3D electrode arrangements utilizing cyclic voltammetry in [Fe(CN)6]3−/4−, along with square-wave voltammetry for clozapine (CLZ) sensing. Our findings reveal that the utilization of the 3D μPED leads to an increase in both the electrochemically active surface area and the electron transfer rate. Consequently, this enhancement contributes to improve sensitivity in the CLZ sensing. The 3D μPED clearly outperforms the 2D μPED arrangement in terms of signal strength. With the 3D μPED under the optimized conditions, a linear dose-response for a concentration range from 7.0 to 100 μM was achieved. The limit of detection and sensitivity was determined to be 1.47 μM and 1.69 μA μM−1 cm−2, respectively. This evaluation is conducted in the context of detection and determination of CLZ in a human blood serum sample. These findings underscore the potential of the 3D μPED for future applications in pharmacokinetic analyses and clinical tests to personalize the management of schizophrenia.
CRIS-Team Scopus Importer:2024-10-25

Second harmonic generation microscopy probes different states of motor protein interaction in myofibrils - Schürmann, Sebastian; von Wegner, Frederic; Fink, Rainer; Friedrich, Oliver; Vogel, M. (Biophysical Journal, 2010)
The second harmonic generation (SHG) signal intensity sourced from skeletal muscle myosin II strongly depends on the polarization of the incident laser beam relative to the muscle fiber axis. This dependence is related to the second-order susceptibility x(2), which can be described by a single component ratio γ under generally assumed symmetries. We precisely extracted γ from SHG polarization dependence curves with an extended focal field model. In murine myofibrillar preparations, we have found two distinct polarization dependencies: With the actomyosin system in the rigor state, γ . has a mean value of γ = 0.52 (SD = 0.04, n = 55); in a relaxed state where myosin is not bound to actin, γ has a mean value of γ = 0.24 (SD = 0.07, n = 70). We observed a similar value in an activated state where the myosin power stroke was pharmacologically inhibited using N-benzyl-p-toluene sulfonamide. In summary, different actomyosin states can be visualized noninvasively with SHG microscopy. Specifically, SHG even allows us to distinguish different actin-bound states of myosin II using γ as a parameter. © 2010 by the Biophysical Society.

Second Harmonic Generation Morphometry of Muscle Cytoarchitecture in Living Cells - Schneidereit, Dominik; Nübler, Stefanie; Friedrich, Oliver (Cell Viability Assays (2nd Edt.), 2023)
The architectural structure of cells is essential for the cells’ function, which becomes especially apparent in the highly “structure functionally” tuned skeletal muscle cells. Here, structural changes in the microstructure can have a direct impact on performance parameters, such as isometric or tetanic force production. The microarchitecture of the actin-myosin lattice in muscle cells can be detected noninvasively in living cells and in 3D by using second harmonic generation (SHG) microscopy, forgoing the need to alter samples by introducing fluorescent probes into them. Here, we provide tools and step-by-step protocols to guide the processes of obtaining SHG microscopy image data from samples, as well as extracting characteristic values from the image data to quantify the cellular microarchitecture using characteristic patterns of myofibrillar lattice alignments.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Multiphoton imaging; Quantitative morphometry; Sarcomere architecture; Second harmonic generation; Skeletal muscle

Second harmonic imaging of intrinsic signals in muscle fibers in situ. - Both, Martin; Vogel, Martin; Friedrich, Oliver; von Wegner, Frederic; Künsting, Thomas; Fink, Rainer; Uttenweiler, Dietmar (Journal of Biomedical Optics, 2004)
We use second harmonic generation (SHG) imaging to study and quantify a strong intrinsic SHG signal in skeletal muscle fiber preparations and single isolated myofibrils. The intrinsic signal follows the striation pattern of the muscle cells and is positioned at the sarcomeric location of the myosin filaments. Interestingly, the signal is enhanced at the region where the myosin heads are located on the myosin filaments. As the intrinsic signal reflects the subcellular structure in an accurate way, SHG can be used for noninvasive high resolution structural imaging without exogenous labels in living muscle cells. This may be very important for detecting changes in myofibrillar organization occurring under pathophysiological conditions, e.g., in cardiac and skeletal myopathies. Due to the strong dependency of SHG on orientation and symmetries of the tissue, it may allow the study of dynamic interactions between the contractile proteins actin and myosin during force production and muscle shortening. Furthermore, SHG imaging can be combined with other nonlinear microscopical techniques, such as laser scanning multiphoton fluorescence microscopy, to simultaneously measure other dynamic cellular processes, representing a complementary method and extending the range of nonlinear microscopical method

SEMPAI: a Self-Enhancing Multi-Photon Artificial Intelligence for Prior-Informed Assessment of Muscle Function and Pathology - Mühlberg, Alexander; Ritter, Paul; Langer, Sabine; Goossens, Chloë; Nübler, Stefanie; Schneidereit, Dominik; Taubmann, Oliver; Denzinger, Felix; Nörenberg, Dominik; Haug, Michael; Schürmann, Sebastian; Horstmeyer, Roarke; et al. (Advanced Science, 2023)
Deep learning (DL) shows notable success in biomedical studies. However, most DL algorithms work as black boxes, exclude biomedical experts, and need extensive data. This is especially problematic for fundamental research in the laboratory, where often only small and sparse data are available and the objective is knowledge discovery rather than automation. Furthermore, basic research is usually hypothesis-driven and extensive prior knowledge (priors) exists. To address this, the Self-Enhancing Multi-Photon Artificial Intelligence (SEMPAI) that is designed for multiphoton microscopy (MPM)-based laboratory research is presented. It utilizes meta-learning to optimize prior (and hypothesis) integration, data representation, and neural network architecture simultaneously. By this, the method allows hypothesis testing with DL and provides interpretable feedback about the origin of biological information in 3D images. SEMPAI performs multi-task learning of several related tasks to enable prediction for small datasets. SEMPAI is applied on an extensive MPM database of single muscle fibers from a decade of experiments, resulting in the largest joint analysis of pathologies and function for single muscle fibers to date. It outperforms state-of-the-art biomarkers in six of seven prediction tasks, including those with scarce data. SEMPAI's DL models with integrated priors are superior to those without priors and to prior-only approaches.
CRIS-Team Scopus Importer:2023-08-25
Keywords: deep learning; explainable artificial intelligence; meta-learning; multiphoton microscopy; muscle research; prior information integration; scientific machine learning

Septic cardiomyopathy in rat LPS-induced endotoxemia: relative contribution of cellular diastolic Ca2+ removal pathways, myofibrillar biomechanics properties and action of the cardiotonic drug levosimendan - Wagner, Sören; Schürmann, Sebastian; Schüttler, Jürgen; Hein, S.; Friedrich, Oliver (Basic research in cardiology, 2015)
Cardiac dysfunction is a common complication in sepsis and is characterized by forward pump failure. Hallmarks of septic cardiomyopathy are decreased myofibrillar contractility and reduced Ca(2+) sensitivity but it is still not clear whether reduced pump efficiency is predominantly a diastolic impairment. Moreover, a comprehensive picture of upstream Ca(2+) handling mechanisms and downstream myosin biomechanical parameters is still missing. Ca(2+)-sensitizing agents in sepsis may be promising but mechanistic insights for drugs like levosimendan are scarce. Here, we used an endotoxemic LPS rat model to study mechanisms of sepsis on in vivo hemodynamics, multicellular myofibrillar Ca(2+) sensitivity, in vitro cellular Ca(2+) homeostasis and subcellular actomyosin interaction with intracardiac catheters, force transducers, confocal Fluo-4 Ca(2+) recordings in paced cardiomyocytes, and in vitro motility assay, respectively. Left ventricular ejection fraction and myofibrillar Ca(2+) sensitivity were depressed in LPS animals but restored by levosimendan. Diastolic Ca(2+) transient kinetics was slowed down by LPS but ameliorated by levosimendan. Selectively blocking intracellular and sarcolemmal Ca(2+) extrusion pathways revealed minor contribution of sarcoplasmic reticulum Ca(2+) ATPase (SERCA) to Ca(2+) transient diastole in LPS-evoked sepsis but rather depressed Na(+)/Ca(2+) exchanger and plasmalemmal Ca(2+) ATPase. This was mostly compensated by levosimendan. Actin sliding velocities were depressed in myosin heart extracts from LPS rats. We conclude that endotoxemia specifically impairs sarcolemmal diastolic Ca(2+) extrusion pathways resulting in intracellular diastolic Ca(2+) overload. Levosimendan, apart from stabilizing Ca(2+)-troponin C complexes, potently improves cellular Ca(2+) extrusion in the septic hear
Keywords: Sepsis; Cardiomyopathy; Levosimendan; Calcium; Motility assay

'Set the controls...' - phenotype matching beyond genetics in muscular dystrophy - Friedrich, Oliver (Experimental physiology, 2014)

Single fibre cytoarchitecture in ventilator-induced diaphragm dysfunction (VIDD) assessed by quantitative morphometry second harmonic generation imaging: Positive effects of BGP-15 chaperone co-inducer and VBP-15 dissociative corticosteroid treatment - Mnuskina, Sofia; Bauer, Julian; Wirth-Hücking, Anette; Schneidereit, Dominik; Nübler, Stefanie; Ritter, Paul; Cacciani, Nicola; Li, Meishan; Larsson, Lars; Friedrich, Oliver (Frontiers in Physiology, 2023)
Ventilator-induced diaphragm dysfunction (VIDD) is a common sequela of intensive care unit (ICU) treatment requiring mechanical ventilation (MV) and neuromuscular blockade (NMBA). It is characterised by diaphragm weakness, prolonged respirator weaning and adverse outcomes. Dissociative glucocorticoids (e.g., vamorolone, VBP-15) and chaperone co-inducers (e.g., BGP-15) previously showed positive effects in an ICU-rat model. In limb muscle critical illness myopathy, preferential myosin loss prevails, while myofibrillar protein post-translational modifications are more dominant in VIDD. It is not known whether the marked decline in specific force (force normalised to cross-sectional area) is a pure consequence of altered contractility signaling or whether diaphragm weakness also has a structural correlate through sterical remodeling of myofibrillar cytoarchitecture, how quickly it develops, and to which extent VBP-15 or BGP-15 may specifically recover myofibrillar geometry. To address these questions, we performed label-free multiphoton Second Harmonic Generation (SHG) imaging followed by quantitative morphometry in single diaphragm muscle fibres from healthy rats subjected to five or 10 days of MV + NMBA to simulate ICU treatment without underlying confounding pathology (like sepsis). Rats received daily treatment of either Prednisolone, VBP-15, BGP-15 or none. Myosin-II SHG signal intensities, fibre diameters (FD) as well as the parameters of myofibrillar angular parallelism (cosine angle sum, CAS) and in-register of adjacent myofibrils (Vernier density, VD) were computed from SHG images. ICU treatment caused a decline in FD at day 10 as well as a significant decline in CAS and VD from day 5. Vamorolone effectively recovered FD at day 10, while BGP-15 was more effective at day 5. BGP-15 was more effective than VBP-15 in recovering CAS at day 10 although not to control levels. In-register VD levels were restored at day 10 by both compounds. Our study is the first to provide quantitative insights into VIDD-related myofibrillar remodeling unravelled by SHG imaging, suggesting that both VBP-15 and BGP-15 can effectively ameliorate the structure-related dysfunction in VIDD.
CRIS-Team Scopus Importer:2023-08-25
Keywords: BGP-15; critical illness; diaphragm dysfunction; quantitative morphometry; second harmonic generation

Single muscle fibre biomechanics and biomechatronics – The challenges, the pitfalls and the future - Friedrich, Oliver; Haug, Michael; Reischl, Barbara; Prölß, Gerhard; Kiriaev, Leon; Head, Stewart I.; Reid, Michael B. (International Journal of Biochemistry and Cell Biology, 2019)
Interest in muscle biomechanics is growing with availabilities of patient biopsies and animal models related to muscle diseases, muscle wasting (sarcopenia, cachexia), exercise and drug effects. However, development of technologies or facilitated systems required to measure biomechanical and contractile properties of single fibres has not kept pace with this demand. Most studies use manual mechatronics systems that have not changed in decades and are confined to a few labs worldwide. Available commercial systems are expensive and limited in versatility, throughput and user-friendliness. We review major standard systems available from research labs and commercial sources, and benchmark those to our recently developed automated MyoRobot biomechatronics platform that provides versatility to cover multiple organ scales, is flexible in programming for active/passive muscle biomechanics using custom-made graphics user interfaces, employs on-the-fly data analyses and does not rely on external research microscopes. With higher throughput, this system blends Industry 4.0 automation principles into myology.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Biomechatronics; Biosensors; Myorobotics; Single fibre; Skeletal muscle

Size matters-in vitro behaviour of human fibroblasts on textured silicone surfaces with different pore sizes - Juia, Tolksdorf; Horch, Raymund E.; Grüner, Jasmin; Schmid, Rafael; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Werner, Siegfried; Schneidereit, Dominik; Friedrich, Oliver; Ludolph, Ingo (Journal of Materials Science: Materials in Medicine, 2020)
Capsular contracture remains a challenge in plastic surgery and represents one of the most common postoperative complications following alloplastic breast reconstruction. The impact of the surface structure of silicone implants on the foreign body reaction and the behaviour of connective tissue-producing cells has already been discussed. The aim of this study was to investigate different pore sizes of silicone surfaces and their influence on human fibroblasts in an in vitro model. Four different textures (no, fine, medium and coarse texture) produced with the salt-loss technique, have been assessed in an in vitro model. Human fibroblasts were seeded onto silicone sheets and evaluated after 1, 4 and 7 days microscopically, with viability assay and gene expression analysis. Comparing the growth behaviour and adhesion of the fibroblasts on the four different textures, a dense cell layer, good adhesion and bridge-building ability of the cells could be observed for the fine and medium texture. Cell number and viability of the cells were increasing during the time course of experiments on every texture. TGFß1 was lowest expressed on the fine and medium texture indicating a trend for decreased fibrotic activity. For silicone surfaces produced with the salt-loss technique, we were able to show an antifibrotic effect of smaller sized pores. These findings underline the hypothesis of a key role of the implant surface and the pore size and pore structure in preventing capsular contracture.<br
Keywords: Silicone Surface; hand surgery; implants; Biocompatibility Studies

Speed of shortening is not altered in the alpha-actinin-3 (ACTN3) 'gene of speed' knock-out mutation in fast-twitch skeletal muscle - Wagner, Sören; Chan, Stephen; Murphy, Robyn; Houweling, Peter; Quinlan, Kate; North, Kathryn; Head, Stewart; Friedrich, Oliver (Wiley-Blackwell, 2015)

Step-by-step guide to building an inexpensive 3D printed motorized positioning stage for automated high-content screening microscopy. - Gilbert, Daniel; Friedrich, Oliver; Schneidereit, Dominik; Meier, Jochen C; Kraus, Larissa (Biosensors and Bioelectronics, 2017)
High-content screening microscopy relies on automation infrastructure that is typically proprietary, non-customizable, costly and requires a high level of skill to use and maintain. The increasing availability of rapid prototyping technology makes it possible to quickly engineer alternatives to conventional automation infrastructure that are low-cost and user-friendly. Here, we describe a 3D printed inexpensive open source and scalable motorized positioning stage for automated high-content screening microscopy and provide detailed step-by-step instructions to re-building the device, including a comprehensive parts list, 3D design files in STEP (Standard for the Exchange of Product model data) and STL (Standard Tessellation Language) format, electronic circuits and wiring diagrams as well as software code. System assembly including 3D printing requires approx. 30h. The fully assembled device is light-weight (1.1kg), small (33×20×8cm) and extremely low-cost (approx. EUR 250). We describe positioning characteristics of the stage, including spatial resolution, accuracy and repeatability, compare imaging data generated with our device to data obtained using a commercially available microplate reader, demonstrate its suitability to high-content microscopy in 96-well high-throughput screening format and validate its applicability to automated functional Cl-- and Ca2+-imaging with recombinant HEK293 cells as a model system. A time-lapse video of the stage during operation and as part of a custom assembled screening robot can be found at https://vimeo.com/158813199.
Keywords: 3D desktop printing; Arduino; High-content screening; Cell viability; YFPI152L; Glycine receptor; TRPV1; Fluo-4 AM

"Store-operated" and P2X-induced Ca2+ entry are differentially modulated by the antibiotic minocycline in murine BV2 microglia cells - Friedrich, Oliver; Gilbert, Daniel; Buttgereit, Andreas; Künzel, Katharina; Watson, J.; Stebbing, Martin J.; Stokes, Leanne; Adams, David J. (Wiley-Blackwell, 2015)

Store-Operated Ca(2+) Entry (SOCE) and Purinergic Receptor-Mediated Ca(2+) Homeostasis in Murine bv2 Microglia Cells: Early Cellular Responses to ATP-Mediated Microglia Activation. - Gilbert, Daniel; Stebbing, Martin J.; Künzel, Katharina; Murphy, Robyn M.; Zacharewicz, Evelyn; Buttgereit, Andreas; Stokes, Leanne; Adams, David J.; Friedrich, Oliver (Frontiers in Molecular Neuroscience, 2016)
Microglia activation is a neuroinflammatory response to parenchymal damage with release of intracellular metabolites, e.g., purines, and signaling molecules from damaged cells. Extracellular purines can elicit Ca(2+)-mediated microglia activation involving P2X/P2Y receptors with metabotropic (P2Y) and ionotropic (P2X) cell signaling in target cells. Such microglia activation results in increased phagocytic activity, activation of their inflammasome and release of cytokines to sustain neuroinflammatory (so-called M1/M2 polarization). ATP-induced activation of ionotropic P2X4 and P2X7 receptors differentially induces receptor-operated Ca(2+) entry (ROCE). Although store-operated Ca(2+) entry (SOCE) was identified to modulate ROCE in primary microglia, its existence and role in one of the most common murine microglia cell line, BV2, is unknown. To dissect SOCE from ROCE in BV2 cells, we applied high-resolution multiphoton Ca(2+) imaging. After depleting internal Ca(2+) stores, SOCE was clearly detectable. High ATP concentrations (1 mM) elicited sustained increases in intracellular [Ca(2+)]i whereas lower concentrations (≤100 μM) also induced Ca(2+) oscillations. These differential responses were assigned to P2X7 and P2X4 activation, respectively. Pharmacologically inhibiting P2Y and P2X responses did not affect SOCE, and in fact, P2Y-responses were barely detectable in BV2 cells. STIM1S content was significantly upregulated by 1 mM ATP. As P2X-mediated Ca(2+) oscillations were rare events in single cells, we implemented a high-content screening approach that allows to record Ca(2+) signal patterns from a large number of individual cells at lower optical resolution. Using automated classifier analysis, several drugs (minocycline, U73122, U73343, wortmannin, LY294002, AZ10606120) were tested on their profile to act on Ca(2+) oscillations (P2X4) and sustained [Ca(2+)]i increases. We demonstrate specific drug effects on purinergic Ca(2+) pathways and provide new pharmacological insights into Ca(2+) oscillations in BV2 cells. For example, minocycline inhibits both P2X7- and P2X4-mediated Ca(2+)-responses, and this may explain its anti-inflammatory action in neuroinflammatory disease. As a technical result, our novel automated bio-screening approach provides a biomedical engineering platform to allow high-content drug library screens to study neuro-inflammation in vitro.

Stretch in Focus: 2D Inplane Cell Stretch Systems for Studies of Cardiac Mechano-Signaling - Friedrich, Oliver; Merten, Anna-Lena; Schneidereit, Dominik; Guo, Yang; Schürmann, Sebastian; Martinac, Boris (Frontiers in Bioengineering and Biotechnology, 2019)
Mechanobiology is a rapidly growing interdisciplinary research field, involving biophysics, molecular and cell biology, biomedical engineering, and medicine. Rapid progress has been possible due to emerging devices and tools engineered for studies of the effect of mechanical forces, such as stretch or shear force, impacting on biological cells and tissues. In response to such mechanical stimuli, cells possess various mechanosensors among which mechanosensitive ion channels are molecular transducers designed to convert mechanical stimuli into electrical and/or biochemical intracellular signals on millisecond time scales. To study their role in cellular signaling pathways, devices have been engineered that enable application of different strain protocols to cells allowing for determination of the stress-strain relationship or other, preferably optical, readouts. Frequently, these devices are mounted on fluorescence microscopes, allowing simultaneous investigation of cellular mechanotransduction processes combined with live-cell imaging. Mechanical stress in organs/tissues can be complex and multiaxial, e.g., in hollow organs, like lung alveoli, bladder, or the heart. Therefore, biomedical engineers have, in recent years, developed devices based on elastomeric membranes for application of biaxial or multiaxial stretch to 2D substrate-adhered or even 3D-embedded cells. Here, we review application of stretch technologies to cellular mechanotransduction with a focus on cardiovascular systems. We also present new results obtained by our IsoStretcher device to examine mechanosensitivity of adult ventricular cardiomyocytes. We show that sudden isotropic stretch of cardiomyocytes can already trigger arrhythmic Ca2+ transients on the single cell level.
CRIS-Team WoS Importer:2019-04-12

Structure-Function Relationships in Muscle Fibres: MyoRobot Online Assessment of Muscle Fibre Elasticity and Sarcomere Length Distributions - Haug, Michael; Ritter, Paul; Michael, Mena; Reischl, Barbara; Schürmann, Sebastian; Prölß, Gerhard; Friedrich, Oliver (IEEE Transactions on Biomedical Engineering, 2022)
Objective: Muscle biomechanics is set by the spacing of repetitive striation patterns of individual sarcomeres within single muscle fibres of stacked myofibrils. Sarcomere lengths (SL) are rather unequally distributed than of equal distance. This non-uniformity may affect both, force production as well as passive-elastic deformation. However, online recording of SL during axially imposed strains is cumbersome due to a lack of compact technologies. Methods: To fuse SL pattern recognition with restoration force assessments during quasi-static axial stretch, we implemented live tracking of SL distributions simultaneous to voice-coil actuated stretch and restoration force recordings in our MyoRobot 2.0 automated biomechatronics platform. Both were obtained online during stretch-relaxation cycles of murine single muscle fibres. Results: Under quasi-static stretch conditions (similar to 1 mu m/s fibre length changes), almost no apparent hysteresis was detected in single fibres. SL showed a non-uniform distribution. While mean SL varied between 2.6 mu m and 3.4 mu m upon 140% stretch, two populations of fibres were noticed: one showing a minor change in SL distribution with stretch, and one becoming more equally distributed upon stretch. Conclusion: A roughly 5% SL variability under rest either diminishes or remains almost unaltered upon elastic axial deformation. This may reflect differential impact of mostly extra-sarcomeric components to stretch in this stretch range. Significance: The augmented functionality of the MyoRobot 2.0 towards online sarcomere analyses within single fibres shall provide a valuable tool for the muscle community to study the contribution of serial elastic and force producing elements in health and disease models.
CRIS-Team WoS Importer:2022-01-07

Structure-related force deficit predicted by quantitative multiphoton microscopy of single skeletal muscle fibers from an animal model of human desminopathy - Diermeier, Stefanie; Buttgereit, Andreas; Winter, Lilli; Clemen, C. S.; Schröder, Rolf; Friedrich, Oliver (Wiley-Blackwell, 2015)

Synthesis of Artemisinin-Derived Dimers, Trimers and Dendrimers: Investigation of Their Antimalarial and Antiviral Activities Including Putative Mechanisms of Action - Fröhlich, Tony; Hahn, Friedrich; Belmudes, Lucid; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Coute, Yohann; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2018)
Generation of dimers, trimers and dendrimers of bioactive compounds is an approach that has recently been developed for the discovery of new potent drug candidates. Herein, we present the synthesis of new artemisinin-derived dimers and dendrimers and investigate their action against malaria parasite Plasmodium falciparum 3D7 strain and human cytomegalovirus (HCMV). Dimer 7 was the most active compound (EC50 1.4 nm) in terms of antimalarial efficacy and was even more effective than the standard drugs dihydroartemisinin (EC50 2.4 nm), artesunic acid (EC50 8.9 nm) and chloroquine (EC50 9.8 nm). Trimer 4 stood out as the most active agent against HCMV in vitro replication and exerted an EC50 value of 0.026 mu m, representing an even higher activity than the two reference drugs ganciclovir (EC50 2.60 mu m) and artesunic acid (EC50 5.41 mu m). In addition, artemisinin-derived dimer 13 and trimer 15 were for the first time both immobilized on TOYOPEARL AF-Amino-650M beads and used for mass spectrometry-based target identification experiments using total lysates of HCMV-infected primary human fibroblasts. Two major groups of novel target candidates, namely cytoskeletal and mitochondrial proteins were obtained. Two putatively compound-binding viral proteins, namely major capsid protein (MCP) and envelope glycoprotein pUL132, which are both essential for HCMV replication, were identified.
EVALuna2:35275

Synthesis of Artemisinin-Estrogen Hybrids Highly Active against HCMV, P-falciparum, and Cervical and Breast Cancer - Fröhlich, Tony; Kiss, Anita; Wolfling, Janos; Mernyak, Erzsebet; Kulmany, Agnes E.; Minorics, Renata; Zupko, Istvan; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Hahn, Friedrich; Marschall, Manfred; et al. (ACS Medicinal Chemistry Letters, 2018)
Artemisinin-estrogen hybrids were for the first time both synthesized and investigated for their in vitro biological activity against malaria parasites (Plasmodium falciparum 3D7), human cytomegalovirus (HCMV), and a panel of human malignant cells of gynecological origin containing breast (MCF7, MDA-MB-231, MDA-MB-361, T47D) and cervical tumor cell lines (HeLa, SiHa, C33A). In terms of antimalarial efficacy, hybrid 8 (EC50 = 3.8 nM) was about two times more active than its parent compound artesunic acid (7) (EC50 = 8.9 nM) as well as the standard drug chloroquine (EC50 = 9.8 nM) and was, therefore, comparable to the clinically used dihydroartemisinin (6) (EC50 = 2.4 nM). Furthermore, hybrids 9-12 showed a strong antiviral effect with EC50 values in the submicromolar range (0.22-0.38 mu M) and thus possess profoundly stronger anti-HCMV activity (approximately factor 25) than the parent compound artesunic acid (7) (EC50 = 5.41 mu M). These compounds also exerted a higher in vitro anti-HCMV efficacy than ganciclovir used as the standard of current antiviral treatment. In addition, hybrids 8-12 elicited substantially more pronounced growth inhibiting action on all cancer cell lines than their parent compounds and the reference drug cisplatin. The most potent agent, hybrid 12, exhibited submicromolar EC50 values (0.15-0.93 mu M) against breast cancer and C33A cell lines.
EVALuna2:35262

Synthesis of new betulinic acid/betulin-derived dimers and hybrids with potent antimalarial and antiviral activities - Capci Karagöz, Aysun; Leidenberger, Maria; Hahn, Friedrich; Friedrich, Oliver; Hampel, Frank; Marschall, Manfred; Kappes, Bärbel; Tsogoeva, Svetlana (Bioorganic & Medicinal Chemistry, 2019)
Severe malaria and viral infections cause life-threatening diseases in millions of people worldwide every year. In search for effective bioactive hybrid molecules, which may possess improved properties compared to their parent compounds, a series of betulinic acid/betulin based dimer and hybrid compounds carrying ferrocene and/or artesunic acid moieties, was designed and, synthesized de novo. Furthermore, they were analyzed in vitro against malaria parasites (growth inhibition of 3D7-strain P. falciparum-infected erythrocytes) and human cytomegalovirus (HCMV). From this series of hybrids/dimers, the betulinic acid/betulin and artesunic acid hybrids 11 and 12 showed the most potent activities against P. falciparum and HCMV. On the strength of results, additive and/or synergistic effects between the natural or semisynthetic products, such as betulinic acid-/betulin- and artesunic acid-derived compounds, are suggested on the basis of putatively complex modes of antimicrobial action. This advantage may be taken into account in future drug development.
Keywords: Betulin; Betulinic acid; Artesunic acid; Ferrocene; Natural product hybrid; Antimalarial activity; Antiviral activity

Synthesis of Novel Hybrids of Quinazoline and Artemisinin with High Activities against Plasmodium falciparum, Human Cytomegalovirus, and Leukemia Cells - Fröhlich, Tony; Reiter, Christoph; Ibrahim, Mohammad M.; Beutel, Jannis; Hutterer, Corina; Zeitträger, Isabel; Bahsi, Hanife; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Efferth, Thomas; Marschall, Manfred; et al. (ACS Omega, 2017)
Many quinazoline derivatives have been synthesized over the last few decades with great pharmacological potential, such as antimalarial, anti-inflammatory, antimicrobial, anticancer, and antiviral. But so far, no quinazoline-artemisinin hybrids have been reported in the literature. In the present study, five novel quinazoline-artemisinin hybrids were synthesized and evaluated for their in vitro biological activity against malarial parasites (Plasmodium falciparum 3D7), leukemia cells (CCRF-CEM and CEM/ADR5000), and human cytomegalovirus. Remarkably, hybrid 9 (EC50 = 1.4 nM), the most active antimalarial compound of this study, was not only more potent than artesunic acid (EC50 = 9.7 nM) but at the same time more active than the clinically used drugs dihydroartemisinin (EC50 = 2.4 nM) and chloroquine (EC50 = 9.8 nM). Furthermore, hybrids 9 and 10 were the most potent compounds with regard to anticytomegaloviral activity (EC50 = 0.15-0.21 μM). They were able to outperform ganciclovir (EC50 = 2.6 μM), which is the relevant standard drug of antiviral therapy, by a factor of 12-17. Moreover, we identified a new highly active quinazoline derivative, compound 14, that is most effective in suppressing cytomegalovirus replication with an EC50 value in the nanomolar range (EC50 = 50 nM). In addition, hybrid 9 exhibited an antileukemia effect similar to that of artesunic acid, with EC50 values in the low micromolar range, and was 45 times more active toward the multidrug-resistant CEM/ADR5000 cells (EC50 = 0.5 μM) than the standard drug doxorubicin.
EVALuna2:35475

Synthesis of Tamoxifen-Artemisinin and Estrogen-Artemisinin Hybrids Highly Potent Against Breast and Prostate Cancer - Fröhlich, Tony; Mai, Christina; Bogautdinov, Roman P.; Morozkina, Svetlana N.; Shavva, Alexander G.; Friedrich, Oliver; Gilbert, Daniel; Tsogoeva, Svetlana (ChemMedChem, 2020)
In the search for new and effective treatments of breast and prostate cancer, a series of hybrid compounds based on tamoxifen, estrogens, and artemisinin were successfully synthesized and analyzed for their in vitro activities against human prostate (PC-3) and breast cancer (MCF-7) cell lines. Most of the hybrid compounds exhibit a strong anticancer activity against both cancer cell lines – for example, EC50 (PC-3) down to 1.07 μM, and EC50 (MCF-7) down to 2.08 μM – thus showing higher activities than their parent compounds 4-hydroxytamoxifen (afimoxifene, 7; EC50=75.1 (PC-3) and 19.3 μM (MCF-7)), dihydroartemisinin (2; EC50=263.6 (PC-3) and 49.3 μM (MCF-7)), and artesunic acid (3; EC50=195.1 (PC-3) and 32.0 μM (MCF-7)). The most potent compounds were the estrogen-artemisinin hybrids 27 and 28 (EC50=1.18 and 1.07 μM, respectively) against prostate cancer, and hybrid 23 (EC50=2.08 μM) against breast cancer. These findings demonstrate the high potential of hybridization of artemisinin and estrogens to further improve their anticancer activities and to produce synergistic effects between linked pharmacophores.
CRIS-Team Scopus Importer:2020-07-10
Keywords: antitumor agents; artemisinin; breast cancer; estrogen; hybrids; prostate cancer; tamoxifen

Synthesis of Thymoquinone-Artemisinin Hybrids: New Potent Antileukemia, Antiviral, and Antimalarial Agents - Fröhlich, Tony; Reiter, Christoph; Saeed, Mohamed E. M.; Hutterer, Corina; Hahn, Friedrich; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Marschall, Manfred; Efferth, Thomas; Tsogoeva, Svetlana (ACS Medicinal Chemistry Letters, 2018)
A series of hybrid compounds based on the natural products artemisinin and thymoquinone was synthesized and investigated for their biological activity against the malaria parasite Plasmodium falciparum 3D7 strain, human cytomegalovirus (HCMV), and two leukemia cell lines (drug sensitive CCRF-CEM and multidrug-resistant subline CEM/ADR5000). An unprecedented one-pot method of selective formation of C-10 alpha-acetate 14 starting from a 1:1 mixture of C-10 alpha- to C-10 beta-dihydroartemisinin was developed. The key step of this facile method is a mild decarboxylative activation of malonic acid mediated by DCC/DMAP. Ether-linked thymoquinone artemisinin hybrids 6a/b stood out as the most active compounds in all categories, while showing no toxic side effects toward healthy human foreskin fibroblasts and thus being selective. They exhibited EC50 values of 0.2 mu M against the doxorubicin-sensitive as well as the multidrug-resistant leukemia cells and therefore can be regarded as superior to doxorubicin. Moreover, they showed to be five times more active than the standard drug ganciclovir and nearly eight times more active than artesunic acid against HCMV. In addition, hybrids 6a/b possessed excellent antimalarial activity (EC50 = 5.9/3.7 nM), which was better than that of artesunic acid (EC50 = 8.2 nM) and chloroquine (EC50 = 9.8 nM). Overall, most of the presented thymoquinone artemisinin-based hybrids exhibit an excellent and broad variety of biological activities (anticancer, antimalarial, and antiviral) combined with a low toxicity/high selectivity profile.
EVALuna2:35278

Taking a deep look: modern microscopy technologies to optimize the design and functionality of biocompatible scaffolds for tissue engineering in regenerative medicine - Vielreicher, Martin; Schürmann, Sebastian; Detsch, Rainer; Schmidt, Miriam; Buttgereit, Andreas; Boccaccini, Aldo R.; Friedrich, Oliver (Journal of the Royal Society Interface, 2013)
This review focuses on modern nonlinear optical microscopy (NLOM) methods that are increasingly being used in the field of tissue engineering (TE) to image tissue non-invasively and without labelling in depths unreached by conventional microscopy techniques. With NLOM techniques, biomaterial matrices, cultured cells and their produced extracellular matrix may be visualized with high resolution. After introducing classical imaging methodologies such as mCT, MRI, optical coherence tomography, electron microscopy and conventional microscopy two-photon fluorescence (2-PF) and second harmonic generation (SHG) imaging are described in detail (principle, power, limitations) together with their most widely used TE applications. Besides our own cell encapsulation, cell printing and collagen scaffolding systems and their NLOM imaging the most current research articles will be reviewed. These cover imaging of autofluorescence and fluorescence-labelled tissue and biomaterial structures, SHG-based quantitative morphometry of collagen I and other proteins, imaging of vascularization and online monitoring techniques in TE. Finally, some insight is given into state-of-the-art three-photon-based imaging methods (e.g. coherent anti-Stokes Raman scattering, third harmonic generation). This review provides an overview of the powerful and constantly evolving field of multiphoton microscopy, which is a powerful and indispensable tool for the development of artificial tissues in regenerative medicine and which is likely to gain importance also as a means for general diagnostic medical imaging. © 2013 The Author(s).
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.taking
Keywords: Artificial tissues; Autofluorescence; Biomaterials; Extracellular matrix; Multiphoton imaging; Second harmonic generation

Tensorial tomographic Fourier ptychography with applications to muscle tissue imaging - Xu, Shiqi; Yang, Xi; Ritter, Paul; Dai, Xiang; Lee, Kyung Chul; Kreiß, Lucas; Zhou, Kevin C.; Kim, Kanghyun; Chaware, Amey; Neff, Jadee; Glass, Carolyn; Lee, Seung Ah; et al. (Advanced Photonics, 2024)
We report tensorial tomographic Fourier ptychography (T2oFu), a nonscanning label-free tomographic microscopy method for simultaneous imaging of quantitative phase and anisotropic specimen information in 3D. Built upon Fourier ptychography, a quantitative phase imaging technique, T2oFu additionally highlights the vectorial nature of light. The imaging setup consists of a standard microscope equipped with an LED matrix, a polarization generator, and a polarization-sensitive camera. Permittivity tensors of anisotropic samples are computationally recovered from polarized intensity measurements across three dimensions. We demonstrate T2oFu’s efficiency through volumetric reconstructions of refractive index, birefringence, and orientation for various validation samples, as well as tissue samples from muscle fibers and diseased heart tissue. Our reconstructions of healthy muscle fibers reveal their 3D fine-filament structures with consistent orientations. Additionally, we demonstrate reconstructions of a heart tissue sample that carries important polarization information for detecting cardiac amyloidosis.
CRIS-Team Scopus Importer:2024-05-24
Keywords: computational imaging; label-free imaging; phase retrieval microscopy; polarization-sensitive imaging; three-dimensional imaging

The desmin mutation R349P increases contractility and fragility of stem cell-generated muscle micro-tissues - Spörrer, Marina; Kah, Delf-Thorge Eric; Gerum, Richard; Reischl, Barbara; Huraskin, Danyil; Dessalles, Claire A.; Schneider, Werner; Goldmann, Wolfgang; Herrmann, Harald; Thievessen, Ingo; Clemen, Christoph S.; Friedrich, Oliver; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims: Desminopathies comprise hereditary myopathies and cardiomyopathies caused by mutations in the intermediate filament protein desmin that lead to severe and often lethal degeneration of striated muscle tissue. Animal and single cell studies hinted that this degeneration process is associated with massive ultrastructural defects correlating with increased susceptibility of the muscle to acute mechanical stress. The underlying mechanism of mechanical susceptibility, and how muscle degeneration develops over time, however, has remained elusive. Methods: Here, we investigated the effect of a desmin mutation on the formation, differentiation, and contractile function of in vitro-engineered three-dimensional micro-tissues grown from muscle stem cells (satellite cells) isolated from heterozygous R349P desmin knock-in mice. Results: Micro-tissues grown from desmin-mutated cells exhibited spontaneous unsynchronised contractions, higher contractile forces in response to electrical stimulation, and faster force recovery compared with tissues grown from wild-type cells. Within 1 week of culture, the majority of R349P desmin-mutated tissues disintegrated, whereas wild-type tissues remained intact over at least three weeks. Moreover, under tetanic stimulation lasting less than 5 s, desmin-mutated tissues partially or completely ruptured, whereas wild-type tissues did not display signs of damage. Conclusions: Our results demonstrate that the progressive degeneration of desmin-mutated micro-tissues is closely linked to extracellular matrix fibre breakage associated with increased contractile forces and unevenly distributed tensile stress. This suggests that the age-related degeneration of skeletal and cardiac muscle in patients suffering from desminopathies may be similarly exacerbated by mechanical damage from high-intensity muscle contractions. We conclude that micro-tissues may provide a valuable tool for studying the organization of myocytes and the pathogenic mechanisms of myopathies.
CRIS-Team Scopus Importer:2021-12-17
Keywords: desmin; desminopathy; micro-tissue; skeletal muscle physiology; tissue engineering

The heart in Duchenne muscular dystrophy: early detection of contractile performance alteration. - Wagner, Sören; Knipp, Stephan; Weber, Cornelia; Hein, Selina; Schinkel, Stefanie; Walther, Andreas; Bekeredjian, Raffi; Müller, Oliver J.; Friedrich, Oliver (Journal of cellular and molecular medicine, 2012)
Progressive cardiomyopathy is a major cause of death in Duchenne muscular dystrophy (DMD) patients. Coupling between Ca(2+) handling and contractile properties in dystrophic hearts is poorly understood. It is also not clear whether developing cardiac failure is dominated by alterations in Ca(2+) pathways or more related to the contractile apparatus. We simultaneously recorded force and Ca(2+) transients in field-stimulated papillary muscles from young (10-14 weeks) wild-type (wt) and dystrophic mdx mice. Force amplitudes were fivefold reduced in mdx muscles despite only 30% reduction in fura-2 ratio amplitudes. This indicated mechanisms other than systolic Ca(2+) to additionally account for force decrements in mdx muscles. pCa-force relations revealed decreased mdx myofibrillar Ca(2+) sensitivity. 'In vitro' motility assays, studied in mdx hearts here for the first time, showed significantly slower sliding velocities. mdx MLC/MHC isoforms were not grossly altered. Dystrophic hearts showed echocardiography signs of early ventricular wall hypertrophy with a significantly enlarged end-diastolic diameter 'in vivo'. However, fractional shortening was still comparable to wt mice. Changes in the contractile apparatus satisfactorily explained force drop in mdx hearts. We give first evidence of early hypertrophy in mdx mice and possible mechanisms for already functional impairment of cardiac muscle in DMD.
Keywords: papillary muscle; muscular dystrophy; calcium; force transients; motility assay

The inotropic peptide βARKct improves βAR responsiveness in normal and failing cardiomyocytes through G(βγ)-mediated L-type calcium current disinhibition. - Völkers, Mirko; Weidenhammer, Christian; Herzog, Nicole; Qiu, Gang; Spaich, Kristin; von Wegner, Frederic; Peppel, Karsten; Müller, Oliver J.; Schinkel, Stefanie; Rabinowitz, Joseph E.; Hippe, Hans-Jörg; Brinks, Henriette; et al. (Circulation Research, 2011)
RATIONALE The G(βγ)-sequestering peptide β-adrenergic receptor kinase (βARK)ct derived from the G-protein-coupled receptor kinase (GRK)2 carboxyl terminus has emerged as a promising target for gene-based heart failure therapy. Enhanced downstream cAMP signaling has been proposed as the underlying mechanism for increased β-adrenergic receptor (βAR) responsiveness. However, molecular targets mediating improved cardiac contractile performance by βARKct and its impact on G(βγ)-mediated signaling have yet to be fully elucidated. OBJECTIVE We sought to identify G(βγ)-regulated targets and signaling mechanisms conveying βARKct-mediated enhanced βAR responsiveness in normal (NC) and failing (FC) adult rat ventricular cardiomyocytes. METHODS AND RESULTS Assessing viral-based βARKct gene delivery with electrophysiological techniques, analysis of contractile performance, subcellular Ca²(+) handling, and site-specific protein phosphorylation, we demonstrate that βARKct enhances the cardiac L-type Ca²(+) channel (LCC) current (I(Ca)) both in NCs and FCs on βAR stimulation. Mechanistically, βARKct augments I(Ca) by preventing enhanced inhibitory interaction between the α1-LCC subunit (Cav1.2α) and liberated G(βγ) subunits downstream of activated βARs. Despite improved βAR contractile responsiveness, βARKct neither increased nor restored cAMP-dependent protein kinase (PKA) and calmodulin-dependent kinase II signaling including unchanged protein kinase (PK)Cε, extracellular signal-regulated kinase (ERK)1/2, Akt, ERK5, and p38 activation both in NCs and FCs. Accordingly, although βARKct significantly increases I(Ca) and Ca²(+) transients, being susceptible to suppression by recombinant G(βγ) protein and use-dependent LCC blocker, βARKct-expressing cardiomyocytes exhibit equal basal and βAR-stimulated sarcoplasmic reticulum Ca²(+) load, spontaneous diastolic Ca²(+) leakage, and survival rates and were less susceptible to field-stimulated Ca²(+) waves compared with controls. CONCLUSION Our study identifies a G(βγ)-dependent signaling pathway attenuating cardiomyocyte I(Ca) on βAR as molecular target for the G(βγ)-sequestering peptide βARKct. Targeted interruption of this inhibitory signaling pathway by βARKct confers improved βAR contractile responsiveness through increased I(Ca) without enhancing regular or restoring abnormal cAMP-signaling. βARKct-mediated improvement of I(Ca) rendered cardiomyocytes neither susceptible to βAR-induced damage nor arrhythmogenic sarcoplasmic reticulum Ca²(+) leakage.
Keywords: βARKct; β-adrenergic receptor; L-type Ca2+ channel; G proteins

The IsoStretcher: An isotropic cell stretch device to study mechanical biosensor pathways in living cells. - Schürmann, Sebastian; Wagner, Sören; Herlitze, Simon; Fischer, C.; Gumbrecht, S.; Wirth-Hücking, Anette; Prölß, Gerhard; Lautscham, Lena; Fabry, Ben; Goldmann, Wolfgang; Nikolova-Krstevski, V.; Martinac, B.; et al. (Biosensors and Bioelectronics, 2016)
Mechanosensation in many organs (e.g. lungs, heart, gut) is mediated by biosensors (like mechanosensitive ion channels), which convert mechanical stimuli into electrical and/or biochemical signals. To study those pathways, technical devices are needed that apply strain profiles to cells, and ideally allow simultaneous live-cell microscopy analysis. Strain profiles in organs can be complex and multiaxial, e.g. in hollow organs. Most devices in mechanobiology apply longitudinal uniaxial stretch to adhered cells using elastomeric membranes to study mechanical biosensors. Recent approaches in biomedical engineering have employed intelligent systems to apply biaxial or multiaxial stretch to cells. Here, we present an isotropic cell stretch system (IsoStretcher) that overcomes some previous limitations. Our system uses a rotational swivel mechanism that translates into a radial displacement of hooks attached to small circular silicone membranes. Isotropicity and focus stability are demonstrated with fluorescent beads, and transmission efficiency of elastomer membrane stretch to cellular area change in HeLa/HEK cells. Applying our system to lamin-A overexpressing fibrosarcoma cells, we found a markedly reduced stretch of cell area, indicative of a stiffer cytoskeleton. We also investigated stretch-activated Ca(2+) entry into atrial HL-1 myocytes. 10% isotropic stretch induced robust oscillating increases in intracellular Fluo-4 Ca(2+) fluorescence. Store-operated Ca(2+) entry was not detected in these cells. The Isostretcher provides a useful versatile tool for mechanobiolog

The MyoRobot: A novel automated biomechatronics system to assess voltage/Ca2+ biosensors and active/passive biomechanics in muscle and biomaterials - Haug, Michael; Reischl, Barbara; Prölß, Gerhard; Pollmann, Charlotte; Buckert, Thomas; Keidel, Christian; Schürmann, Sebastian; Hock, Magdalena; Rupitsch, Stefan; Heckel, Michael; Pöschel, Thorsten; Scheibel, T; et al. (Biosensors and Bioelectronics, 2018)
We engineered an automated biomechatronics system, MyoRobot, for robust objective and versatile assessment of muscle or polymer materials (bio-)mechanics. It covers multiple levels of muscle biosensor assessment, e.g. membrane voltage or contractile apparatus Ca2+ ion responses (force resolution 1 µN, 0–10 mN for the given sensor; [Ca2+] range 100 nM–25 µM). It replaces previously tedious manual protocols to obtain exhaustive information on active/passive biomechanical properties across various morphological tissue levels. Deciphering mechanisms of muscle weakness requires sophisticated force protocols, dissecting contributions from altered Ca2+ homeostasis, electro-chemical, chemico-mechanical biosensors or visco-elastic components. From whole organ to single fibre levels, experimental demands and hardware requirements increase, limiting biomechanics research potential, as reflected by only few commercial biomechatronics systems that can address resolution, experimental versatility and mostly, automation of force recordings. Our MyoRobot combines optical force transducer technology with high precision 3D actuation (e.g. voice coil, 1 µm encoder resolution; stepper motors, 4 µm feed motion), and customized control software, enabling modular experimentation packages and automated data pre-analysis. In small bundles and single muscle fibres, we demonstrate automated recordings of (i) caffeine-induced-, (ii) electrical field stimulation (EFS)-induced force, (iii) pCa-force, (iv) slack-tests and (v) passive length-tension curves. The system easily reproduces results from manual systems (two times larger stiffness in slow over fast muscle) and provides novel insights into unloaded shortening velocities (declining with increasing slack lengths). The MyoRobot enables automated complex biomechanics assessment in muscle research. Applications also extend to material sciences, exemplarily shown here for spider silk and collagen biopolymer

The MyoRobot technology discloses a premature biomechanical decay of skeletal muscle fiber bundles derived from R349P desminopathy mice - Haug, Michael; Meyer, Charlotte; Reischl, Barbara; Prölß, Gerhard; Vetter, Karoline; Iberl, Julian; Nübler, Stefanie; Schürmann, Sebastian; Rupitsch, Stefan; Heckel, Michael; Pöschel, Thorsten; Winter, Lilli; et al. (Scientific Reports, 2019)
Mutations in the Des gene coding for the muscle-specific intermediate filament protein desmin lead to myopathies and cardiomyopathies. We previously generated a R349P desmin knock-in mouse strain as a patient-mimicking model for the corresponding most frequent human desmin mutation R350P. Since nothing is known about the age-dependent changes in the biomechanics of affected muscles, we investigated the passive and active biomechanics of small fiber bundles from young (17–23 wks), adult (25–45 wks) and aged (>60 wks) heterozygous and homozygous R349P desmin knock-in mice in comparison to wild-type littermates. We used a novel automated biomechatronics platform, the MyoRobot, to perform coherent quantitative recordings of passive (resting length-tension curves, visco-elasticity) and active (caffeine-induced force transients, pCa-force, ‘slack-tests’) parameters to determine age-dependent effects of the R349P desmin mutation in slow-twitch soleus and fast-twitch extensor digitorum longus small fiber bundles. We demonstrate that active force properties are not affected by this mutation while passive steady-state elasticity is vastly altered in R349P desmin fiber bundles compatible with a pre-aged phenotype exhibiting stiffer muscle preparations. Visco-elasticity on the other hand, was not altered. Our study represents the first systematic age-related characterization of small muscle fiber bundle preparation biomechanics in conjunction with inherited desminopathy.
CRIS-Team Scopus Importer:2019-08-02

The sick and the weak: Neuropathies/ myopathies in the critically ill - Friedrich, Oliver; Reid, Michael; van den Berghe, Greet; Vanhorebeek, Ilse; Hermans, Greet; Rich, Mark Monroe; Larsson, Lars (Physiological Reviews, 2015)
Critical illness polyneuropathies (CIP) and myopathies (CIM) are common complications of critical illness. Several weakness syndromes are summarized under the term intensive care unit-acquired weakness (ICUAW). We propose a classification of different ICUAW forms (CIM, CIP, sepsis-induced, steroid-denervation myopathy) and pathophysiological mechanisms from clinical and animal model data. Triggers include sepsis, mechanical ventilation, muscle unloading, steroid treatment, or denervation. Some ICUAW forms require stringent diagnostic features; CIM is marked by membrane hypoexcitability, severe atrophy, preferential myosin loss, ultrastructural alterations, and inadequate autophagy activation while myopathies in pure sepsis do not reproduce marked myosin loss. Reduced membrane excitability results from depolarization and ion channel dysfunction. Mitochondrial dysfunction contributes to energy-dependent processes. Ubiquitin proteasome and calpain activation trigger muscle proteolysis and atrophy while protein synthesis is impaired. Myosin loss is more pronounced than actin loss in CIM. Protein quality control is altered by inadequate autophagy. Ca(2+) dysregulation is present through altered Ca(2+) homeostasis. We highlight clinical hallmarks, trigger factors, and potential mechanisms from human studies and animal models that allow separation of risk factors that may trigger distinct mechanisms contributing to weakness. During critical illness, altered inflammatory (cytokines) and metabolic pathways deteriorate muscle function. ICUAW prevention/treatment is limited, e.g., tight glycemic control, delaying nutrition, and early mobilization. Future challenges include identification of primary/secondary events during the time course of critical illness, the interplay between membrane excitability, bioenergetic failure and differential proteolysis, and finding new therapeutic targets by help of tailored animal models.

The toxic effect of R350P mutant desmin in striated muscle of man and mouse. - Clemen, Christoph; Stöckigt, Florian; Strucksberg, Karl-Heinz; Chevessier, Frederic; Winter, Lilli; Schütz, Johanna; Bauer, Ralf; Thorweihe, José-Manuel; Wenzel, Daniela; Schlötzer-Schrehardt, Ursula; Rasche, Volker; Krsmanovic, Pavle; et al. (Acta Neuropathologica, 2015)
Mutations of the human desmin gene on chromosome 2q35 cause autosomal dominant, autosomal recessive and sporadic forms of protein aggregation myopathies and cardiomyopathies. We generated R349P desmin knock-in mice, which harbor the ortholog of the most frequently occurring human desmin missense mutation R350P. These mice develop age-dependent desmin-positive protein aggregation pathology, skeletal muscle weakness, dilated cardiomyopathy, as well as cardiac arrhythmias and conduction defects. For the first time, we report the expression level and subcellular distribution of mutant versus wild-type desmin in our mouse model as well as in skeletal muscle specimens derived from human R350P desminopathies. Furthermore, we demonstrate that the missense-mutant desmin inflicts changes of the subcellular localization and turnover of desmin itself and of direct desmin-binding partners. Our findings unveil a novel principle of pathogenesis, in which not the presence of protein aggregates, but disruption of the extrasarcomeric intermediate filament network leads to increased mechanical vulnerability of muscle fibers. These structural defects elicited at the myofiber level finally impact the entire organ and subsequently cause myopathy and cardiomyopathy.
Keywords: Desminopathy; R350P desmin missense mutation; Desmin knock-in mouse; Mouse model; Mutant desmin; Intermediate filament; Extrasarcomeric intermediate filament network; Mechanical vulnerability; Protein aggregation myopathy; Skeletal muscle weakness; Protein aggregation cardiomyopathy; Cardiac arrhythmia; Cardiac conduction defect

The toxic effects of s(+)-ketamine on differentiating neurons in vitro as a consequence of suppressed neuronal Ca2+ oscillations. - Sinner, Barbara; Friedrich, Oliver; Zink, Wolfgang; Zausig, York; Graf, Bernhard (Anesthesia and analgesia, 2011)
BACKGROUND In the immature brain, neuronal Ca2+ oscillations are present during a time period of high plasticity and regulate neuronal differentiation and synaptogenesis. In this study we examined the long-term blockade of hippocampal Ca2+ oscillations, the role of the N-methyl-D-aspartate (NMDA) receptors and the effects of S(+)-ketamine on neuronal synapsin expression. METHODS Hippocampal neurons were incubated at day 15 in culture with the specific NMDA receptor antagonists dizocilpine (MK 801, 100 μM) or S(+)-ketamine (3 μM to 25 μM) for 24 hours. Terminal-deoxynucleotidyl-transferase (TUNEL) and activated caspase3 were used to detect apoptotic neurons. Ca2+ oscillations were detected after loading the neurons with the Ca2+-sensitive dye fura-2AM, and dual wavelength excitation fluorescence microscopy was performed. Ca2+/calmodulin kinase II (CaMKII) was measured using Western blots. Synapsin was identified with confocal antisynapsin immunofluorescence. RESULTS Blocking the NMDA receptor with MK 801 or 25 μM S(+)-ketamine resulted in a significant increase in apoptotic neurons. MK 801 led to a significant increase in cytosolic Ca2+ concentration and reduction of the amplitude and frequency of the Ca2+ oscillations. Similar to MK 801, the long-term application of S(+)-ketamine resulted in a significant increase in cytosolic Ca2+ concentration 24 hours after washout. This was associated with a down-regulation of the CaMKII and a reduction of the synapsin 24 hours after washout. CONCLUSION Neuronal Ca2+ oscillations mediate neuronal differentiation and synaptogenesis via activating CaMKII. By acting via the NMDA receptor, S(+)-ketamine exerts its toxic effect through the suppression of neuronal Ca2+ oscillations, down-regulation of the CaMKII, and consecutively reduced synaptic integrity.

Tissue imaging with 2-photon microscopy - Vielreicher, Martin; Schürmann, Sebastian; Detsch, Rainer; Boccaccini, Aldo R.; Arkudas, Andreas; Friedrich, Oliver (BioNanoMaterials, 2013)

Tissue Viability of Free Flaps after Extracorporeal Perfusion Using a Modified Hydroxyethyl Starch Solution - Taeger, Christian D.; Friedrich, Oliver; Horch, Raymund E.; Distler, Caroline; Kengelbach-Weigand, Annika; Wenzel, Carina; Prantl, Lukas; Präbst, Konstantin (Journal of Clinical Medicine, 2020)
Background: In free flap surgery, tissue is stored under hypothermic ischemia. Extracorporeal perfusion (EP) has the potential to extend storage time and the tissue's perspective of survival. In the present study, the aim is to improve a recently established, simplified extracorporeal perfusion system. Methods: Porcine musculus rectus abdominis were stored under different conditions. One group was perfused continuously with a simplified one-way perfusion system for six hours, while the other received only a single flush but no further treatment. A modified hydroxyethyl starch solution was used as a perfusion and flushing solution. Vitality, functionality, and metabolic activity of both groups were analyzed. Results: Perfused muscles, in contrast to the ischemically stored ones, showed no loss of vitality and significantly less functionality loss, confirming the superiority of storage under continuous perfusion over ischemic storage. Furthermore, in comparison to a previous study, the results were improved even further by using a modified hydroxyethyl starch solution. Conclusion: The use of EP has major benefits compared to the clinical standard static storage at room temperature. Continuous perfusion not only maintains the oxygen and nutrient supply but also removes toxic metabolites formed due to inadequate storage conditions.
CRIS-Team WoS Importer:2021-01-08

Towards in vitro DT/DNT testing: Assaying chemical susceptibility in early differentiating NT2 cells. - Menzner, Ann-Katrin; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Toxicology, 2015)
Human pluripotent embryonal carcinoma (NT2) cells are increasingly considered as a suitable model for in vitro toxicity testing, e.g. developmental toxicity and neurotoxicity (DT/DNT) studies, as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and permit toxicity testing at different stages of maturation. NT2 cells have recently been reported to show specific changes in dielectric resistance profiles during differentiation which can be observed as early as 24 h upon RA-stimulation. These observations suggest altered susceptibility to chemicals at an early stage of differentiation. However, chemical susceptibility of early differentiating NT cells has not yet been studied. To address this question, we have established a cell fitness screening assay based on the analysis of intracellular ATP levels and we applied the assay in a large-scale drug screening experiment in NT2 stem cells and early differentiating NT2 cells. Subsequent analysis of ranked fitness phenotypes revealed 19 chemicals with differential toxicity profile in early differentiating NT2 cells. To evaluate whether any of the identified drugs have previously been associated with DT/DNT, we conducted a literature search on the identified molecules and quantified the fraction of chemicals assigned to the FDA (Food and Drug Administration) pregnancy risk categories (PRC) N, A, B, C, D, and X in the hit list and the small molecule library. While the fractions of the categories N and B were decreased (0.81 and 0.35-fold), the classes C, D and X were increased (1.35, 1.47 and 3.27-fold) in the hit list compared to the chemical library. From these data as well as from the literature review, identifying large fractions of chemicals being directly (42%) and indirectly associated with DT/DNT (32%), we conclude that our method may be beneficial to systematic in vitro-based primary screening for developmental toxicants and neurotoxicants and we propose cell fitness screening in early differentiating NT2 cells as a strategy for evaluating chemical susceptibility at different stages of differentiation to reduce animal testing in the context of the 3Rs.
Keywords: Developmental toxicity and neurotoxicity testing; Chemical susceptibility; Cell viability screening; Human pluripotent embryonal carcinoma cells Differentiation

Toxic effects of midazolam on differentiating neurons in vitro as a consequence of suppressed neuronal Ca 2+-oscillations - Sinner, Barbara; Friedrich, Oliver; Zausig, York; Bein, Thomas; Graf, Bernhard (Toxicology, 2011)
Background: In immature neurons anesthetics induce apoptosis and influence neuronal differentiation. Neuronal Ca -oscillations regulate differentiation and synaptogenesis. We examined the effects of the long-term blockade of hippocampal Ca -oscillations with midazolam on neuronal synapsin expression. Material and methods: Hippocampal neurons were incubated at day 15 in culture with the specific GABA receptor agonist muscimol (50μM) or with midazolam (100 and 300nM), respectively, for 24h. TUNEL and activated-Caspase-3 staining were used to detect apoptotic neurons. Ca -oscillations were detected using the Ca -sensitive dye FURA-2 and dual wavelength excitation fluorescence microscopy. Synapsin was identified with confocal anti-synapsin immunofluorescence microscopy. Results: Muscimol, when applied for 24h, decreased the amplitude and frequency Ca -oscillations significantly. Midazolam concentration-dependently suppressed the amplitude and frequency of the Ca -oscillations. This was associated by a downregulation of the synapsin expression 24h after washout. Conclusion: Neuronal Ca -oscillations mediate neuronal differentiation and are involved in synaptogenesis. By acting via the GABA receptor, midazolam exerts its toxic effect through the suppression of neuronal Ca -oscillations, a reduction in synapsin expression and consecutively reduced synaptic integrity. © 2011 Elsevier Ireland Ltd.
Keywords: Benzodiazepines; GABA A receptor; Neuronal differentiation; Neurotoxicity

Transient Receptor Potential Channel 6 (TRPC6) Is An Important Mediator Of Mechanical Stretch Responses In The Atrial Endocardial Endothelium - Nikolova-Krstevski, Vesna; Wagner, Sören; Friedrich, Oliver; Fatkin, Diane (American Heart Association, 2013)
Keywords: Atrial arrhythmia; Mechanical stress; Ca2+signalling

Transrectal Absorber Guide Raster-Scanning Optoacoustic Mesoscopy for Label-Free In Vivo Assessment of Colitis - Bühler, Adrian; Brown, Emma; Paulus, Lars-Philip; Eckstein, Markus; Thoma, Oana-Maria; Oraiopoulou, Mariam-Eleni; Rother, Ulrich; Hörning, André; Hartmann, Arndt; Neurath, Markus; Wölfle, Joachim; Friedrich, Oliver; et al. (Advanced Science, 2023)
Optoacoustic imaging (OAI) enables microscale imaging of endogenous chromophores such as hemoglobin at significantly higher penetration depths compared to other optical imaging technologies. Raster-scanning optoacoustic mesoscopy (RSOM) has recently been shown to identify superficial microvascular changes associated with human skin pathologies. In animal models, the imaging depth afforded by RSOM can enable entirely new capabilities for noninvasive imaging of vascular structures in the gastrointestinal tract, but exact localization of intra-abdominal organs is still elusive. Herein the development and application of a novel transrectal absorber guide for RSOM (TAG-RSOM) is presented to enable accurate transabdominal localization and assessment of colonic vascular networks in vivo. The potential of TAG-RSOM is demonstrated through application during mild and severe acute colitis in mice. TAG-RSOM enables visualization of transmural vascular networks, with changes in colon wall thickness, blood volume, and OAI signal intensities corresponding to colitis-associated inflammatory changes. These findings suggest TAG-RSOM can provide a novel monitoring tool in preclinical IBD models, refining animal procedures and underlines the capabilities of such technologies to address inflammatory bowel diseases in humans.
CRIS-Team WoS Importer:2023-05-12

Ultra-low-cost 3D bioprinting: Modification and application of an off-the-shelf desktop 3D-printer for biofabrication - Kahl, Melanie; Gertig, Markus; Hoyer, Phillipp; Friedrich, Oliver; Gilbert, Daniel (Frontiers in Bioengineering and Biotechnology, 2019)
3D bioprinting has become a versatile and powerful method in tissue engineering and regenerative medicine and is increasingly adapted by other disciplines due to its tremendous potential beyond its typical applications. However, commercially available 3D bioprinting systems are typically expensive circumventing the broad implementation, including laboratories in low-resource settings. To address the limitations of conventional and commercially available technology, we developed a 3D bioprinter by modification of an off-the-shelf 3D desktop printer, that can be installed within a single day, is of handy size to fit into a standard laminar flow hood, customizable, ultra-low cost and thus, affordable to a broad range of research labs, or educational institutions. We evaluate accuracy and reproducibility of printing results using alginate and alginate/gelatin-hydrogels and demonstrate its potential for biomedical use by printing of various two-and three-dimensional cell-free and mammalian cell-laden objects using recombinant HEKYFP cells, stably expressing yellow fluorescent protein (YFP) as a model system and high-content imaging. We further provide a parts list and 3D design files in STL and STEP format for reconstructing the device. A time-lapse video of the custom-built device during operation is available at https://vimeo.com/274482794.
CRIS-Team Scopus Importer:2019-08-09
Keywords: 3D desktop printing; Alginate and alginate/gelatin-based hydrogel; HEK293; Rapid prototyping; Ultra-low-cost bioprinting technology

Ultra-rapid activation and deactivation of store-operated Ca(2+) entry in skeletal muscle. - Edwards, Joshua N.; Murphy, Robyn M; Cully, Tanya R.; von Wegner, Frederic; Friedrich, Oliver; Launikonis, Bradley S. (Cell calcium, 2010)
Skeletal muscle is highly specialized for the rapid delivery of Ca(2+) to the contractile apparatus during excitation-contraction coupling (EC coupling). Previous studies have shown the presence of a relatively fast-activated store-operated Ca(2+) entry (SOCE) mechanism (<1s) to be present in skeletal muscle, unlike the situation occurring in non-excitable cells. We simultaneously imaged [Ca(2+)] in the t-system and cytoplasm in mechanically skinned fibers during SR Ca(2+) release and observed both cell-wide Ca(2+) release and Ca(2+) waves. SOCE activation followed cell-wide Ca(2+) release from high sarcoplasmic reticulum (SR) [Ca(2+)] ([Ca(2+)](SR)) by seconds, consistent with depletion of [Ca(2+)](SR) to an absolute threshold for SOCE and an unformed SOCE complex at high [Ca(2+)](SR). Ca(2+) waves occurred at low [Ca(2+)](SR), close to the threshold for SOCE, minimizing the time between Ca(2+) release and Ca(2+) influx. Local activation of SOCE during Ca(2+) waves occurred in approximately 27ms following local initiation of SR depletion indicating a steep relationship between [Ca(2+)](SR) and SOCE activation. Most of this delay was due to slow release of Ca(2+) from SR, leaving only milliseconds at most for the activation of Ca(2+) entry following store depletion. SOCE was also observed to deactivate effectively instantly during store refilling at low [Ca(2+)](SR). These rapid kinetics of SOCE persisted as subsequent Ca(2+) waves propagated along the fiber. Thus we show for the first time millisecond activation and deactivation of SOCE during low amplitude [Ca(2+)](SR) oscillations at low [Ca(2+)](SR). To account for the observed Ca(2+) movements we propose the SOCE complex forms during the progressive depletion of [Ca(2+)](SR) prior to reaching the activation threshold of SOCE and this complex remains stable at low [Ca(2+)](SR).
Keywords: Skeletal muscle; Excitation–contraction coupling; Ryanodine receptor; Store-operated Ca2+ entry; t-system; Sarcoplasmic reticulum

Understanding critical illness myopathy: approaching the pathomechanism. - Friedrich, Oliver; Fink, Rainer; Hund, Ernst (Journal of Nutrition, 2005)
Myopathies occurring in critically ill patients have gained increasing interest during the past years. For the patient, they represent a crucial factor for prolonged intensive care unit treatment and secondary complications. Critical illness myopathies (CIMs) seem to be related to various pathogenic factors. Among those, the septic inflammatory response syndrome seems to play a major role. It has been suggested that, similar to sepsis-related multiorgan failure, CIM might be considered a failure of the organ muscle. Muscle function might be impaired by proposed "myotoxic" humoral factors. These could be endogenously produced during the innate immune response to sepsis. This article follows up recent evidence for such active fractions in the blood serum of CIM patients. To explain muscle weakness in CIM, serum fractions acutely modified membrane excitability and subcellular Ca2+ regulation in an animal model. From the differential serum effects, early-phase CIM seems to involve a reduction in the overall force generation in muscle but also a compensation by the membrane, increasing the excitability. Different animal models will help to elucidate the underlying mechanisms accounting for the specific proteolytic activities found in different forms of CIM. CIM represents a systemic rather than a local disorder. Humoral factors might initiate the local reaction of skeletal muscle clinically seen as muscle weakness, altered excitability, and proteolysis of contractile proteins. Establishing the interactions in the excitation-contraction cascade in CIM is a challenging task, not only to clarify its pathomechanism but also to deduce clinical interventions.

Unloaded speed of shortening in voltage-clamped intact skeletal muscle fibers from wt, mdx, and transgenic minidystrophin mice using a novel high-speed acquisition system. - Friedrich, Oliver; Weber, Cornelia; von Wegner, Frederic; Chamberlain, Jeffrey S.; Fink, Rainer (Biophysical Journal, 2008)
Skeletal muscle unloaded shortening has been indirectly determined in the past. Here, we present a novel high-speed optical tracking technique that allows recording of unloaded shortening in single intact, voltage-clamped mammalian skeletal muscle fibers with 2-ms time resolution. L-type Ca(2+) currents were simultaneously recorded. The time course of shortening was biexponential: a fast initial phase, tau(1), and a slower successive phase, tau(2,) with activation energies of 59 kJ/mol and 47 kJ/mol. Maximum unloaded shortening speed, v(u,max), was faster than that derived using other techniques, e.g., approximately 14.0 L(0) s(-1) at 30 degrees C. Our technique also allowed direct determination of shortening acceleration. We applied our technique to single fibers from C57 wild-type, dystrophic mdx, and minidystrophin-expressing mice to test whether unloaded shortening was affected in the pathophysiological mechanism of Duchenne muscular dystrophy. v(u,max) and a(u,max) values were not significantly different in the three strains, whereas tau(1) and tau(2) were increased in mdx fibers. The results were complemented by myosin heavy and light chain (MLC) determinations that showed the same myosin heavy chain IIA profiles in the interossei muscles from the different strains. In mdx muscle, MLC-1f was significantly increased and MLC-2f and MLC-3f somewhat reduced. Fast initial active shortening seems almost unaffected in mdx muscle.

Upregulation of store-operated Ca2+ entry in dystrophic mdx mouse muscle. - Edwards, Joshua N.; Friedrich, Oliver; Cully, Tanya R.; von Wegner, Frederic; Murphy, Robyn M; Launikonis, Bradley S. (American journal of physiology. Cell physiology, 2010)
Store-operated Ca(2+) entry (SOCE) is an important mechanism in virtually all cells. In adult skeletal muscle, this mechanism is highly specialized for the rapid delivery of Ca(2+) from the transverse tubule into the junctional cleft during periods of depleting Ca(2+) release. In dystrophic muscle fibers, SOCE may be a source of Ca(2+) overload, leading to cell necrosis. However, this possibility is yet to be examined in an adult fiber during Ca(2+) release. To examine this, Ca(2+) in the tubular system and cytoplasm were simultaneously imaged during direct release of Ca(2+) from sarcoplasmic reticulum (SR) in skeletal muscle fibers from healthy (wild-type, WT) and dystrophic mdx mouse. The mdx fibers were found to have normal activation and deactivation properties of SOCE. However, a depression of the cytoplasmic Ca(2+) transient in mdx compared with WT fibers was observed, as was a shift in the SOCE activation and deactivation thresholds to higher SR Ca(2+) concentrations ([Ca(2+)](SR)). The shift in SOCE activation and deactivation thresholds was accompanied by an approximately threefold increase in STIM1 and Orai1 proteins in dystrophic muscle. While the mdx fibers can introduce more Ca(2+) into the fiber for an equivalent depletion of [Ca(2+)](SR) via SOCE, it remains unclear whether this is deleterious.

Vascularization of Poly-ε-Caprolactone-Collagen I-Nanofibers with or without Sacrificial Fibers in the Neurotized Arteriovenous Loop Model - Kratzer, Simon; Arkudas, Andreas; Himmler, Marcus; Schubert, Dirk W.; Schneidereit, Dominik; Bauer, Julian; Friedrich, Oliver; Horch, Raymund E.; Cai, Aijia (Cells, 2022)
Electrospun nanofibers represent an ideal matrix for the purpose of skeletal muscle tissue engineering due to their highly aligned structure in the nanoscale, mimicking the extracellular matrix of skeletal muscle. However, they often consist of high-density packed fibers, which might impair vascularization. The integration of polyethylene oxide (PEO) sacrificial fibers, which dissolve in water, enables the creation of less dense structures. This study examines potential benefits of poly-ε-caprolactone-collagen I-PEO-nanoscaffolds (PCP) in terms of neovascularization and distribution of newly formed vessels compared to poly-ε-caprolactone -collagen I-nanoscaffolds (PC) in a modified arteriovenous loop model in the rat. For this purpose, the superficial inferior epigastric artery and vein as well as a motor nerve branch were integrated into a multilayer three-dimensional nanofiber scaffold construct, which was enclosed by an isolation chamber. Numbers and spatial distribution of sprouting vessels as well as macrophages were analyzed via immunohistochemistry after two and four weeks of implantation. After four weeks, aligned PC showed a higher number of newly formed vessels, regardless of the compartments formed in PCP by the removal of sacrificial fibers. Both groups showed cell influx and no difference in macrophage invasion. In this study, a model of combined axial vascularization and neurotization of a PCL-collagen I-nanofiber construct could be established for the first time. These results provide a foundation for the in vivo implantation of cells, taking a major step towards the generation of functional skeletal muscle tissue.<br
Keywords: vascularization of nanofiber scaffolds; neurotization; neoangiogenesis; EPI loop model; AV loop model; PCL-collagen I-nanofiber scaffolds; polyethylene oxide

Velocity distributions of single F-actin trajectories from a fluorescence image series using trajectory reconstruction and optical flow mapping. - von Wegner, Frederic; Ober, Tobias; Weber, Cornelia; Schürmann, Sebastian; Winter, Rene; Friedrich, Oliver; Fink, Rainer; Vogel, Martin (Journal of Biomedical Optics, 2008)
We present an approach for the computation of single-object velocity statistics in a noisy fluorescence image series. The algorithm is applied to molecular imaging data from an in vitro actin-myosin motility assay. We compare the relative efficiency of wavelet and curvelet transform denoising in terms of noise reduction and object restoration. It is shown that while both algorithms reduce background noise efficiently, curvelet denoising restores the curved edges of actin filaments more reliably. Noncrossing spatiotemporal actin trajectories are unambiguously identified using a novel segmentation scheme that locally combines the information of 2-D and 3-D segmentation. Finally, the optical flow vector field for the image sequence is computed via the 3-D structure tensor and mapped to the segmented trajectories. Using single-trajectory statistics, the global velocity distribution extracted from an image sequence is decomposed into the contributions of individual trajectories. The technique is further used to analyze the distribution of the x and y components of the velocity vectors separately, and it is shown that directed actin motion is found in myosin extracts from single skeletal muscle fibers. The presented approach may prove helpful to identify actin filament subpopulations and to analyze actin-myosin interaction kinetics under biochemical regulatio

Vinculin phosphorylation at residues Y100 and Y1065 is required for cellular force transmission. - Auernheimer, Vera; Lautscham, Lena; Leidenberger, Maria; Friedrich, Oliver; Kappes, Bärbel; Fabry, Ben; Goldmann, Wolfgang (Journal of cell science, 2015)
The focal adhesion protein vinculin connects the actin cytoskeleton via talin and integrin with the extracellular matrix. Vinculin consists of a globular head and tail domain, which undergo conformational changes from a closed auto-inhibited conformation in the cytoplasm to an open conformation in focal adhesions. Src-phosphorylation has been suggested to regulate this conformational switch. To explore the role of phosphorylation in vinculin activation, we used knock-out mouse embryonic fibroblasts re-expressing different vinculin mutants in traction microscopy, magnetic tweezer microrheology, FRAP, and actin-binding assays. Compared to cells expressing wildtype or constitutively active vinculin, we found reduced tractions, cytoskeletal stiffness, adhesion strength, and increased vinculin dynamics in cells expressing constitutively inactive vinculin or vinculin where Src-phosphorylation was blocked by replacing tyrosine at position 100 and/or 1065 with non-phosphorylatable phenylalanine. Replacing tyrosines with phospho-mimicking glutamic acid restored cellular tractions, stiffness, adhesion strength as well as vinculin dynamics, and facilitated vinculin-actin binding. These data demonstrate that Src-phosphorylation is necessary for vinculin activation, and that phosphorylation controls cytoskeletal mechanics by regulating force transmission between the actin cytoskeleton and focal adhesion proteins.

Viscoelastic Measurements of Cells in a Rotational Rheometer - Dakhil, Haider; Wierschem, Andreas; Gilbert, Daniel; Amtmann, Anette; Hübner, Holger; Buchholz, Rainer; Friedrich, Oliver (Chemie Ingenieur Technik, 2015)
UnivIS-Import:2018-09-11:Pub.2015.tech.ITC.cbiove.viscoe

Weak by the machines: muscle motor protein dysfunction - a side effect of intensive care unit treatment. - Friedrich, Oliver; Diermeier, Stefanie; Larsson, Lars (Acta Physiologica, 2018)
Intensive care interventions involve periods of mechanical ventilation, sedation and complete mechanical silencing of patients. Critical illness myopathy (CIM) is an ICU-acquired myopathy that is associated with limb muscle weakness, muscle atrophy, electrical silencing of muscle and motor proteinopathy. The hallmark of CIM is a preferential muscle myosin loss due to increased catabolic and reduced anabolic activity. The ubiquitin proteasome pathway plays an important role, apart from recently identified novel mechanisms affecting non-lysosomal protein degradation or autophagy. CIM is not reproduced by pure disuse atrophy, denervation atrophy, steroid-induced atrophy or septic myopathy, although combinations of high-dose steroids and denervation can mimic CIM. New animal models of critical illness and ICU treatment (i.e. mechanical ventilation and complete immobilization) provide novel insights regarding the time course of protein synthesis and degradation alterations, and the role of protective chaperone activities in the process of myosin loss. Altered mechano-signalling seems involved in triggering a major part of myosin loss in experimental CIM models, and passive loading of muscle potently ameliorates the CIM phenotype. We provide a systematic overview of similarities and distinct differences in the signalling pathways involved in triggering muscle atrophy in CIM and isolated trigger factors. As preferential myosin loss is mostly determined from biochemistry analyses providing no spatial resolution of myosin loss processes within myofibres, we also provide first results monitoring myosin signal intensities during experimental ICU intervention using multi-photon Second Harmonic Generation microscopy. Our results confirm that myosin loss is an evenly distributed process within myofibres rather than being confined to hot spot
Keywords: second harmonic generation microscopy; skeletal muscle; critical illness; preferential myosin loss; myofibrillar proteins